Solar device with borosilicate glass and method thereof
By using a borosilicate glass composition with high content of SiO2, B2O3 and Al2O3, glass laminates with high thermal impact properties and crack resistance were prepared, which solved the problem of prone to cracking in and outside the existing automotive glass laminates.
Patent Information
- Application Number
- CN202380044775.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-15
- Filing Date
- 2023-06-15
- Publication Date
- 2025-02-07
AI Technical Summary
The thicker outer glass sheets in the existing automotive glass laminates are susceptible to heat impact and debris impact, and it is difficult to effectively improve their strength and heat resistance.
Using a borosilicate glass composition containing at least 74 mole % SiO2, 10 mole % B2O3 and Al2O3 such that the sum of SiO2, B2O3 and Al2O3 reaches at least 90 mole % liquid viscosity and 1725 are prepared by a fusion forming process. Glass laminates at °C or lower.
The thermal impact performance and crack resistance of the glass laminate are improved, and the spread of radial cracks and the formation of intermediate cracks are prevented, thereby enhancing the overall strength of the glass laminate.
Smart Images

Figure CN119403769A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority under 35 USC §119 to U.S. Provisional Application No. 63 / 352,531, filed on June 15, 2022, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0003] The present disclosure relates to glass compositions and glass articles made therefrom, and more particularly, to borosilicate glass compositions that can be fusion-formed at greater thicknesses and glass articles made therefrom. Background Art
[0004] Glass is used in windows because of its optical transparency and durability. Automotive and architectural glass can include a single glass ply or a laminate comprising two glass plies and an interlayer of polymeric material disposed therein. Particularly for automotive applications, there is a trend to use laminates to improve fuel economy and / or impact performance. Some laminate designs may employ thicker outer glass plies and thin inner glass plies. For example, the thicker glass plies may be soda-lime silicate glass, which is susceptible to thermal shock and is prone to cracking after impact via, for example, stones or other debris thrown from the road. Therefore, there is a need to improve the glass used as the thicker outer glass plies in laminates. Summary of the invention
[0005] According to one aspect, embodiments of the present disclosure relate to borosilicate glass compositions. Unless otherwise specified, the glass compositions disclosed herein are described as mole percent (mol %) analyzed in terms of oxides. In one or more embodiments, the borosilicate glass composition comprises at least 74 mol % SiO2, at least 10 mol % B2O3, and an amount of Al2O3 such that the sum of SiO2, B2O3, and Al2O3 is at least 90 mol %. In one or more embodiments, the borosilicate glass composition has a liquidus viscosity greater than 500 kP. In one or more embodiments, the borosilicate glass composition has a temperature of 1725°C or less when the viscosity of the borosilicate glass composition is 200P.
[0006] According to another aspect, embodiments of the present disclosure relate to a glass ply. The glass ply has a first major surface and a second major surface opposite the first major surface. The glass ply is made from one or more embodiments of the borosilicate glass composition described herein.
[0007] According to another aspect, embodiments of the present disclosure relate to a laminate. The laminate includes a first glass ply according to one or more embodiments of the glass plies described herein. The laminate also includes a second glass ply and an interlayer bonding the first glass ply to the second glass ply.
[0008] According to another aspect, embodiments of the present disclosure relate to automotive glazing. The automotive glazing is made from a laminate according to the laminate described previously.
[0009] According to another aspect, embodiments of the present disclosure relate to a vehicle. The vehicle includes a body that defines an interior of the vehicle, and at least one opening and an automotive glass window as described above disposed in the at least one opening. In the vehicle, the second glass ply is disposed to face the interior of the vehicle, and the first glass ply faces the exterior of the vehicle. In one or more embodiments, the first glass ply is disposed to face the interior of the vehicle, and the second glass ply faces the exterior of the vehicle.
[0010] According to another aspect, embodiments of the present disclosure relate to a method for forming a glass ply. The glass ply has a first major surface and a second major surface. In the method, a groove in an overflow trough overflows with at least two streams of a borosilicate glass composition having a liquidus viscosity greater than 500 kP and a temperature less than 1725°C when the viscosity of the glass composition is 200 P. In one or more embodiments, the borosilicate glass composition comprises at least 74 mol % SiO2 and at least 10 mol % B2O3. In addition, in one or more embodiments, the total amount of SiO2, B2O3, and Al2O3 contained in the composition is at least 90 mol %. In one or more embodiments of the method, the at least two streams of the borosilicate glass composition are fused at the root of the overflow trough to form a glass ply having a thickness of at least 2 mm between the first major surface and the second major surface.
[0011] According to another aspect, embodiments of the present disclosure relate to a glass ply. The glass ply has a first major surface and a second major surface opposite the first major surface. The glass ply is made of a borosilicate glass composition. When the glass ply is subjected to a quasi-static 2 kgf indentation load with a Vickers tip, the glass ply exhibits an annular crack and a plurality of radial cracks, and each of the plurality of radial cracks is bounded by the annular crack.
[0012] According to another aspect, an embodiment of the present disclosure is directed to a glass laminate. The glass laminate includes a first glass ply, a second glass ply, and an interlayer. The first glass ply has a first major surface and a second major surface opposite the first major surface. The first glass ply is made of a borosilicate glass composition. The second glass ply has a third major surface and a fourth major surface opposite the third major surface. The interlayer bonds the second major surface of the first glass ply to the third major surface of the second glass ply. The borosilicate glass composition includes at least 74 mol % SiO2, at least 10 mol % B2O3, and an amount of Al2O3 such that the sum of SiO2, B2O3, and Al2O3 is at least 90 mol %.
[0013] According to another embodiment, an embodiment of the present disclosure is directed to a system comprising a sensor and a glass laminate. The glass laminate comprises a first glass ply having a first major surface and a second major surface opposite the first major surface. The first glass ply is made of a borosilicate glass composition. The glass laminate comprises a second glass ply having a third major surface and a fourth major surface opposite the third major surface. The interlayer bonds the second major surface of the first glass ply to the third major surface of the second glass ply. The borosilicate glass composition comprises at least 74 mol % SiO2, at least 10 mol % B2O3, and an amount of Al2O3 such that the sum of SiO2, B2O3 and Al2O3 is at least 90 mol %. The sensor is configured to receive, transmit, or simultaneously receive and transmit a signal through the glass laminate, and the signal has a peak wavelength in the range of 400 nm to 750 nm or in the range of 1500 nm or more.
[0014] According to another aspect, an embodiment of the present disclosure is directed to a glass laminate. The glass laminate includes a first glass ply having a first major surface and a second major surface opposite the first major surface. The first glass ply is a fusion-formed borosilicate glass composition. The glass laminate also includes a second glass ply having a third major surface and a fourth major surface opposite the third major surface. In addition, the glass laminate includes an interlayer that bonds the second major surface of the first glass ply to the third major surface of the second glass ply. The transmission of ultraviolet light in the wavelength range of 300-380 nm through the glass laminate is 75% or less. The transmission of light in the visible light spectrum through the glass laminate is 73% or greater, and the total sunlight transmission through the glass laminate is 61% or less.
[0015] According to another aspect, an embodiment of the present disclosure is directed to a glass composition consisting of: an amount of SiO2 ranging from about 72 mol% to about 80 mol%, an amount of Al2O3 ranging from about 2.5 mol% to about 5 mol%, and an amount of B2O3 ranging from about 11.5 mol% to about 14.5 mol%. The glass composition has a liquidus viscosity greater than 500 kP; and when the viscosity of the borosilicate glass composition is 200P, the glass composition has a temperature of 1725°C or less.
[0016] According to another aspect, embodiments of the present disclosure are directed to a glass composition consisting of 74 mol % to 80 mol % SiO2, 2.5 mol % to 5 mol % Al2O3, 11.5 mol % to 14.5 mol % B2O3, 4.5 mol % to 8 mol % Na2O, 0.5 mol % to 3 mol % K2O, 0.5 mol % to 2.5 mol % MgO, and 0 mol % to 4 mol % CaO.
[0017] Other features and advantages of the present invention are set forth in the following detailed description, some of which will be readily apparent to those skilled in the art from the description or recognized by practicing the various embodiments described herein, including the following detailed description, claims, and accompanying drawings.
[0018] It is to be understood that both the foregoing general description and the following detailed description are merely exemplary, and are intended to provide an overview or framework for understanding the nature and character of the claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings provide a further understanding and are incorporated in and constitute a part of this specification. The drawings illustrate one or more embodiments and together with the description serve to explain the principles and operations of the various embodiments. In the drawings:
[0020] Figure 1 is a view of a vehicle including a glass article or laminate according to one or more embodiments;
[0021] Figure 2 is a side view of a glass article according to one or more embodiments;
[0022] Figure 3 is a side view showing a laminate including a glass article according to one or more embodiments;
[0023] Figure 4 is a side view of a laminate including a glass article according to one or more embodiments;
[0024] Figures 5A-5CMicroscope images of cracks resulting from indentation testing and related images showing the following: Disclosed fusion-formed borosilicate glass compositions ( Figure 5A ), compared with the soda-lime silicate glass composition ( Figure 5B ), and comparative float formed borosilicate glass compositions ( Figure 5C );
[0025] Fig. 6A and 6B Results of thermal shock testing are shown for the disclosed fusion-formed borosilicate glass compositions ( Fig. 6A ) and comparative soda-lime-silicate glass compositions ( Figure 6B );
[0026] Figure 7 shows a fusion forming apparatus for fusion forming a glass ply of a borosilicate glass composition according to an exemplary embodiment;
[0027] Figure 8 A graph showing solar transmittance of various borosilicate glass compositions according to an exemplary embodiment;
[0028] Fig. 9 A system according to an exemplary embodiment is shown, comprising a sensor configured to send and receive signals through a glass laminate having at least one glass ply made from a borosilicate glass composition;
[0029] Fig.10 and 11 showing a graph of visible light, total solar light, and ultraviolet light transmission as a function of iron content in glass according to an exemplary embodiment; and
[0030] Fig.12 and 13 A graph showing visible light transmission versus total solar transmission for glass compositions according to exemplary embodiments.
[0031] Fig.14 is a digital image of a cross-section of a glass article according to an exemplary embodiment.
[0032] Fig.15 Graphs 1 and 2 are transmission measurements of two example compositions according to an exemplary embodiment.
[0033] Fig.16 is a graph of retained strength measurements after indentation of samples constructed using example compositions described herein both before and after thermal shock, according to an exemplary embodiment.
[0034] Fig.17A is an image of a sample constructed from an example composition according to the present disclosure having a scratch from a Knoop scratch test, according to an exemplary embodiment.
[0035] Fig. 17B is an image of a sample constructed from a counterexample composition according to the present disclosure having a scratch from a Knoop scratch test, according to an exemplary embodiment.
[0036] Fig. 17C is an image of a sample constructed from a counterexample composition according to the present disclosure having a scratch from a Knoop scratch test, according to an exemplary embodiment.
[0037] Fig.18 A schematic cross-sectional side view of an embodiment of a solar panel 10 is provided having one or more substrates from the borosilicate composition described herein incorporating various aspects of the present disclosure.
[0038] Fig.19A -C According to one or more embodiments of the present disclosure, various schematic embodiments of enlarged cross-sectional side views of aspects are provided, which incorporate the borosilicate composition of the embodiments of the present disclosure into a layer in a solar module of various configurations ( Fig.19A and 19B ) and as a retrofit cover configured to attach to a surface of a solar panel ( Fig.19C ).
[0039] Fig. 20 Transmission data for iron-free borosilicate glass and clear soda-lime silicate glass are provided, plotted as percent transmittance versus wavelength (300 nm to 800 nm). According to one or more aspects of the present disclosure, each glass sample is constructed to the same thickness.
[0040] Fig.21 According to one or more aspects of the present disclosure, a series of SEM images at 20,000X magnification are provided of the surfaces of two glass samples: (1) soda-lime silicate glass (top row) versus (2) a borosilicate glass composition embodiment described in detail above (bottom row), under three conditions: initial state before weathering (Initial State); after weathering; and after weathering and cleaning.
[0041] Fig. 22 A comparative analysis according to one or more aspects of the present disclosure is provided that provides examples of how borosilicate glass compositions according to embodiments herein behave with respect to weathering and cleaning after scratch testing.
[0042] Fig.23According to one or more aspects of the present disclosure, comparative analysis from microscope images at 100X magnification showing spot and scratch damage on some samples from a proxy analysis from the automotive field is provided.
[0043] Fig.24 According to one or more aspects of the present disclosure, there is provided Fig.23 Comparative analysis of the samples, shown as confocal microscopy images, except that the confocal microscopy images were taken after abrasion (top row) and then after the weathering and cleaning process (bottom row).
[0044] Figures 25A to 25C Three separate % transmission diffusion graphs over the visible light spectrum (nm) are provided according to one or more aspects of the present disclosure and show that borosilicate glass after linear abrasion ( Fig.25A ), after linear wear followed by weathering ( Fig.25B ), and after linear wear followed by weathering and then washing ( Fig.25C )Maintain transmissive support.
[0045] Fig.26A According to one or more aspects of the present disclosure, crack behavior under subcritical stress is shown by performing a ring-on-ring test of 3 kgf Vickers indentation glass under subcritical crack growth stress at different applied stresses (30 MPa and 35 MPa) for two groups of samples. Fig.26B Two representative images taken with the initial view of the sample are shown ( Fig.26B top) and representative views of the images after the run ( Fig.26B bottom).
[0046] Fig. 27 and 28 According to one or more embodiments of the present disclosure, according to one or more aspects of the present disclosure, the following schematic support is provided: one or more borosilicate glass compositions of the present disclosure can be obtained by thermal tempering ( Fig. 27 ) or ion exchange ( Fig.28 ) is strengthened by at least one of the following. DETAILED DESCRIPTION
[0047] Reference is made in detail to various embodiments, examples of which are shown in the accompanying drawings. The borosilicate glass compositions of the present disclosure are capable of being fused-formed or fused-formed into glass sheets having a thickness of at least 2 mm, specifically: at least 3 mm, at least 3.3 mm, or at least 3.8 mm. In an embodiment, the borosilicate glass composition comprises at least 74 mol % SiO2, at least 10 mol % B2O3, and at least some Al2O3, and in an embodiment, the total amount of SiO2, B2O3, and Al2O3 is at least 90 mol %. The borosilicate glass compositions described herein exhibit a liquidus viscosity of at least 500 kilopoise (kP), and a temperature (T ) at which the viscosity is 200 poise (P). 200P ) is 1725℃ or lower.
[0048] In addition, the embodiments of the borosilicate glass compositions disclosed herein are particularly suitable for use as laminates for automotive glazing applications. In one or more embodiments, the borosilicate glass compositions are used as outer layers in such laminates. Compared to conventional automotive glazings containing soda-lime-silicate glass layers, the glass layers made from the disclosed borosilicate glass compositions are densified during deformation, which helps prevent the formation (initiation) or spreading (propagation) of radial or median cracks that tend to impair the strength of the glass layers. In addition, the borosilicate glass compositions disclosed herein are more resistant to thermal shock than soda-lime-silicate glass, which also helps prevent crack initiation and propagation. These performance advantages can be useful when the borosilicate glass compositions are used as inner or outer glass layers of a glass laminate. In some cases, these performance advantages are particularly useful when the borosilicate glass compositions are used as outer glass layers in a laminate. These and other aspects and advantages of the disclosed borosilicate glass compositions and the products formed therefrom will be discussed in more detail below. The embodiments discussed herein are presented in an illustrative and non-restrictive manner.
[0049] This article involves Figure 1The vehicle 100 shown is used to describe an embodiment of the borosilicate glass composition. The vehicle 100 includes a body 110 defining an interior and at least one opening 120 communicating with the interior. The vehicle 100 also includes an automotive glass window 130, i.e., a window, disposed in the opening 120. The automotive glass window includes at least one ply of the borosilicate glass composition described herein. The automotive glass window 130 may form at least one of the following in the vehicle 100: a sidelight, a windshield, a rear window, a window, and a sunroof. In some embodiments, the vehicle glass window 130 may form an interior partition (not shown) in the interior of the vehicle 100, or may be disposed on an exterior surface of the vehicle 100 and form, for example, an engine block cover, a headlight cover, a taillight cover, a door panel cover, or a pillar cover. As used herein, a vehicle includes: a vehicle (examples of which are Figure 1 As shown), locomotives, trains, boats, ships, as well as airplanes, helicopters, drones and spacecraft, etc. In addition, although the present disclosure is based on a vehicle as a framework, the borosilicate glass composition can be used in other environments, such as architectural glass windows or bulletproof glass window applications.
[0050] like Figure 2 As shown, in embodiments, the automotive glazing 130 includes at least one glass ply 200 that includes, consists of, or consists essentially of an embodiment of the borosilicate glass composition described herein. In one or more embodiments, the automotive glazing 130 includes only a single glass ply 200 (i.e., a single glass ply is sometimes referred to as a monolith in the industry). Figure 2 As can be seen, glass ply 200 has a first major surface 202 and a second major surface 204. First major surface 202 is opposite second major surface 204. Secondary surface 206 extends around the perimeter of glass ply 200 and connects first major surface 202 and second major surface 204.
[0051] A first thickness 210 is defined between the first major surface 202 and the second major surface 204. In embodiments, the first thickness 210 is: at least 0.5 mm, at least 1 mm, at least 2 mm, at least 3 mm, at least 3.3 mm, or at least 3.8 mm.In one or more embodiments, the first thickness 210 is in the range of about 0.1 mm to about 6 mm, 0.2 mm to about 6 mm, 0.3 mm to about 6 mm, 0.4 mm to about 6 mm, 0.5 mm to about 6 mm, 0.6 mm to about 6 mm, 0.7 mm to about 6 mm, 0.8 mm to about 6 mm, 0.9 mm to about 6 mm, 1 mm to about 6 mm, 1.1 mm to about 6 mm, 1.2 mm to about 6 mm, 1.3 mm to about 6 mm, 1.4 mm to about 6 mm, 1.5 mm to about 6 mm, 1.6 mm to about 6 mm, about 1.8 mm to about 6 mm, about 2 mm to about 6 mm, about 2 mm to about 6 mm, about 3 mm to about 6 mm, about 4 mm to about 6 mm, about 5 mm to about 6 mm, about 6 mm to about 8 mm, about 7 mm to about 8 mm, about 9 mm to about 10 mm, about 11 mm to about 12 mm, about 13 mm to about 14 mm, about 15 mm to about 16 mm, about 17 mm to about 18 mm, about 19 mm to about 19 mm, about 20 mm to about 21 mm, about 21 mm to about 6mm, about 2.4mm to about 6mm, about 2.6mm to about 6mm, about 2.8mm to about 6mm, about 3mm to about 6mm, about 3.1mm to about 6mm, about 3.2mm to about 6mm, about 3.3mm to about 6mm, about 3.4mm to about 6mm, about 3.5mm to about 6mm, about 3.6mm to about 6mm, about 3.7mm to about 6mm, about 3.8mm to about 6mm, about 3.9mm to about 6mm, about 4mm to about 6mm, about 4.2mm to about 6mm, about 4.4mm to about 6mm, about 4.5mm to about 6mm, about 4.6mm to about 6mm, about 4.8mm to about 6mm, about 5 mm to about 6 mm, about 5.2 mm to about 6 mm, about 5.4 mm to about 6 mm, about 5.5 mm to about 6 mm, about 5.6 mm to about 6 mm, about 5.8 mm to about 6 mm, about 1.6 mm to about 5.8 mm, about 1.6 mm to about 5.6 mm, about 1.6 mm to about 5.5 mm, about 1.6 mm to about 5.4 mm, about 1.6 mm to about 5.2 mm, about 1.6 mm to about 5 mm, about 1.6 mm to about 4.8 mm, about 1.6 mm to about 4.6 mm, about 1.6 mm to about 4.4 mm, about 1.6 mm to about 4.2 mm, about 1.6 mm to about 4 mm, about 1.6 mm to about 3.9 mm m, about 1.6 mm to about 3.8 mm, about 1.6 mm to about 3.7 mm, about 1.6 mm to about 3.6 mm, about 1.6 mm to about 3.5 mm, about 1.6 mm to about 3.4 mm, about 1.6 mm to about 3.3 mm, about 1.6 mm to about 3.2 mm, about 1.6 mm to about 3.1 mm, about 1.6 mm to about 3 mm, about 1.6 mm to about 2.8 mm, about 1.6 mm to about 2.6 mm, about 1.6 mm to about 2.4 mm, about 1.6 mm to about 2.2 mm, about 1.6 mm to about 2 mm, about 1.6 mm to about 1.8 mm, about 3 mm to about 5 mm, or about 3 mm to about 4 mm. In other embodiments, the glass plies can be thinner than 2 mm or thicker than 6 mm.
[0052] In some embodiments, the glass plies can have curvature, such as a rounded geometry or a tubular shape, for example, where the first major surface is the outer surface of the tube and the second major surface is the inner surface of the tube. In some embodiments, the perimeter of the glass plies is generally linear, while in other embodiments, the perimeter is a complex shape. The first major surface can have an orifice, a slit, a hole, a protrusion, a pit, or other geometric shape.
[0053] As will be discussed in more detail below, in one or more embodiments, the glass ply 200 is a fusion-formed borosilicate glass composition having a liquidus viscosity of at least 500 kP and a T of 1725° C. or less. 200P .
[0054] Figure 3 An embodiment of an automotive glass window 130 is shown, wherein the automotive glass window 30 comprises Figure 2 As mentioned above, the glass ply 200 can include, consist of, or consist essentially of an embodiment of the borosilicate glass composition described herein. Figure 3 In the illustrated embodiment, the first glass ply 310 is bonded to the second glass ply 320 via the interlayer 330. Specifically, the second glass ply 320 has a third major surface 332 and a fourth major surface 334. The third major surface 332 is opposite to the fourth major surface 334. The minor surface 336 extends around the perimeter of the second glass ply 320 and connects the third major surface 332 and the fourth major surface 334.
[0055] A second thickness 340 is defined between third major surface 332 and fourth major surface 334. In an embodiment, second thickness 340 is less than first thickness 210 of first glass ply 310. In an embodiment, second glass thickness is 2 mm or less. In an embodiment, total glass thickness (i.e., first thickness 210 plus second thickness 340) is: 8 mm or less, 7 mm or less, 6.5 mm or less, 6 mm or less, 5.5 mm or less, or 5 mm or less. In an embodiment, the lower limit of total glass thickness is about 2 mm.
[0056] In an embodiment, the second glass ply 320 comprises a glass composition different from the borosilicate glass composition of the first glass ply 310. In an embodiment, the second glass composition comprises a soda-lime-silicate glass composition, an aluminosilicate glass composition, an alkali aluminosilicate glass composition, an alkali-containing borosilicate glass composition, an alkali aluminophosphosilicate glass composition, or an alkali aluminoborosilicate glass composition.
[0057] In addition, in embodiments, the first glass ply 310 and / or the second glass ply 320 may be strengthened. For example, the first glass ply 310 and / or the second glass ply 320 may be thermally strengthened, chemically strengthened, and / or mechanically strengthened. Specifically, in embodiments, the first glass ply 310 and / or the second glass ply 320 are chemically strengthened by an ion exchange process. In one or more embodiments, the first glass ply 310 and / or the second glass ply 320 are mechanically strengthened by utilizing a mismatch in thermal expansion coefficients between portions of the ply to create a compressive stress region and a central region exhibiting tensile stress. In some embodiments, the first glass ply 310 and / or the second glass ply 320 may be thermally strengthened by heating the glass ply to a temperature above the glass transition point and then rapidly quenching. In some embodiments, various combinations of chemical strengthening, mechanical strengthening, and thermal strengthening may be used to strengthen the second glass ply 320. In one or more embodiments, the second glass ply 320 is strengthened while the first glass ply 310 is not strengthened (but may optionally be annealed), and exhibits a surface compressive stress of less than about 3 MPa, or about 2.5 MPa or less, 2 MPa or less, 1.5 MPa or less, 1 MPa or less, or about 0.5 MPa or less.
[0058] In one or more embodiments, the interlayer 330 bonds the second major surface 204 of the first glass ply 310 to the third major surface 332 of the second glass ply 320. In an embodiment, the interlayer 330 includes a polymer, such as at least one of polyvinyl butyral (PVB), acoustic PVB (APVB), ionomer, ethylene vinyl acetate (EVA) and thermoplastic polyurethane (TPU), polyester (PE) or polyethylene terephthalate (PET), etc. The thickness of the interlayer can range from about 0.5 mm to about 2.5 mm, specifically about 0.7 mm to about 1.5 mm. In other embodiments, the thickness can be less than 0.5 mm or greater than 2.5 mm. In addition, in an embodiment, the interlayer 330 can include a polymer layer or film that provides various functions for the laminate structure 300. For example, the interlayer 330 can integrate at least one of the following: display features, solar insulation, sound insulation, antennas, anti-glare treatment or anti-reflection treatment, etc. In a specific embodiment, the intermediate layer 330 is modified to provide: ultraviolet (UV) absorption, infrared (IR) absorption, IR reflection, acoustic control / sound absorption, adhesion promotion and color. The intermediate layer 330 can be modified by suitable additives (e.g., dyes, pigments, dopants, etc.) to impart the desired properties.
[0059] In one or more embodiments, in addition to or in lieu of the functional or decorative film of the intermediate layer 330, a functional or decorative coating may be provided for the first glass ply 310 or the second glass ply 320. In an embodiment, the coating is at least one of an infrared reflective (IRR) coating, a glass frit, an anti-reflective coating, or a pigment coating. In an example embodiment of IRR, the second major surface 204 of the first glass ply 310 or the third major surface 332 of the second glass ply 320 is coated with an infrared reflective film, and optionally one or more layers of transparent dielectric film. In an embodiment, the infrared reflective film comprises a conductive metal (e.g., silver, gold, or copper) that reduces heat transmission through the coated plies 310, 320. In an embodiment, the optional dielectric film may be used to anti-reflect the infrared reflective film and control other properties and characteristics of the coating (e.g., color and durability). In an embodiment, the dielectric film comprises one or more oxides of zinc, tin, indium, bismuth, and titanium, among others. In an example embodiment, the IRR coating comprises one or two layers of silver, each layer being sandwiched between two layers of transparent dielectric film. In an embodiment, the IRR coating is applied using, for example, physical or chemical vapor deposition or via lamination.
[0060] In an embodiment, one or both of the first glass ply 310 and the second glass ply 320 include glass frit. In an embodiment, the glass frit is applied to, for example, the second major surface 204 of the first glass ply 310, the third major surface 332 of the second glass ply 320, and / or the fourth major surface 334 of the second glass ply 320. In an embodiment, the glass frit provides a reinforced bonding surface for an adhesive (e.g., an interlayer 330) or an adhesive that joins the glass window 130 to a bonding surface that defines an opening 120 in the vehicle body 110. In addition, in an embodiment, the glass frit provides a decorative frame for the glass window 130. In addition, in an embodiment, the glass frit can be used as a supplement to the IRR coating described above. In an embodiment, the glass frit is an enamel glass frit. In other embodiments, the glass frit is designed to be ion exchangeable. That is, the glass frit can be applied to the ion exchangeable glass before the ion exchange treatment. Such glass frit is configured to allow the exchange of ions between the glass and the treatment bath. In an embodiment, the glass frit is: Bi-Si-B alkaline system, Zn-based Bi system, Bi-Zn system, Bi system, Si-Zn-B-Ti system without Bi or with a small amount of Bi, Si-Bi-Zn-B-alkaline system and / or Si-Bi-Ti-B-Zn-alkaline system, etc. An example of an ion-exchangeable glass frit containing a colorant includes: 45.11 mol% Bi2O3, 20.61 mol% SiO2, 13.56 mol% Cr2O3, 5.11 mol% CuO, 3.48 mol% MnO, 3.07 mol% ZnO, 2.35 mol% B2O3, 1.68 mol% TiO2, 1.60 mol% Na2O, 1.50 mol% Li2O, 0.9 1 mol % K2O, 0.51 mol % Al2O3, 0.15 mol % P2O5, 0.079 mol % SO3, 0.076 mol % BaO, 0.062 mol % ZrO2, 0.060 mol % Fe2O3, 0.044 mol % MoO3, 0.048 mol % CaO, 0018 mol % Nb2O5, 0.006 mol % Cl, and 0.012 mol % SrO. Other examples of ion-exchangeable glass frits are disclosed in U.S. Pat. No. 9,346,708B2 (Application No. 13 / 464,493, filed May 4, 2012) and U.S. Publication No. 2016 / 0002104A1 (Application No. 14 / 768,832, filed August 19, 2015), both of which are incorporated herein by reference in their entirety.
[0061] In an embodiment, the second glass ply 320 can be provided with a colorant coating comprising an ink (e.g., an organic ink). In an embodiment particularly suitable for such a colorant coating, the colorant coating is applied to the third major surface 332 of the second glass ply 320 or the fourth major surface 334 of the second glass ply 320, and the second glass ply 320 is cold formed against the first glass ply 310. Advantageously, such a colorant coating can be applied to the second glass ply 320 when the second glass ply 320 is in a planar configuration, and the second glass ply 320 can then be cold formed into a curved configuration without disturbing the colorant coating (e.g., an organic ink coating). In an embodiment, the colorant coating comprises at least one pigment, at least one mineral filler, and a binder comprising an alkoxysilane functionalized isocyanurate or an alkoxysilane functionalized biuret. Examples of such a colorant coating are described in European Patent No. 2617690B1, which is incorporated herein by reference in its entirety. Other suitable colorant coatings and methods for applying colorant coatings are described in U.S. Publication No. 2020 / 0171800A1 (application number 16 / 613,010, filed on November 12, 2019) and U.S. Patent No. 9,724,727 (application number 14 / 618,398, filed on February 10, 2015), both of which are incorporated herein by reference in their entirety.
[0062] In an embodiment, the coating is an anti-reflective coating. In a specific embodiment, the anti-reflective coating is applied to the fourth major surface 334 of the second glass ply 320. In an embodiment, the anti-reflective coating comprises multiple layers of low and high refractive index materials, or multiple layers of low, medium and high refractive index materials. For example, in an embodiment, the anti-reflective coating comprises two to twelve layers of alternating low and high refractive index materials, such as silicon dioxide (low refractive index) and niobium oxide (high refractive index). In another example embodiment, the anti-reflective coating comprises three to twelve layers of repeating low, medium and high refractive index materials, such as silicon dioxide (low refractive index), aluminum oxide (medium refractive index) and niobium oxide (high refractive index). In other embodiments, the low refractive index material in the stack can be an ultra-low refractive index material, such as magnesium fluoride or porous silica. Generally speaking, an anti-reflective coating with more layers in the stack will perform better at higher angles of incidence than an anti-reflective coating with fewer layers in the stack. For example, at an incident angle greater than 60°, for example, an anti-reflective coating stack having four layers may perform better (less reflection) than an anti-reflective coating stack having two layers. In addition, in embodiments, an anti-reflective coating stack having an ultra-low refractive index material may perform better (less reflection) than an anti-reflective coating stack having a low refractive index material. Other anti-reflective coatings known in the art may also be suitable for use in stack 300.
[0063] In an embodiment, at least along a first axis, the glass ply 200 or laminate 300 exhibits at least one curvature including a radius of curvature of 300 mm to about 10 m. In an embodiment, along a second axis that is transverse to the first axis (specifically, perpendicular to the first axis), the glass ply 200 or laminate 300 exhibits at least one curvature including a radius of curvature of 300 mm to about 10 m. In other embodiments, the glass ply exhibits curvature, but the curvature has a radius of curvature of less than 300 μm or greater than 10 m. In some embodiments, the curvature is complex and varied.
[0064] In an embodiment, curvature (s) is introduced into the glass ply 200 or each glass ply 310, 320 of the glass laminate 300 by a thermal process. The thermal process may include a sagging process that uses gravity to shape the heated glass ply 200 or glass ply 310, 320. In the sagging step, a glass ply (e.g., glass ply 200) is placed on a mold having an open interior that is heated in a furnace (e.g., a box furnace or a annealing furnace) and is naturally and gradually sagged into the open interior of the mold under the influence of gravity. In one or more embodiments, the thermal process may include a pressing process that uses a mold to shape the glass ply 200 or glass ply 310, 320 while being heated or while being heated. In some embodiments, two glass plies (e.g., glass plies 310, 320) are formed together in a "pair forming" process. In such a process, a glass ply is placed one on top of another to form a stack (possibly with an intervening release layer) which is placed on a mold. In an embodiment, to facilitate the pair forming process, the glass plies 310, 320 used as the inner and / or thinner glass plies have a pair forming temperature (10 11 The temperature of the glass sheets 310, 320 when parked is greater than that of the outer and / or thicker glass sheets 310, 320.
[0065] In one or more embodiments, the mold may have an open interior for the bending process. Both the stack and the mold are heated by placing them in a furnace and gradually heating the stack to the bending or sagging temperature of the glass plies. During this process, the glass plies are formed together into a curved shape. Advantageously, at least some of the borosilicate glass compositions disclosed herein have a viscosity curve between 10 11 The poise viscosity is similar to conventional float-formed borosilicate glass compositions, allowing existing facilities and techniques to be used to form glass ply 200 or plies 310 , 320 .
[0066] According to an exemplary embodiment, the heating time and temperature are selected to obtain the desired degree of curvature and final shape. Afterwards, the glass ply or multiple glass plies are removed from the furnace and cooled. For glass plies formed in pairs, the two glass plies are separated, reassembled with an interlayer (e.g., interlayer 330) between the glass plies, and heated, for example, under vacuum, so that the glass plies and the interlayer are sealed together into a laminate.
[0067] In one or more embodiments, only one glass ply is bent using heating (e.g., by a sagging process or a pressing process), while the other glass ply is bent using a cold forming process (by pressing the glass ply to be bent to conform to the already bent glass ply) at a temperature less than the softening temperature of the glass composition (specifically, a temperature of 200° C. or less, 100° C. or less, 50° C. or less, or room temperature). The pressure to cold-form the glass ply against the other glass ply can be provided by, for example, vacuum, mechanical pressing, or one or more clamps. The cold-formed glass ply can be held in conformity with the already bent glass ply via an interlayer and / or mechanical clamping or any other connection.
[0068] Figure 4 An exemplary embodiment of a curved glass laminate 400 is shown. Figure 4 As can be seen, second major surface 204 of first glass ply 310 has a first depth of curvature 410 defined as a maximum depth relative to the flatness (dashed line) of second major surface 204. In embodiments where second glass ply 320 is curved, fourth major surface 334 of second glass ply 320 has a second depth of curvature 420 defined as a maximum depth relative to the flatness (dashed line) of fourth major surface 334.
[0069] In an embodiment, one or both of the first depth of curvature 410 and the second depth of curvature 420 is about 2 mm or greater. The depth of curvature may be defined as the maximum distance that a surface is orthogonal to a plane defined by a point on the perimeter of the surface. For example, one or both of the first depth of curvature 410 and the second depth of curvature 420 may range from about 2 mm to about 30 mm. In an embodiment, the first depth of curvature 410 and the second depth of curvature 420 are substantially equal to each other. In one or more embodiments, the first depth of curvature 410 is within 10% of the second depth of curvature 420, and more specifically, within 5% of the second depth of curvature 420. For illustration, the second depth of curvature 420 is about 15 mm, while the first depth of curvature 410 ranges from about 13.5 mm to about 16.5 mm (or is within 10% of the second depth of curvature 420).
[0070] In one or more embodiments, the shape deviation between the first curved glass ply 310 and the second curved glass ply 330, which includes them (the first curved glass ply 310 and the second curved glass ply 320), is ±5 mm or less, which is measured by an optical 3D scanner (e.g., an ATOS triple scanner supplied by GOM in Braunschweig, Germany). In one or more embodiments, the shape deviation is measured between the second major surface 204 and the third major surface 332 or between the first major surface 202 and the fourth major surface 334. In one or more embodiments, the shape deviation between the first glass ply 310 and the second glass ply 320 is about ±4 mm or less, about ±3 mm or less, about ±2 mm or less, about ±1 mm or less, about ±0.8 mm or less, about ±0.6 mm or less, about ±0.5 mm or less, about ±0.4 mm or less, about ±0.3 mm or less, about ±0.2 mm or less, or about ±0.1 mm or less. As used herein, shape deviation applies to stacked glass plies (i.e., without an interlayer) and refers to the maximum deviation from a desired curvature between coordinate locations on the respective second major surface 204 and third major surface 332 or on the first major surface 202 and fourth major surface 334.
[0071] In one or more embodiments, one or both of the first major surface 202 and the fourth major surface 334 exhibit minimal optical distortion. For example, one or both of the first major surface 202 and the fourth major surface 334 exhibit less than about 400 millidopters, less than about 300 millidopters, less than about 250 millidopters, or less than about 200 millidopters as measured using an optical distortion detector of transmission optics according to ASTM 1561. A suitable optical distortion detector is available from ISRA VISIION AG, Darmstadt, Germany, under the trade name SCREENSCAN-Faultfinder. In one or more embodiments, one or both of the first major surface 202 and the fourth major surface 334 exhibits: about 190 millidopters or less, about 180 millidopters or less, about 170 millidopters or less, about 160 millidopters or less, about 150 millidopters or less, about 140 millidopters or less, about 130 millidopters or less, about 120 millidopters or less, about 110 millidopters or less, about 100 millidopters or less, about 90 millidopters or less, about 80 millidopters or less, about 70 millidopters or less, about 60 millidopters or less, or about 50 millidopters or less. As used herein, optical distortion refers to the maximum optical distortion measured on the corresponding surface.
[0072] It is believed that the reduction in optical distortion of the glass ply 200 or ply 310, 320 is related to both the borosilicate glass composition disclosed herein and the fusion forming process made possible by the disclosed borosilicate glass composition. As far as the forming process is concerned, conventional float glass technology for forming borosilicate glass compositions involves floating molten glass on liquid tin, and when floating on the tin, the glass naturally has a thickness of 6 mm or more. In order to produce a lower thickness, the glass is stretched or drawn while floating, which produces a thickness variation on the surface of the glass called a draw line and produces internal stress. Both the draw line and the internal stress contribute to the optical distortion. By fusion forming the borosilicate glass composition according to the present disclosure, such draw lines and internal stresses are substantially avoided. In addition, the outer surface of the glass ply 200 or ply 310, 320 does not come into contact with any structure during the fusion forming process, which also reduces optical distortion. With respect to composition, the borosilicate glasses disclosed herein are preferably selected from the group consisting of: a glass having a liquidus viscosity of at least 500 kP and a T of 1725°C or less; 200P Fusion forming of the glass plies 200 or plies 310, 320 is achieved. In addition, it is also believed that the borosilicate glass composition according to the present disclosure reduces the refractive index variation on the surface of the glass plies 200 or plies 310, 320 compared to the conventionally used soda-lime silicate glass composition. It is known that the refractive index variation also causes optical distortion, and thus the reduction in the refractive index variation is expected to reduce the optical distortion.
[0073] In one or more embodiments, a first major surface or a second major surface of a first bent glass ply exhibits low film tensile stress. During the cooling process of the bent ply or stack, film tensile stresses may exist. As the glass cools, the major surfaces and edge surfaces (orthogonal to the major surfaces) develop surface compressions that are offset by the central region that exhibits tensile stresses. In some cases, such stresses may be problematic around the perimeter where edge cooling effects build up stresses and the bending tool creates thermal gradients that generate stresses. The low CTE associated with embodiments of the borosilicate glass compositions disclosed herein minimizes adverse residual stresses that may be induced during the annealing process of hot forming. Such stresses are proportional to the CTE, and therefore by reducing the CTE of the borosilicate glass composition, the residual stresses are also reduced.
[0074] Bending or forming introduces additional surface tension near the edge and causes the central tensile region to approach the glass surface. Therefore, the film tensile stress is the tensile stress measured near the edge (e.g., about 10-25 mm from the edge surface). In one or more embodiments, the film tensile stress at the first major surface or the second major surface of the first curved glass layer is less than about 7 megapascals (MPa), which is measured by an edge stress gauge according to ASTM C1279. Examples of such surface stress gauges are edge stress meters (Edge Stress Meter) or VRP (both available from Strainoptic Technologies). In one or more embodiments, the film tensile stress at the first major surface or the second major surface of the first curved glass layer is about 6 MPa or less, about 5 MPa or less, about 4 MPa or less, or about 3 MPa or less. In one or more embodiments, the lower limit of the film tensile stress is about 0.01 MPa or about 0.1 MPa. In other embodiments, the film tensile stress can be negligible (e.g., about 0). As stated herein, stress refers to either compression or tension, and the magnitudes of such stresses are provided as absolute values.
[0075] In one or more embodiments, the laminate 300, 400 can have a thickness of 10 mm or less, 9 mm or less, 8 mm or less, 7 mm or less, or 6 mm or less, wherein the thickness includes the sum of the thicknesses of the first glass ply 310, the second glass ply 320, and the interlayer 330. In various embodiments, the laminate 300, 400 can have a thickness ranging from about 1.8 mm to about 10 mm, or about 1.8 mm to about 9 mm, or about 1.8 mm to about 8 mm, or about 1.8 mm to about 7 mm, or about 1.8 mm to about 6 mm, or about 1.8 mm to about 5 mm, or 2.1 mm to about 10 mm, or about 2.1 mm to about 9 mm, or about 2.1 mm to about 8 mm, or about 2.1 mm to about 7 mm, or about 2.1 mm to about 6 mm, Or about 2.1mm to about 5mm, or about 2.4mm to about 10mm, or about 2.4mm to about 9mm, or about 2.4mm to about 8mm, or about 2.4mm to about 7mm, or about 2.4mm to about 6mm, or about 2.4mm to about 5mm, or about 3.4mm to about 10mm, or about 3.4mm to about 9mm, or about 3.4mm to about 8mm, or about 3.4mm to about 7mm, or about 3.4mm to about 6mm, or about 3.4mm to about 5mm. In other embodiments, the laminate thickness can be less than 1.8mm or greater than 10mm.
[0076] In one or more embodiments, the second curved glass ply (or the second glass ply used to form the second curved glass ply) is thinner than the first curved glass ply (or the first glass ply used to form the first curved glass ply). In other words, the first curved glass ply (or the first glass ply used to form the first curved glass ply) has a thickness greater than the second curved glass ply (or the second glass ply used to form the second curved glass ply). In one or more embodiments, the first thickness (or the thickness of the first glass ply used to form the first curved glass ply) is more than twice the second thickness. In one or more embodiments, the first thickness (or the thickness of the first glass ply used to form the first curved glass ply) is about 1.5 times to about 10 times the second thickness (e.g., about 1.75 times to about 10 times, about 2 times to about 10 times, about 2.25 times to about 10 times, about 2.5 times to about 10 times, about 2.75 times to about 10 times, about 3 times to about 10 times, about 3.25 times to about 10 times, about 3.5 times to about 10 times, about 3.75 times to about 10 times, about 1.5 times to about 10 times, about 1.6 times to about 10 times, about 1.8 times to about 10 times, about 1.9 times to about 10 times, about 2.3 times to about 10 times, about 2.4 times to about 10 times, about 2.6 times to about 10 times, about 2.75 times to about 10 times, about 3 times to about 10 times, about 3.25 times to about 10 times, about 3.5 times to about 10 times, about 3.75 times to about 10 times, about 1.6 times to about 10 times, about 2. 1 times, about 1.5 times to about 5 times, about 1.5 times to about 6 times, about 1.5 times to about 7 times, about 1.5 times to about 8 times, about 1.5 times to about 7.5 times, about 1.5 times to about 7 times, about 1.5 times to about 6.5 times, about 1.5 times to about 6 times, about 1.5 times to about 5.5 times, about 1.5 times to about 5 times, about 1.5 times to about 4.5 times, about 1.5 times to about 4 times, about 1.5 times to about 3.5 times, about 2 times to about 7 times, about 2.5 times to about 6 times, about 3 times to about 6 times). In other embodiments, the plies can be any other size, for example, the second ply can be thicker than the first or have the same thickness.
[0077] In one or more embodiments, the second thickness (or the thickness of the second glass ply used to form the second curved glass ply) is less than 2.0 mm (e.g., 1.95 mm or less, 1.9 mm or less, 1.85 mm or less, 1.8 mm or less, 1.75 mm or less, 1.7 mm or less, 1.65 mm or less, 1.6 mm or less, 1.55 mm or less, 1.5 mm or less, 1.45 mm or less, 1.4 mm or less, 1.35 mm or less, 1.3 mm or less, 1.25 mm or less, 1.2 mm or less, 1.1 The thickness may be 0.1 mm or less, 0.2 mm or less, 0.15 mm or less, or about 0.1 mm or less). The lower limit of the thickness may be 0.1 mm, 0.2 mm, or 0.3 mm. In some embodiments, the second thickness (or the thickness of the second glass ply used to form the second curved glass ply) is in the range of about 0.1 mm to less than about 2.0 mm, about 0.1 mm to about 1.9 mm, about 0.1 mm to about 1.8 mm, about 0.1 mm to about 1.7 mm, about 0.1 mm to about 1.6 mm, about 0.1 mm to about 1.5 mm, about 0.1 mm to about 1.4 mm, about 0.1 mm to about 1.3 mm, about 0.1 mm to about 1.2 mm, about 0.1 mm to about 1.1 mm, about 0.1 mm to about 1.2 mm. In some embodiments, the second layer can be thicker than 2.0 mm or thinner than 0.1 mm, for example, less than 700 μm, 500 μm, 300 μm, 200 μm, 100 μm, 80 μm, 40 μm, and / or at least 10 μm.
[0078] In some embodiments, the first thickness (or the thickness of the first glass ply used to form the first curved glass ply) is about 2.0 mm or greater. In such embodiments, the first thickness (or the thickness of the first glass ply used to form the first curved glass ply) and the second thickness (or the thickness of the second glass ply used to form the second curved glass ply) are different from each other. For example, the first thickness (or the thickness of the first glass ply used to form the first curved glass ply) is about 2.0 mm or greater, about 2.1 mm or greater, about 2.2 mm or greater, about 2.3 mm or greater, about 2.4 mm or greater, about 2.5 mm or greater, about 2.6 mm or greater, about 2.7 mm or greater, about 2.8 mm or greater, about 2.9 mm or greater, about 3.0 mm or greater, about 3.1 mm or greater, about 3.2 mm or greater. or larger, approximately 3.3 mm or larger, 3.4 mm or larger, 3.5 mm or larger, 3.6 mm or larger, 3.7 mm or larger, 3.8 mm or larger, 3.9 mm or larger, 4 mm or larger, 4.2 mm or larger, 4.4 mm or larger, 4.6 mm or larger, 4.8 mm or larger, 5 mm or larger, 5.2 mm or larger, 5.4 mm or larger, 5.6 mm or larger, 5.8 mm or larger, or 6 mm or larger. In some embodiments, the first thickness (or the thickness of the first glass ply used to form the first curved glass ply) is in the range of about 2.0 mm to about 6 mm, about 2.1 mm to about 6 mm, about 2.2 mm to about 6 mm, about 2.3 mm to about 6 mm, about 2.4 mm to about 6 mm, about 2.5 mm to about 6 mm, about 2.6 mm to about 6 mm, about 2.8 mm to about 6 mm, about 3 mm to about 6 mm, about 3.2 mm to about 6 mm, about 3.4 mm to about 6 mm, about 3.6 mm to about 6 mm, about 3.8 mm to about 6 mm, about 4 mm to about 6 mm, about 2.0 mm to about 6 mm. m to about 5.8mm, about 2.0mm to about 5.6mm, about 2.0mm to about 5.5mm, about 2.0mm to about 5.4mm, about 2.0mm to about 5.2mm, about 2.0mm to about 5mm, about 2.0mm to about 4.8mm, about 2.0mm to about 4.6mm, about 2.0mm to about 4.4mm, about 2.0mm to about 4.2mm, about 2.0mm to about 4mm, about 2.0mm to about 3.8mm, about 2.0mm to about 3.6mm, about 2.0mm to about 3.4mm, about 2.0mm to about 3.2mm, or about 2.0mm to about 3mm. In other embodiments, the first ply may be thicker than 10.0 mm or thinner than 2.0 mm, such as less than 1.5 mm, 1.0 mm, 700 μm, 500 μm, 300 μm, 200 μm, 100 μm, 80 μm, 40 μm, and / or at least 10 μm.
[0079] In one or more specific examples, the first thickness (or the thickness of the first glass ply used to form the first curved glass ply) is about 2.0 mm to about 3.5 mm, and the second thickness (or the thickness of the second glass ply used to form the second curved glass ply) ranges from about 0.1 mm to less than about 2.0 mm. In an embodiment, the ratio of the first thickness to the total glass thickness is at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9.
[0080] In one or more embodiments, the laminate 300, 400 is substantially free of visual deformation as measured by ASTM C1652 / C1652M. In specific embodiments, the laminate, the first curved glass ply, and / or the second curved glass ply are substantially free of wrinkles or deformation that can be detected by naked eye vision according to ASTM C1652 / C1652M.
[0081] In one or more embodiments, the first major surface 202 or the second major surface 204 comprises a surface compressive stress of less than 3 MPa as measured by a surface stress gauge (e.g., a surface stress gauge commercially available from Orihara Industrial Co., Ltd. (Japan) under the trade name FSM-6000, "FSM"). In some embodiments, the first curved glass ply is not strengthened, as described herein (but may optionally be annealed), and exhibits a surface compressive stress of less than about 3 MPa, or about 2.5 MPa or less, 2 MPa or less, 1.5 MPa or less, 1 MPa or less, or about 0.5 MPa or less. In some embodiments, such surface compressive stress ranges are present on both the first major surface and the second major surface.
[0082] In one or more embodiments, the first and second glass plies used to form the first curved glass ply and the second curved glass ply are substantially flat before being formed in pairs to form the first curved glass ply and the second curved glass ply. In some cases, one or both of the first glass ply and the second glass ply used to form the first curved glass ply and the second curved glass ply may have a 3D or 2.5D shape that does not exhibit the desired depth of curvature that will eventually be formed during the pair forming process and present in the resulting laminate. Additionally or alternatively, the thickness of one or both of the first curved glass ply (or the first glass ply used to form the first curved glass ply) and the second curved glass ply (or the second glass ply used to form the second curved glass ply) may be constant along one or more dimensions or may vary along one or more dimensions thereof for aesthetic and / or functional reasons. For example, the edges of one or both of the first curved glass ply (or the first glass ply used to form the first curved glass ply) and the second curved glass ply (or the second glass ply used to form the second curved glass ply) may be thicker than the more central areas of the glass plies.
[0083] The length (e.g., the longest centerline of a surface (e.g., the first major surface)), width (e.g., the longest dimension of the surface orthogonal to the length), and thickness (e.g., the dimension of the ply orthogonal to the length and width) dimensions of the first curved glass ply (or the first glass ply used to form the first curved glass ply) and the second curved glass ply (or the second glass ply used to form the second curved glass ply) may also vary depending on the product application or use. In one or more embodiments, the first curved glass ply (or the first glass ply used to form the first curved glass ply) includes a first length and a first width (the first thickness is orthogonal to both the first length and the first width), and the second curved glass ply (or the second glass ply used to form the second curved glass ply) includes a second length and a second width orthogonal to the second length (the second thickness is orthogonal to both the second length and the second width). In one or more embodiments, either or both of the first length and the first width are approximately 0.25 meters (m) or greater. For example, the first length and / or the second length can be in the range of about 1m to about 3m, about 1.2m to about 3m, about 1.4m to about 3m, about 1.5m to about 3m, about 1.6m to about 3m, about 1.8m to about 3m, about 2m to about 3m, about 1m to about 2.8m, about 1m to about 2.8m, about 1m to about 2.8m, about 1m to about 2.6m, about 1m to about 2.5m, about 1m to about 2.4m, about 1m to about 2.2m, about 1m to about 2m, about 1m to about 1.8m, about 1m to about 1.6m, about 1m to about 1.5m, about 1.2m to about 1.8m or about 1.4m to about 1.6m. In some embodiments, the surface dimension from perimeter to perimeter through the centroid of the corresponding surface (e.g., first surface, second surface, monomer major surface, layer surface) is: at least 1 mm, at least 1 cm, at least 10 cm, at least 1 m, and / or no more than 10 m, so that the contained ruptures will not cause failure of the corresponding layer. In other embodiments, the layer can be any other size.
[0084] For example, the first width and / or the second width can be in the range of about 0.5m to about 2m, about 0.6m to about 2m, about 0.8m to about 2m, about 1m to about 2m, about 1.2m to about 2m, about 1.4m to about 2m, about 1.5m to about 2m, about 0.5m to about 1.8m, about 0.5m to about 1.6m, about 0.5m to about 1.5m, about 0.5m to about 1.4m, about 0.5m to about 1.2m, about 0.5m to about 1m, about 0.5m to about 0.8m, about 0.75m to about 1.5m, about 0.75m to about 1.25m, or about 0.8m to about 1.2m. In other embodiments, the ply can be any other size.
[0085] In one or more embodiments, the second length is within 5% of the first length (e.g., about 5% or less, about 4% or less, about 3% or less, or about 2% or less). For example, if the first length is 1.5m, the second length can range from about 1.425m to about 1.575m and still be within 5% of the first length. In one or more embodiments, the second width is within 5% of the first width (e.g., about 5% or less, about 4% or less, about 3% or less, or about 2% or less). For example, if the first width is 1m, the second width can range from about 1.05m to about 0.95m and still be within 5% of the first width.
[0086] Having described the glass plies, their laminate structures, and their uses, the borosilicate glass composition will now be described in more detail. In an embodiment, the borosilicate glass composition comprises at least 74 mol % SiO2, at least 10 mol % B2O3, and at least some Al2O3. In a specific embodiment, the borosilicate glass composition comprises at least 0.03 mol % iron oxide (e.g., Fe2O3 or FeO). In a more specific embodiment, SiO2, Al2O3, and B2O3 account for at least 90 mol % of the borosilicate glass composition. In addition, the borosilicate glass composition has a liquidus viscosity of at least 500 kilopoise (kP), and a temperature (T ) of 1725°C or less at a viscosity of 200 poise (P). 200P ).
[0087] In an embodiment, the borosilicate glass composition comprises SiO2 in an amount ranging from at least about 72 mol%, more specifically about 72 mol% to about 80 mol%, and specifically 74 mol% to 80 mol%. For example, the borosilicate glass composition comprises SiO2 in an amount ranging from about 72 mol% to about 85 mol%, about 73 mol% to about 85 mol%, about 74 mol% to about 85 mol%, about 75 mol% to about 85 mol%, about 76 mol% to about 85 mol%, about 77 mol% to about 85 mol%, about 78 mol% to about 85 mol%, about 79 mol% to about 85 mol%, about 80 mol% to about 85 mol%, about 81 mol% to about 85 mol%, about 82 mol% to about 85 mol%, about % to about 83 mol %, about 84 mol % to about 85 mol %, about 74 mol % to about 84 mol %, about 74 mol % to about 84 mol %, about 74 mol % to about 83 mol %, about 74 mol % to about 82 mol %, about 74 mol % to about 81 mol %, about 74 mol % to about 80 mol %, about 74 mol % to about 79 mol %, about 74 mol % to about 78 mol %, about 74 mol % to about 77 mol %, about 74 mol % to about 76 mol %, and all ranges and subranges therebetween. In other embodiments, the glass can have less than 74 mol % SiO2.
[0088] In an embodiment, the borosilicate glass composition comprises B2O3 in an amount ranging from about 10 mol% to about 16 mol%, specifically about 11.5 mol% to about 14.5 mol%. In various embodiments, the borosilicate glass composition comprises B2O3 in an amount ranging from about 10 mol% to about 16 mol%, about 11 mol% to about 16 mol%, about 12 mol% to about 16 mol%, about 13 mol% to about 16 mol%, about 14 mol% to about 16 mol%, about 15 mol% to about 16 mol%, about 11 mol% to about 15 mol%, about 11 mol% to about 14 mol%, about 11 mol% to about 13 mol%, about 11 mol% to about 12 mol%, about 12 mol% to about 13 mol%, about 12 mol% to about 14 mol%, about 14 mol% to about 15 mol%, or any range or sub-range therebetween. In other embodiments, the glass may have less than 10 mol% B2O3 or more than 16 mol% B2O3.
[0089] In an embodiment, the borosilicate glass composition includes Al2O3 in an amount ranging from about 2 mol% to about 6 mol%, specifically about 2.5 mol% to about 5 mol%. In various embodiments, the borosilicate glass composition includes Al2O3 in an amount ranging from about 2 mol% to about 6 mol%, about 3 mol% to about 6 mol%, about 4 mol% to about 6 mol%, about 5 mol% to about 6 mol%, about 3 mol% to about 5 mol%, about 3 mol% to about 4 mol%, about 4 mol% to about 5 mol%, or any range or sub-range therebetween. Advantageously, the Al2O3 present in these amounts helps prevent phase separation of the borosilicate glass composition. In other embodiments, the glass may have less than 2 mol% Al2O3 or more than 6 mol% Al2O3.
[0090] In an embodiment, the borosilicate glass composition includes Na2O in an amount ranging from about 3 mol% to about 8 mol%, specifically about 4.5 mol% to about 8 mol%. In various embodiments, the borosilicate glass composition includes Na2O in an amount ranging from about 3 mol% to about 8 mol%, about 4 mol% to about 8 mol%, about 5 mol% to about 8 mol%, about 6 mol% to about 8 mol%, about 7 mol% to about 8 mol%, about 3 mol% to about 7 mol%, about 4 mol% to about 7 mol%, about 5 mol% to about 7 mol%, about 6 mol% to about 7 mol%, about 4 mol% to about 6 mol%, about 5 mol% to about 6 mol%, or any range and sub-range therebetween. In other embodiments, the glass may have less than 3 mol% Na2O or more than 8 mol% Na2O.
[0091] In an embodiment, the borosilicate glass composition includes K2O in an amount ranging from about 0.5 mol% to about 5 mol%, specifically about 0.5 mol% to about 3 mol%. In various embodiments, the borosilicate glass composition includes K2O in an amount ranging from about 0.5 mol% to about 5 mol%, about 0.6 mol% to about 5 mol%, about 0.7 mol% to about 5 mol%, about 0.8 mol% to about 5 mol%, about 0.9 mol% to about 5 mol%, about 1 mol% to about 5 mol%, about 2 mol% to about 5 mol%, about 3 mol% to about 5 mol%, about 4 mol% to about 5 mol%, about 2 mol% to about 4 mol%, 3 mol% to 4 mol%, or any range and sub-range therebetween. In other embodiments, the glass may have less than 0.8 mol% K2O or more than 5 mol% K2O.
[0092] The presence of Na2O and KO has an effect on the liquidus viscosity. Thus, in an embodiment, at least one of Na2O or KO is present in an amount of at least 4 mol%. In an embodiment, when other alkaline earth oxides (e.g., CaO or MgO) are present in an amount of at least 1.5 mol%, the total amount of Na2O and KO is present in an amount of at least 5.5 mol%. In other embodiments, regardless of the alkaline earth oxide, the total amount of Na2O and KO is present in an amount of at least 8 mol%. In some cases, it is believed that KO and Na2O tend to lower the liquidus temperature, thereby increasing the liquidus viscosity. In addition, when combined with B2O3 and Al2O3, KO and Na2O tend to increase the liquidus viscosity.
[0093] In an embodiment, the ratio of K2O to Na2O is about 0.1 to about 0.75. In an embodiment, the ratio of K2O to Na2O is about 0.15 to about 0.75, about 0.20 to about 0.75, about 0.25 to about 0.75, about 0.30 to about 0.75, about 0.35 to about 0.75, about 0.40 to about 0.75, about 0.45 to about 0.75, about 0.50 to about 0.75, about 0.55 to about 0.75, about 0.60 to about 0.75, about 0.65 to about 0. 75, about 0.70 to about 0.75, about 0.1 to about 0.70, about 0.1 to about 0.65, about 0.1 to about 0.60, about 0.1 to about 0.55, about 0.1 to about 0.50, about 0.1 to about 0.45, about 0.1 to about 0.40, about 0.1 to about 0.35, about 0.1 to about 0.30, about 0.1 to about 0.25, about 0.1 to about 0.20, or about 0.1 to about 0.15.
[0094] In an embodiment, the borosilicate glass composition includes P2O5 in an amount ranging from 0 mol% to about 4 mol%, from about 1 mol% to about 4 mol%, from about 2 mol% to about 4 mol%, from about 3 mol% to about 4 mol%, from about 1 mol% to about 3 mol%, from about 2 mol% to about 3 mol%, from about 1 mol% to about 2 mol%, or any range and sub-range therebetween. P2O5 tends to reduce the density of the borosilicate glass composition, which may result in increased densification during deformation as discussed below. In addition, it is expected that P2O5 may increase the liquidus viscosity.
[0095] In an embodiment, the borosilicate glass composition includes CaO in an amount ranging from 0 mol% to about 5 mol%, 0 mol% to about 4 mol%, 0 mol% to about 3 mol%, 0 mol% to about 2 mol%, 0 mol% to about 1 mol%, about 1 mol% to about 5 mol%, about 2 mol% to about 5 mol%, about 3 mol% to about 5 mol%, about 4 mol% to about 5 mol%, about 2 mol% to about 4 mol%, about 2 mol% to about 3 mol%, about 3 mol% to about 4 mol%, and all ranges and sub-ranges therebetween.
[0096] In an embodiment, the borosilicate glass composition includes MgO in an amount ranging from 0 mol% to about 5 mol%, specifically about 0.5 mol% to about 2.5 mol%. In various embodiments, the borosilicate glass composition includes MgO in an amount ranging from 0 mol% to about 5 mol%, 0 mol% to about 4 mol%, 0 mol% to about 3 mol%, 0 mol% to about 2 mol%, 0 mol% to about 1 mol%, about 1 mol% to about 5 mol%, about 2 mol% to about 5 mol%, about 3 mol% to about 5 mol%, about 4 mol% to about 5 mol%, about 2 mol% to about 4 mol%, about 2 mol% to about 3 mol%, about 3 mol% to about 4 mol%, and all ranges and sub-ranges therebetween.
[0097] In an embodiment, the total amount of CaO and MgO is up to 5 mol%. In an embodiment, for a total amount of K2O and Na2O less than 7 mol%, the total amount of CaO and MgO is at least 1.5 mol%. Alkaline earth oxides such as CaO and MgO tend to lower the liquidus temperature and increase the liquidus viscosity.
[0098] In an embodiment, the borosilicate glass composition includes SnO2 in an amount up to about 0.25 mol%. In an embodiment, the borosilicate glass composition includes SnO2 in an amount ranging from 0 mol% to about 0.25 mol%, from about 0.05 mol% to about 0.25 mol%, from about 0.10 mol% to about 0.25 mol%, from about 0.15 mol% to about 0.25 mol%, from about 0.20 mol% to about 0.25 mol%, from about 0.05 mol% to about 0.20 mol%, from about 0.05 mol% to about 0.15 mol%, from about 0.05 mol% to about 0.10 mol%, from about 0.10 mol% to about 0.15 mol%, from about 0.10 mol% to about 0.20 mol%, from about 0.15 mol% to about 0.20 mol%, or all ranges and sub-ranges therebetween. In some embodiments, SnO2 may be replaced by another fining agent, such as a multivalent or other oxygen absorber including antimony, arsenic, iron, and cerium.
[0099] In an embodiment, the borosilicate glass composition includes one or more iron compounds, such as iron (III) oxide (Fe2O3) or iron (II) oxide (FeO; provided from a source such as iron oxalate (C2FeO4)), particularly to absorb infrared radiation from sunlight. In an embodiment, the borosilicate glass composition includes the iron compound in an amount up to about 0.50 mol%, particularly in the range of about 0.20 to about 0.40 mol%. In an embodiment, the borosilicate glass composition includes an iron compound in an amount ranging from about 0.03 mol % to about 0.50 mol %, about 0.10 mol % to about 0.50 mol %, about 0.15 mol % to about 0.50 mol %, about 0.20 mol % to about 0.50 mol %, about 0.25 mol % to about 0.50 mol %, about 0.30 mol % to about 0.50 mol %, about 0.35 mol % to about 0.50 mol %, about 0.40 mol % to about 0.50 mol %, about 0.45 mol % to about 0.50 mol %, or any range or sub-range therebetween. In other embodiments, in addition to or in place of the iron compound, other modifiers (e.g., TiO2) may be used to reduce the transmission of UV radiation. In an embodiment, the amount of TiO2 provided may be about 0.04 mol % to about 0.12 mol %.
[0100] In an embodiment, the glass composition (or glass article formed therefrom) exhibits a liquidus viscosity of at least 500 kilopoise (kP) and up to 50,000 kP. Advantageously, glass compositions having a liquidus viscosity greater than 1000 kP are less susceptible to baggy warp during fusion drawing. As used herein, the term "liquidus viscosity" refers to the viscosity of a molten glass at the liquidus temperature, wherein the term "liquidus temperature" refers to the temperature at which crystals first appear as the molten glass cools from the melting temperature, or the temperature at which the last bit of crystals melts as the temperature increases from room temperature.
[0101] The borosilicate glass compositions described herein having a liquidus viscosity of at least 500 kP are fusion-formable at a thickness of at least 2 mm, at least 3 mm, at least 3.3 mm, or at least 3.8 mm. In some embodiments, the fusion-formed glass plies are substantially free of draw lines present in typical float-formed glass products. The liquidus viscosity is determined by the following method. First, the liquidus temperature of the glass is measured according to ASTM C829-81 (2015), entitled "Standard Practice for Measurement of Liquidus Temperature of Glass by the Gradient Furnace Method". Next, the viscosity of the glass at the liquidus temperature is measured according to ASTM C965-96 (2012), entitled "Standard Practice for Measuring Viscosity of Glass Above the Softening Point".
[0102] In an embodiment, the borosilicate glass composition exhibits a strain point temperature in the range of about 480°C to about 560°C, about 490°C to about 560°C, about 500°C to about 560°C, about 510°C to about 560°C, about 520°C to about 560°C, about 530°C to about 560°C, about 540°C to about 560°C, about 550°C to about 560°C, about 480°C to about 550°C, about 480°C to about 540°C, about 480°C to about 530°C, about 480°C to about 520°C, about 480°C to about 510°C, about 480°C to about 500°C, or any range or sub-range therebetween. In an embodiment, the strain point temperature is determined using the beam bending viscosity method of ASTM C598-93 (2013). In an embodiment, the strain point is defined as a viscosity of 10 14.68 The temperature of the park.
[0103] In an embodiment, the borosilicate glass composition exhibits an annealing point temperature in the range of about 520°C to about 590°C, about 530°C to about 590°C, about 540°C to about 590°C, about 550°C to about 590°C, about 560°C to about 590°C, about 570°C to about 590°C, about 580°C to about 590°C, about 520°C to about 580°C, about 520°C to about 570°C, about 520°C to about 560°C, about 520°C to about 550°C, about 520°C to about 540°C, about 520°C to about 530°C, or any range or sub-range therebetween. The annealing point is determined using the beam bending viscosity method of ASTM C598-93 (2013). In an embodiment, the annealing point is defined as a viscosity of 10 13.18 The temperature of the park.
[0104] In an embodiment, the glass composition exhibits a maximum temperature (T) of 1725° C. at a viscosity of about 200 P. 200P ), which is determined by Fulcher fitting the high temperature viscosity (HTV) data (i.e., all temperature measurements from 100 kP to 100 poise). For example, a glass composition may exhibit a range of T 200P : about 1500°C to about 1725°C, about 1525°C to about 1725°C, about 1550°C to about 1725°C, about 1575°C to about 1725°C, about 1600°C to about 1725°C, about 1625°C to about 1725°C, about 1650°C to about 1725°C, about 1675°C to about 1725°C, about 1700°C to about 1725°C, about 1500°C to about 1700°C, about 1500°C to about 1675°C, about 1500°C to about 1650°C, about 1500°C to about 1625°C, about 1500°C to about 1600°C, about 1500°C to about 1575°C, about 1500°C to about 1550°C, about 1500°C to about 1525°C, or any range or sub-range therebetween.
[0105] In one or more embodiments, the glass composition or glass article formed therefrom exhibits a density at 20°C of less than 2.4 g / cm 3 In an embodiment, the density at 20°C is: 2.39 g / cm 3 or lower, 2.38g / cm 3 or lower, 2.37g / cm 3 or lower, 2.36g / cm 3 or lower, 2.35g / cm 3 or lower, 2.34g / cm 3 or lower, 2.33g / cm 3 or lower, 2.32g / cm 3 or lower, 2.31g / cm3 or lower, 2.30g / cm 3 Or lower, 2.29g / cm 3 Or lower, 2.28g / cm 3 or lower, 2.27g / cm 3 or lower, 2.26g / cm 3 or lower, 2.25g / cm 3 or lower, 2.24g / cm 3 or lower, 2.23g / cm 3 or lower, 2.22g / cm 3 or lower, 2.21g / cm 3 or lower, or 2.20g / cm 3 or lower. In an embodiment, the density is determined using the buoyancy method of ASTM C693-93 (2013). Advantageously, the density is less than 2.4 g / cm 3 The density of the glass is less than that of the soda-lime-silicate glass conventionally used in automotive glazing laminates.
[0106] As mentioned, the borosilicate glass compositions according to the present disclosure are capable of fusion forming. The resulting glass plies can be described as fusion formed. Figure 7 An exemplary embodiment of an apparatus 700 for fusion-forming a glass ply from a borosilicate glass composition is shown. The fusion-forming apparatus 700 includes an isopipe 702 defined by a groove 704, a first forming surface 706, and a second forming surface 708. The first forming surface 706 and the second forming surface 708 are angled inwardly below the groove 704 and meet at a root 710 of the isopipe 702. A borosilicate glass composition 712 disclosed herein is provided to the groove 704 in a molten state, and the borosilicate glass composition 712 overflows the groove 704, forming two streams and downward along the forming surfaces 706, 708. The streams of molten glass meet at the root 710 to form a glass ply 714, which is cooled and cut from the flowing streams.
[0107] In an embodiment, the fusion forming apparatus 700 includes a second isopipe 716 having a second groove 718, a third forming surface 720, and a fourth forming surface 722. A glass composition 724 (having the same or different composition as the borosilicate glass composition 712) is provided in a molten state to the second groove 718 and overflows the second groove 718. The molten glass composition 724 flows downward along the third and fourth forming surfaces 720, 722, where it is directed outwardly around the borosilicate glass composition 712. In this manner, the glass composition 724 flows downwardly along the first and second forming surfaces 706, 708 outside the stream of the borosilicate glass composition 712. At the root 710 of the isopipe 702, the combination of the stream of the borosilicate glass composition 712 and the stream of the glass composition 724 produces a glass ply 714 having cladding layers 726a, 726b. Such coatings may mechanically strengthen the glass based on residual stresses established based on the different thermal expansion coefficients between the compositions 712, 724, or the coatings may be chemically strengthenable (e.g., by ion exchange treatment). The coatings 726a, 726b may also provide other features, such as providing specific optical properties to the glass ply 714 formed in this manner.
[0108] The fusion forming process provides the advantage that, because the two glass streams overflowing from the channel fuse together, no external surface of the resulting glass article comes into contact with any part of the apparatus. Thus, the surface properties of the fusion drawn glass article are not affected by such contact. In an embodiment, the fusion formed borosilicate glass composition of the present disclosure exhibits an optical distortion of no greater than 75 millidopters as measured by an optical distortion detector using transmission optics in accordance with ASTM 1561. The liquidus viscosity is less than 500 kP and T 200P Conventional borosilicate glass compositions having temperatures greater than 1725°C cannot be fusion formed using a fusion draw process at a thickness of 2 mm or greater, and instead such conventional borosilicate glass compositions of such thickness are typically formed using a float process.
[0109] Example
[0110] The following table provides various embodiments of fusion-formable borosilicate glass compositions.
[0111] Table 1: Composition and properties of Examples 1-6
[0112]
[0113]
[0114] Examples 1-6 are exemplary glass compositions according to one or more embodiments of the present disclosure. As can be seen from Table 1, the liquidus viscosities of these glass compositions are much higher than the 500 kP required for the glass compositions to be fused and formed. In addition, the T 200P Far below 1725°C. In addition, advantageously, the density of these glasses is less than 2.4 g / cm 3 Conventional laminates use thick outer glass plies of soda-lime silicate glass with a density greater than 2.4 g / cm 3 Thus, not only are the mechanical properties enhanced as described below, but the disclosed fusion-formable borosilicate glass compositions also have a relative low molecular weight of less than 2.4 g / cm 3 (Specifically 2.35g / cm 3 Densities of 500 ppm / °C or less (or less) provide weight savings (and therefore enhance fuel efficiency). The thermal properties of the resulting glass plies are also enhanced via a low temperature coefficient of thermal expansion (LTCTE) obtained by measuring the expansion of the glass at temperatures between 0°C and 300°C. In an embodiment, the LTCTE is 5.6 ppm / °C or less, specifically 5.3 ppm / °C or less, and especially 5.1 ppm / °C or less. In addition to the properties just discussed, Table 1 also contains information related to strain point temperature, annealing point temperature, high temperature CTE (HTCTE), Young's modulus, and Poisson's ratio.
[0115] Table 2 below provides additional exemplary compositions according to the present disclosure.
[0116] Table 2: Composition and properties of Examples 7-9 and Comparative Examples 10 and 11
[0117]
[0118]
[0119] Likewise, it can be seen from Table 2 that Examples 7-9 of the disclosed fusion-formable borosilicate glass compositions exhibit properties desirable for fusion-forming at thicknesses greater than 2 mm. In addition, the properties of the borosilicate glass compositions are advantageous compared to the same properties of soda-lime silicate glass (e.g., density and LTCTE). However, it can be seen from Comparative Examples 10 and 11 that compositions falling outside of those ranges disclosed herein do not have the properties desirable for fusion-forming at greater thicknesses with respect to fusion-formability. Comparative Example 10 has a low B2O3 content of 8.47 mol% resulting in a total of SiO2, B2O3, and Al2O3 of less than 90 mol%, while Comparative Example 11 contains no K2O or MgO and has little to no CaO, which tends to increase liquidus viscosity, as discussed above. However, as discussed later, some embodiments may be useful as windshields or other articles, for example due to fracture behavior performance, regardless of whether the corresponding composition is fusion-formable.
[0120] Table 3 below provides other exemplary compositions of borosilicate glass compositions according to the present disclosure.
[0121] Table 3: Composition of Examples 12-14 and 18 and Comparative Examples 15-17
[0122]
[0123]
[0124] The borosilicate glass composition examples 12-14 and 18 in Table 3 have liquidus viscosities and T values required for fusion forming. 200P Temperature and also the properties that are advantageous for using the disclosed borosilicate glass composition as an outer layer in an automotive glazing laminate. In addition, it can be seen that these examples demonstrate that increasing the amount of B2O3 has an effect on reducing density. Examples 12-17 each have a density of less than 2.3 g / cm 3 The density of some embodiments is 2.250 g / cm 3 or lower density. Comparative Examples 15-17 exhibit T values higher than 1725°C. 200PTemperature. Comparative Examples 15-17 have, for example, too little basic oxide and too little basic and alkaline earth oxide (also referred to as alkaline earth oxide) for some of the fusion-forming properties disclosed herein compared to Examples 12-14 and 18, but may be sufficient basic and alkaline earth oxide for other embodiments, such as windshields and other articles with annular cracks (including transverse and radial cracks from a Vickers indenter), as described below. Specifically, Examples 12-14 and 15 each contain at least 5.5 mol% Na2O+KO and at least 7.0 mol% Na2O+KO+MgO+CaO in total. From the examples in Tables 1-3, it is believed that embodiments of the present disclosure will exhibit the desired T for fusion forming. 200P and liquidus viscosity, wherein the total amount of Na2O+K2O+MgO+CaO is at least 7.0 mol%, particularly wherein there are at least 5.5 mol% Na2O+K2O and at least 1.5 mol% MgO+CaO. It is also believed that embodiments of the present disclosure will exhibit the T required for fusion forming. 200P and a liquidus viscosity wherein, regardless of the amounts of MgO and CaO, Na2O+K2O is at least 8 mol%.
[0125] Table 4 provides additional exemplary compositions of disclosed borosilicate glass compositions having further added iron compounds (e.g., as iron (II) oxide or iron (III) oxide) to absorb sunlight (particularly infrared (IR) radiation) that causes elevated temperatures inside vehicles. Thus, by providing IR absorption, automotive glazing comprising a laminate having an outer ply of the disclosed borosilicate glass composition can provide additional fuel efficiency and comfort by reducing heat buildup in the vehicle and the burden on the air cooling system. Table 4 provides example borosilicate glass compositions of Table 4, with the amount of iron (Fe2O3) increased from 0 mol% to 0.44 mol%, and one composition (Example 25) containing primarily iron (II) oxide (FeO) as the primary iron compound. In Example 25, iron (II) oxide is provided by using iron oxalate (C2FeO4) as a batch source. The carbon of the iron oxalate leaves as carbon dioxide (CO2), leaving primarily iron (II) oxide and some iron (III) oxide in the glass.
[0126] Table 4: Composition and optical properties of Examples 19-25
[0127]
[0128] Tables 5 and 6 below provide transmission data for the borosilicate glass compositions of Table 4 for glass plies having thicknesses of 3.3 mm and 2.1 mm, respectively. In embodiments, for borosilicate glass compositions of given composition, the addition of an iron compound serves to reduce visible light (i.e., from about 400 nm to about 750 nm), total solar transmission, and UV transmission. All transmission values are measured at normal incidence. Example 3 has a visible light transmission (T VIS ) and 92.0% total solar transmittance (TTS), measured according to ISO 13837A (A / 2°). By gradually adding Fe2O3, T VIS As shown in Table 4, the addition of 0.07 mol% (or 0.19 wt%) Fe2O3 makes TTS VIS The addition of 0.37 mol% (or 0.92 wt%) Fe2O3 caused T VIS According to ISO 13837, for glazing of road vehicles, T VIS The minimum requirement is 73%. Figure 8 Transmittance graphs for Examples 3, 19-24 are provided. It can be seen that the addition of Fe2O3 results in a decrease in the overall transmittance measured, and a significant decrease in the transmittance measured between about 750 nm and 1500 nm corresponding to the near infrared spectrum. In embodiments, automotive glazing comprising a laminate 300, 400 comprising at least one glass ply of the fusion-formable borosilicate glass composition disclosed herein has a TTS of 61% or less and / or a TTS of at least 73%. VIS , measured according to ISO 13837A (A / 2°). In such embodiments, the inventors, based on previous experience in making such glazings and laminates, believe that the interlayer and other glass plies will have a significant effect on T VIS There is minimal impact (eg, up to about 0.5% reduction) and further reductions in TTS, such as 3-5%. This is particularly true when the fusion-formable borosilicate glass plies disclosed herein are used as thicker outer plies of a laminate glazing.
[0129] Table 5: Transmission properties based on iron content for 3.3 mm glass
[0130]
[0131] It can also be seen from Table 5 that in addition to making T VISIn addition to the decrease in TTS, increasing the iron content increases the UV cutoff wavelength (i.e., the wavelength at which the UV transmission becomes less than 10%) and decreases the total UV transmission in the range of 300-380 nm. In Example 3, the glass composition does not contain iron content. The UV cutoff wavelength is less than 300 nm, and the UV transmission is 85.7%. As the iron content increases from 0 wt % (or 0 mol %) to 0.92 wt % (or 0.37 mol %), the UV cutoff wavelength increases to 365 nm and the TTS decreases. UV Reduced to 6.1%. In addition to the T VIS and TTS requirements, the laminated bodies 300, 400 embodiments comprising at least one glass ply of the fusion-formable borosilicate glass composition disclosed herein have a TTS of less than 75%. UV Advantageously, reducing UV transmission in the laminate can help reduce yellowing of the polymer interlayer. Fig.10 Based on the data contained in Table 5, T values for Examples 3, 19-23, and 25 are shown for a single glass ply. VIS 、T UV and TTS as a function of iron content.
[0132] Table 6 provides transmission data for glass plies of the same composition as contained in Table 5 (with the exception of Example 24, which is not included). However, the thickness of the glass plies was reduced from 3.3 mm to 2.1 mm. As can be seen from Table 6, the reduction in ply thickness resulted in a slight decrease in the UV cutoff wavelength, and a decrease in T UV 、T VIS and TTS increased compared to the thicker 3.3 mm plies of Table 5. However, Table 6 still confirms that T UV 、T VIS And TTS is still decreasing step by step. Fig.11 Based on the data contained in Table 6, the T VIS 、T UV and TTS as a function of iron content. It can also be seen from Tables 5 and 6 that the iron (II) oxide from iron oxalate provided to the batch provides similar or better levels of UV and solar radiation absorption than iron (III) oxide when considered on a weight percent basis.
[0133] Table 6: Transmission properties based on iron content for 2.1 mm glass
[0134]
[0135] Fig.12 and 13 The TTS and T values are plotted for the glass compositions contained in Tables 5 and 6. VIS From Fig.12 and 13 It can be seen that as the plot points move from the upper right to the lower left, the iron content increases, defining a quadratic relationship. Fig.12 In, T VIS The relationship between TTS is given by the following equation: TTS = 0.0097 (T VIS ) 2 –0.6609(T VIS )+68.688. Fig.13 In, T VIS The relationship between TTS is given by the following equation: TTS = 0.014 (T VIS ) 2 –1.4278(T VIS )+103.47. It is believed that the use of iron oxalate as the raw material of the iron compound of borosilicate glass can shift the curve to the right, which makes T VIS Increased occurrence.
[0136] In embodiments, the stacks 300, 400 described herein may be used in a system 800 that also includes a sensor 810, such as Fig. 9 Specifically, the previous discussion demonstrates that the stacks 300, 400 are transparent to electromagnetic radiation in the visible spectrum and as shown in FIG. Figure 8 As shown, the stack is also substantially transparent to electromagnetic radiation having wavelengths greater than 1500 nm (eg, short wave infrared). Signals transmitted using electromagnetic radiation within these ranges can penetrate the stack 300, 400. Fig. 9 The sensor 810 is shown receiving an input signal 820 and transmitting an output signal 830 across the stack 300, 400. For example, in one or more embodiments, the stack 300, 400 is included as a glass window 130 in the vehicle 100, such as Figure 1As shown. In such embodiments, the sensor 810 is arranged on the interior of the vehicle 100. In this way, the vehicle 100 is able to transmit and receive signals 820, 830. In one or more embodiments, the signals 820, 830 have peak wavelengths in the visible light (about 400nm to about 750nm) or short-wave infrared spectrum (1500nm or greater). In an embodiment, such signals contribute to the possibility of automatic or semi-automatic driving of the vehicle, open road charging, telecommunications, traffic monitoring and control, and communication between vehicles and vehicles. An example of a sensor 810 that can be used in the system 800 is a LIDAR that uses one or both of visible light or short-wave infrared radiation. In an embodiment of the stack 300, 400 comprising an IRR coating, in the area where the sensor 810 is configured to receive and send signals through the stack 300, 400, the IRR coating can be ablated on the ply from which it is applied.
[0137] As described above, the borosilicate glass compositions disclosed herein have surprisingly improved deformation properties compared to conventional soda-lime-silicate glass compositions and even compared to conventional borosilicate glass compositions. Specifically, the inventors have discovered that glass plies formed from the borosilicate glass compositions disclosed herein surprisingly and unexpectedly densify after deformation, which can limit the propagation of radial cracks generated by, for example, rocks and other flying debris from the road.
[0138] Figures 5A-5C It is shown that for the borosilicate glass composition disclosed herein ( Figure 5A ), conventional soda-lime-silicate glass composition ( Figure 5B ) and conventional borosilicate glass compositions ( Figure 5C ) were subjected to crack formation produced by quasi-static indentation using a Vickers indentation tip at 2 kilogram force (kgf). It is believed that quasi-static indentation testing using a Vickers tip provides a good representation of windshield performance when the exterior surface of the windshield is impacted by flying debris (e.g., rocks).
[0139] In the test, a borosilicate glass composition that is more conventional with respect to formability includes: 83.60 mol% SiO2, 1.20 mol% Al2O3, 11.60 mol% B2O3, 3.00 mol% Na2O, and 0.70 mol% K2O. This conventional borosilicate glass composition has: 2.23 g / cm 3density, a strain point of 518°C, an annealing point of 560°C, an LTCTE of 3.25 pm / °C, a Young's modulus of 64 GPa, and a Poisson's ratio of 0.2. Thus, compared to the embodiments of the borosilicate glass compositions disclosed herein, conventional borosilicate glass compositions contain less Al2O3, less total alkali content (particularly K2O), and less total alkaline earth content. Such conventional borosilicate glass compositions can be used in scenarios where a low coefficient of thermal expansion (e.g., 3.3 ppm / °C or less) is desired. Oxides of alkali and alkaline earth substances tend to increase the coefficient of thermal expansion. Here, a slight increase in the coefficient of thermal expansion to about 5-6 ppm / °C results in the borosilicate glass compositions disclosed herein resulting in an increase in liquidus viscosity and T 200P The balance of the reduction in temperature and the fusion forming ability. In addition, as discussed below, the disclosed borosilicate glass compositions have surprising and unexpected effects on the fracture properties of glass plies made from the borosilicate glass compositions.
[0140] from Figures 5A-5C It can be seen that each glass composition exhibits radial cracks 510 extending outward from the point at which the Vickers indentation tip is pressed into the respective ply. Figure 5A As shown, the glass plies of the borosilicate glass composition disclosed herein exhibit the formation of annular cracks 520 that bound radial cracks 510 and prevent them from further growth. Specifically, the radial cracks 510 do not continue to extend radially because the radial cracks 510 are likely (e.g., more likely, statistically more likely, at least 51% likely, such as at least 60% likely, at least 80% likely in 100 sample sizes) to be stopped and not traverse the annular cracks 520 (e.g., interrupted by them). Advantageously, by limiting the propagation of the radial cracks 510, the impact on the overall strength of the glass ply (which would reduce strength) is reduced.
[0141] Figure 5B and 5C The graph in Figure 5B and 5C The topography of the crack line segment shown in the microscope image. Figure 5B It can be seen that the radial crack 510 has a valley 530 at the center of the pattern where the depth below the surface is deepest. Figure 5B For soda-lime-silicate glass, the structure of the glass provides a relatively reduced free volume, and the broken glass network shears under sharp contact, which causes surface pile-up to peak 540. Therefore, if Figure 5B As shown in the microscope image of FIG. 5 , the surface around the radial crack 510 is convex.
[0142] for Figure 5C The conventional borosilicate glass composition of sodium-lime-silicate glass has a relatively higher free volume and a highly connected network in the glass structure, which preferentially densifies under sharp contact. The radial crack 510 still contains a central valley 530 at the center of the pattern, but there are no obvious peaks at the edges of the radial crack 510 because the densification of the structure (as shown by arrows 550) saves volume, resulting in the following Figure 5C High ring stress in the annular crack cluster as shown in the microscope image.
[0143] Back to Figure 5A , it can be seen Figure 5C A comparison between conventional borosilicate glass compositions and the borosilicate glass compositions disclosed herein. Figure 5A In the graph of FIG. 5 , the ring cracking stress is shown as a function of the distance from the contact circle of the indenter. For conventional borosilicate glass compositions (shown as curve 560), the ring stress decreases with increasing distance from the contact circle, which causes the maximum ring cracking stress to be located at the perimeter of the contact circle. However, for the borosilicate glass compositions disclosed herein, Figure 5A and 5C Stress field analysis of the cracks of the embodiment of the present invention confirms that the maximum ring cracking stress (indicated by asterisk 570) is surprisingly and unexpectedly spaced apart from the perimeter of the contact circle. For the borosilicate glass compositions disclosed herein, the strength-limiting intermediate and radial cracks 510 are contained within the annular crack 520 by forming the ring at a distance spaced apart from the crack boundary.
[0144] Although the Vickers indentation test contemplates quasi-static loading (i.e., where the load is applied slowly so that the inertial effects of the load are negligible), the fusion-formed borosilicate glass compositions were also found to perform as well as conventional float-formed borosilicate glasses and better than soda-lime-silicate glasses when exposed to dynamic loading using the Vickers dart drop test. In the Vickers dart drop test, a dart with a Vickers indentation tip (136°) and a weight of 8.6 g is dropped at increasing heights (50 mm increments) until a visually visible crack (i.e., a crack of at least 10 mm in length) forms in the glass ply. Soda-lime-silicate glass has an average height of less than 600 mm for visually visible crack formation. The borosilicate glass disclosed herein has an average height of more than 600 mm (specifically, more than 650 mm) before visually visible crack formation, which is approximately equal to what would be expected for conventional borosilicate glass compositions. It is believed that the dart drop test provides the contact rate and force required to allow radial crack formation to exceed the densified glass's ability to form annular cracks in the borosilicate glass compositions disclosed herein.
[0145] As also mentioned above, glass plies formed from the borosilicate glass compositions disclosed herein are more resistant to thermal shock than soda-lime-silicate glass. Fig. 6A and 6B The effect of thermal shock load is shown. Specifically, the fusion-formed glass composition disclosed herein ( Fig. 6A ) and soda-lime silicate glass ( Figure 6B ) is used for the sample Figure 5A and 5B The Vickers indenter in question was used to make an indentation at 2 kgf. The sample was then heated to a maximum of 150°C, and a water drop (25°C ± 5°C) was dropped onto the indentation point while the sample was still hot. Figure 6B It can be seen that cracks in the soda-lime-silicate glass propagate readily during this thermal shock event. In contrast, cracks in the fusion-formed borosilicate glass composition remain confined to Fig. 6A Annular crack boundaries are shown. One reason for thermal shock resistance is that the annular crack boundaries prevent radial crack extension. Another reason for thermal shock resistance is that the LTCTE of fusion-formed borosilicate glass compositions is much lower than that of soda-lime silicate (5.6 ppm / °C or less for fusion-formed borosilicate glass compositions and 8.0 ppm / °C for soda-lime silicate).
[0146] Unless otherwise stated, it is not intended that any method described herein be construed as requiring that its steps be performed in a specific order. Therefore, when a method claim does not actually state that its steps follow a certain order or it does not specifically indicate in any other way in the claims or specification that the steps are limited to a specific order, it is not intended to imply any particular order. In addition, as used herein, the article "a" is intended to include one or more than one component or element, and is not intended to be construed as meaning only one.
[0147] It will be apparent to those skilled in the art that various modifications and variations may be made without departing from the spirit or scope of the illustrated embodiments. Because those skilled in the art may conceive of various modifications, combinations, sub-combinations, and variations of the disclosed embodiments that incorporate the spirit and substance of the embodiments, the disclosed embodiments should be considered to include all of the contents within the scope of the appended claims and their equivalents.
[0148] ***
[0149] According to an exemplary embodiment and further in accordance with the information disclosed above, a vehicle windshield or other article may include: a first ply (eg, an outer ply, a glass sheet; see e.g. Figure 3A first glass ply 310) comprising a first major surface (e.g., an outer surface, a front-facing surface) and a second major surface opposite the first major surface; a second ply (e.g., an outer ply, a glass sheet; see, e.g., second glass ply 320) comprising a third major surface and a fourth major surface opposite the third major surface; and an intermediate layer (see, e.g., intermediate layer 330) connecting the second major surface of the first ply to the third major surface of the second ply. In contemplated embodiments, any of the first, second, third, and / or fourth surfaces may be coated, for example, with a functional layer, such as: a UV light reflecting layer, a hydrophobic layer, an adhesion promoting layer, etc., as disclosed above.
[0150] In some embodiments, the second ply is a tempered soda lime silicate glass. In other embodiments, the second ply is an ion exchanged aluminoborosilicate glass. In other embodiments, the second ply is a glass ceramic. In some embodiments, the interlayer comprises a polymer, such as polyvinyl butyral.
[0151] Referring to Tables 1-3, the low temperature coefficient of thermal expansion of the compositions disclosed herein may range from greater than 4.4 ppm / °C to less than 6.09 ppm / °C, such as 4.5 ppm / °C to 6 ppm / °C, to 5.8 ppm / °C and / or 5.6 ppm / °C. As shown, the LTCTE is obtained by measuring the expansion of the glass at temperatures from 0°C to 300°C, such as by thermomechanical analysis as described in ASTM test method E831 (reference 4). In other contemplated embodiments, the glasses disclosed herein having unique fracture behavior may not have a viscosity for fusion forming, and the glasses may have a lower or higher LTCTE. In some embodiments, the LTCTE of the compositions disclosed herein is less than 8.7 ppm / °C (which may be associated with soda-lime silicate glass) and / or greater than 3.25 ppm / °C (which may be associated with lower CTE borosilicates). Therefore, it may be counter-intuitive that the thermal shock resistance of the glasses disclosed herein may not be as good as some lower CTE borosilicates. However, applicants have discovered that higher CTE (e.g., greater than 3.25 ppm / °C) may result in higher surface compression after thermal reforming. The disadvantages associated with lower thermal shock resistance can be compensated by the unique fracture mechanism of the glasses disclosed herein, as discussed further below. As a result, the glasses disclosed herein are more thermally resistant than soda-lime silicates due to having a LTCTE below 8.7 ppm / °C, and may also have improved blunt impact performance compared to other borosilicates.
[0152] In some embodiments, the thickness of the first ply is at least 200 μm and no more than 1 cm, and / or the thicknesses disclosed above, such as 0.1 mm to about 6 mm. In other contemplated embodiments, the first ply, single ply, monolithic sheet, substrate, or other article of borosilicate glass disclosed herein can have such thicknesses disclosed above or other thicknesses, such as: less than 200 μm and / or at least 20 μm, or at least 1 cm and / or less than 1 m, wherein the thickness of the article (e.g., glass sheet, ply) can be constant or approximately constant, such as within 100 μm of the average thickness of the corresponding article, such as within 10 μm of the average thickness, or the thickness of the article can vary, such as for glass containers with thicker lips or bottoms.
[0153] According to an exemplary embodiment, the interlayer acts as a buffer for the first ply relative to the second ply, thereby reducing crack communication therebetween. In contemplated embodiments, the interlayer has a modulus of rigidity that is less than that of the glass of the first and / or second ply, such as less than 0.7 thereof, such as less than 0.5 thereof.
[0154] According to an exemplary embodiment, the intermediate layer is adhered to the first ply, thereby controlling the fragment loss from the rupture of the first ply. In some embodiments, the intermediate layer directly contacts the first ply. As discussed above, in some embodiments, the intermediate layer is adhered to the first ply, the second ply, and / or both, and connects the first and second plies. According to an exemplary embodiment, the second ply reinforces the first ply, making the first ply stiff to resist bending forces applied thereto. However, in other contemplated embodiments, the first ply may be independent of the second ply or the intermediate layer, and may instead be, for example, monolithic.
[0155] According to an exemplary embodiment, the first ply has a curvature such that the second major surface is concavely curved, and the second ply has a curvature such that the third major surface is convexly curved and conforms to the second major surface, as disclosed above so that the first major surface of the first ply is configured as an outward-facing surface of a glazing (e.g., a laminate glazing, such as a windshield) and is configured to be outboard when installed on a vehicle.
[0156] According to an exemplary embodiment, the first ply comprises a borosilicate glass composition, such as those disclosed herein. In terms of constituent oxides, the borosilicate glass composition of the first glass ply comprises: (i) SiO2, B2O3 and / or Al2O3; and (ii) one or more alkali metal oxides (also referred to as basic oxides; for example, Li2O, Na2O, K2O, Rb2O, Cs2O) and / or one or more divalent cation oxides (zinc oxide and / or alkaline earth metal oxides, also referred to as alkaline earth oxides, such as MgO, CaO, SrO, BaO).
[0157] According to some embodiments, such as those exhibiting self-terminating crack loop behavior as disclosed herein, the concentrations in terms of mole percentage of SiO2, B2O3, the one or more alkali metal oxides, Al2O3 (when included in the composition), and the one or more divalent cation oxides satisfy some (e.g., a combination of one or more) or all of the following relationships: (Relationship 1) SiO2 ≥ 72 mol%, such as SiO2 ≥ 72.0, such as SiO2 ≥ 73.0, such as SiO2 ≥ 74.0, and / or SiO2 ≤ 92, such as SiO2 ≤ 90; (Relationship 2) B2O3 ≥ 10 mol%, such as B2O3 ≥ 10.0, for example, B2O3≥10.5, and / or B2O3≤20, for example, B2O3≤18; (Relationship 3) (R2O+R'O)≥Al2O3, for example, (R2O+R'O)≥(Al2O3+1), for example, (R2O+R'O)≥(Al2O3+2); and / or (Relationship 4) 0.80≤(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])≤0.93, wherein R2O is the sum of the concentrations of the one or more alkali metal oxides, and when contained in the borosilicate glass composition, R'O is the sum of the concentrations of the one or more divalent cation oxides. For example, R2O may be the sum of Li2O, Na2O, K2O, Rb2O, and Cs2O; and for example, R'O may be the sum of MgO, CaO, SrO, BaO, and ZnO.
[0158] The inventive glasses disclosed herein may include additional constituent components. In some embodiments, the borosilicate glass composition may further include P2O5. It should be noted that if P2O5 is added to the glass, it should be treated as a non-rotatable network former (u or v) when considering equation (4) such as R2O or R'O, where equations (3) and (4) can be rewritten as (R2O+R'O+P2O5)≥Al2O3 and 0.80≤(1-[(2R2O+2R'O+2P2O5) / (SiO2+2Al2O3+2B2O3)])≤0.93. Other minor chemical components (e.g., fining agents SnO2, Sb2O3, NaCl) are generally negligible with respect to rotatability and fracture behavior. Other minor chemical components (e.g., colorants, e.g., concentrations less than 0.5 mol%) are negligible.
[0159] Applicants believe that relationships (3) and (4) may be related to the fracture behavior of the borosilicate glass compositions disclosed herein and characterize the "rotatability" aspect of the corresponding compositions. For compositions of the form xSiO2·yAl2O3·zB2O3·uR2O·vRO, where x, y, z, u, v represent the mole % or mole fraction of each type of oxide. If (u+v)≥y, then Applicants believe that the fracture behavior is related to the rotatability parameter (1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)]). For values of the rotatability parameter of 0.80 to 0.93, Applicants found that Vickers indenter testing produced radial and transverse cracks that were contained within small (<1 mm diameter) crack loops. As a result, glass sheets within this range did not crack to failure in Vickers indenter testing, but instead only formed small circular cracks that contained other cracks and prevented them from propagating.
[0160] Similarly, Applicants believe that density can be correlated to the fracture behavior of the borosilicate glass compositions disclosed herein. According to exemplary embodiments, the density of the glass is greater than 2.230 g / cm 3 and / or less than 2.397 g / cm 3 , and this cracking behavior is observed in this range.
[0161] Vickers indenter testing can be used to characterize the fracture behavior of the glass, as discussed in Gross et al., Crack-resistant glass with high shear band density, Journal of Non-Crystalline Solids, 94 (2018) 13-20, and Gross, Deformation and cracking behavior of glasses indented with diamond tips of various sharpness, Journal of Non-Crystalline Solids, 358 (2012) 3445-3452, both of which are incorporated herein by reference. In some embodiments, when the glass of the borosilicate glass composition having the first glass ply is formed into at least 10 1 mm thick and having a major surface of at least 2x2 cm 2 Polished flat samples (e.g., 100 samples) of area (e.g., 2 cm by 2 cm square) and tested with a square-based 136° four-sided pyramid Vickers indenter directed orthogonally into the center of the major surface at 25°C, 50% relative humidity and quasi-static displacement of the indenter at a rate of 60 μm per second up to a maximum indentation load of 3 kg force for 10 seconds (unless sample fracture failure occurs first), most of the time (at least 51 out of 100 times; at least 6 out of 10 times), all cracks extending radially and / or laterally through the sample from below the indenter tip (i.e., where the indenter tip contacts the glass) are interrupted by self-terminating crack loops (e.g., annular cracks), so that sample cracking from the Vickers indenter is confined to cracking in the loop. Essentially, the indenter crushes and cracks the glass below the indenter. However, the crack loop forms and prevents cracks originating from the indenter contact from propagating beyond the crack loop. Conversely, otherwise, in other glasses, transverse or radial cracks may form before and / or pass through such crack loops (e.g., abnormal cracking), or may not form crack loops (e.g., normal cracking), and in either case, the transverse or radial cracks will not be contained by the crack loops and may propagate throughout the entire glass product, resulting in fracture through the product and its failure.
[0162] Table 100 below summarizes the values of the rotatability parameter (1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)]), density, and Vickers indentation fracture behavior for various borosilicate glass compositions tested.
[0163] Table 100 (divided into three parts to fit the page)
[0164]
[0165]
[0166] In Table 100, for some compositions, the fracture behavior is identified as "contained" rather than "abnormal" or "normal" fracture behavior. The radial and transverse cracks contained in the crack loop (e.g., circular annular cracks) did not extend beyond the crack loop, even after several hours of indentation testing (e.g., 12 hours, 24 hours, 72 hours). Thus, such samples have cracks that are contained in the crack loop and only partially open, and there is no failure beyond the crack loop. As summarized in Table 100, the applicant observed polished flat samples of 1 mm to 3.3 mm thickness tested with a square 136° four-sided pyramid Vickers indenter at a quasi-static displacement rate of 60 μm per second until fracture or up to a maximum force of 3 kg (indentation load and hold for 10 seconds). In addition, as verified by the contained radial and transverse cracks, when the corresponding samples were rapidly cooled by placing them in cold water, the cracks did not propagate beyond the crack loop and the observed samples did not fail outside the crack loop. For the rapidly cooled samples, the radial and transverse cracks contained within the crack loop did not extend beyond the crack loop, even after several hours of indentation testing (eg, after 2 hours, 12 hours, 24 hours, 72 hours).
[0167] For the compositions labeled DUE in Table 100, the crack loops were observed to be in the form of circular rings or annular cracks (see approximately Figure 5A and 6A ). When loaded to 2kg force, the ring radius ranges from 101 to 136 microns. When loaded to 3kg force, the ring radius ranges from 119 to 229 microns.
[0168] In addition, for the composition labeled DUE in Table 100, 19 different indentation tests were performed on samples with a thickness of 1 mm, and the results were that 19 of the 19 tests had circular annular cracks that accommodated radial and transverse cracks from the indenter. Applicants expect to have similar results for more tests, such as at least 90, such as at least 95, such as at least 98 of the 100 samples.
[0169] Applicants observed that for some samples, cracks may be delayed but show up at the latest within approximately 2 hours of indentation testing. However, radial and transverse cracks of the DUE samples were contained within the crack loop and did not extend beyond the crack loop, even after several hours of indentation testing (e.g., after 2 hours, 12 hours, 24 hours, 72 hours).
[0170] For the composition marked as DQS in Table 100, 10 different indentation tests were performed on samples with a thickness of 1 mm, and the result was that 10 of the 10 samples produced a crack loop in the form of a donut-shaped annular crack that accommodated radial and transverse cracks from the indenter. The radial and transverse cracks did not extend beyond the crack loop, even after several hours of indentation testing (e.g., after 2 hours, 12 hours, 24 hours, 72 hours). Applicants expect to have similar results for more tests, such as at least 90, such as at least 95, such as at least 98 of the 100 samples.
[0171] Testing the same DQS composition on samples with a thickness of 3.3 mm, 16 out of 20 different tests resulted in circular annular cracks that accommodated radial and transverse cracks originating from the indenter. Applicants expect to have similar results for more tests, such as at least 50 out of 100 samples, such as at least 60, such as at least 75. Without being bound by theory, applicants believe that the reduced percentage of occurrence for the 3.3 mm sample may be due to the heterogeneity of the sample rather than the thickness.
[0172] For the samples marked as DSX composition in Table 100, 21 different indentation tests were performed for samples with a thickness of 1 mm, and the results were 19 with circular annular cracks that accommodated radial and transverse cracks from the indenter. Applicants expect to have similar results for more tests, such as at least 70, such as at least 80, such as at least 90 of the 100 samples. Those radial and transverse cracks did not extend beyond the crack loop, even after several hours of indentation testing (e.g., after 2 hours, 12 hours, 24 hours, 72 hours).
[0173] like Fig.14 As shown, applicants were able to observe cross sections of samples of borosilicate glass as disclosed herein to view the cracking of the samples via fractographic analysis. The images showed cracking of a normal cone below the indentation location, which then appeared to change direction and return to the same surface, possibly forming a crack loop. In addition, the crack cone continued to extend through the sample to the opposite surface. Applicants believe this is a newly discovered fracture behavior of the glasses and structures disclosed herein.
[0174] In contemplated embodiments, the glass articles (e.g., sheets, plies, films, covers, tubes, containers) of borosilicate glass disclosed herein comprise one or more crack loops as disclosed above, e.g., having a substantially circular perimeter, e.g., a circular perimeter. The crack loops may be particularly small, e.g., having a cross-sectional dimension in a direction along the surface of the glass article of less than 10 mm, e.g., less than 2 mm, e.g., less than 1 mm, e.g., less than 0.7 mm (e.g., less than 1 mm, e.g., less than 0.7 mm). Fig. 6A), and / or at least 10 μm, for example at least 50 μm, for example at least 100 μm, for example at least 200 μm.
[0175] The thickness of the article, the uniformity of the article dimensions, the loading rate, the composition and microstructure of the borosilicate glass, the support beneath the article, the geometry of the indenter, or other parameters may affect the fracture behavior. For example, Applicants have demonstrated different size crack loops resulting from DUE compositions at different loads as discussed above.
[0176] If the cone extends to the opposite surface and the crack loop intersects the cone (e.g. Fig.14 As shown), the annular crack combined with the cone may form a crack closed section of the article that completely penetrates the article. At least a portion of the crack closed section may have a circular perimeter, such as at the surface of the article. The crack closed section may generally have a conical shape, an hourglass shape, or other shapes. Due to the unique fracture behavior of the borosilicate glass disclosed herein, the purposeful mechanical fracture of the glass article can be used to form holes or other precise geometric features, such as surface depressions in which the cone does not extend completely through the article. Etching agents, lasers, plasmas, heating, etc. can be used to further process the article, such as capturing cracks and blunting sharp edges associated with cracking.
[0177] In contemplated embodiments, the article may have at least one crack loop and / or associated structure (e.g., hole) as disclosed above, or the article may have more than one crack loop, such as at least 10, at least 100, at least 1000 crack loops, which may be connected with a cone to completely penetrate such an article to form a hole (when the (cracked) glass inside the crack loop is removed mechanically or by a chemical etchant). Such articles may be used as, for example, a screen, mesh, panel, substrate, or component in a battery or electronic device. Lines of small crack loops in series (e.g., perforated lines) can help control the separation of sheets or shapes by guiding cracks between loops. The formation of holes in the article can achieve air permeability of the article, and / or allow liquids, adhesives, polymers in a fluid state, conductive metals, etc. to pass through the article. The loop cracks can be arranged in a pattern or multiple patterns on the article. In some contemplated embodiments, such as for articles (e.g., sheets) having more than one crack loop, the crack loops may vary in size, such as where one or more crack loops are at least 20% larger in diameter than another crack loop in the same article.
[0178] Controlled cracking of articles (e.g., borosilicate glass sheets) as disclosed herein may be different from cracking a glass sheet using a laser to form a perforation or other hole or feature because the crack loop disclosed herein may be a single continuous crack loop, as opposed to many smaller cracks extending in various directions. A crack loop may not propagate beyond the loop, as demonstrated by testing disclosed herein. In some embodiments, an article containing one or more crack loops or related structures may not require or may require less etchant or other means to blunt the edges or to cause microcracking.
[0179] Nevertheless, some of the inventive glasses disclosed herein may have conventional fracture behavior, such as a glass that is a borosilicate glass that can be fusion-formed, but has normal or abnormal cracking in the Vickers indentation test disclosed herein. And vice versa, some of the inventive glasses disclosed herein may have unique crack loop fracture behavior, such as a glass that is a borosilicate glass but may be more difficult to fusion-form. Other embodiments may have unique fracture behaviors and fusion-formability, thereby providing glasses that are particularly advantageous for outer plies in laminate windshields or other articles disclosed herein.
[0180] The entirety of each of U.S. Application No. 63 / 023518 filed on May 12, 2020, No. 17 / 327870 filed on May 24, 2021, No. 63 / 088525 filed on October 7, 2020, No. 17 / 068272 filed on October 12, 2020, No. 63 / 136381 filed on January 12, 2021, No. 63 / 151210 filed on February 19, 2021, No. 63 / 177536 filed on April 21, 2021, and No. 63 / 209489 filed on May 11, 2021 is incorporated herein by reference. U.S. Application No. 63 / 059105 filed on July 30, 2020 is incorporated herein by reference in its entirety. U.S. Application No. 63 / 050181, filed on July 10, 2020, is incorporated herein by reference in its entirety.
[0181] ***
[0182] According to exemplary embodiments and further based on the information disclosed above, other examples are described herein. Table 200 below summarizes the described other examples.
[0183] Table 200
[0184]
[0185]
[0186] As shown in Table 200, the composition of Example 26 includes: greater than or equal to 12 mol% B2O3, an amount of Al2O3 greater than or equal to 3 mol% and less than or equal to 5 mol%, an amount of Na2O greater than or equal to 4 mol% and less than or equal to 6 mol%, and meets the relationships (1), (2), (3), and (4) described herein. Therefore, the glass constructed according to Example 26 exhibits the favorable fracture behavior described herein and can also be fusion-formed to produce glass products suitable for the uses described herein.
[0187] In an embodiment, the glass composition described herein includes Al2O3 and Na2O in an amount satisfying the relationship Na2O>Al2O3+1 (e.g., Na2O>Al2O3+1.25, Na2O>Al2O3+1.5, Na2O>Al2O3+1.75, Na2O>Al2O3+2.0). In an embodiment, the glass composition described herein has an Al2O3 content greater than or equal to 2.0 mol% and less than or equal to 5.0 mol% (e.g., greater than or equal to 2.5 mol% and less than or equal to 5.0 mol%, greater than or equal to 3.0 mol% and less than or equal to 5 mol%). When combined with a composition having greater than or equal to 12.0 mol % B2O3 (e.g., greater than or equal to 13.0 mol % B2O3, greater than or equal to 14.0 mol % B2O3, greater than or equal to 15.0 mol % B2O3 and less than or equal to 16 mol % B2O3), such Al2O3 content is sufficient to prevent phase separation of the borosilicate glass, but is still low enough so that SiO2 and B2O3 are the primary network formers in the glass. When the Al2O3 content is at such levels, the Na2O content in excess of Al2O3 aids in the dissolution of silica during the glass melting process. In embodiments, the Na2O content in the glass compositions described herein is less than or equal to 6.25 mol (e.g., less than or equal to 6.20 mol %, less than or equal to 6.15 mol %, less than or equal to 6.10 mol %, less than or equal to 6.05 mol %, less than or equal to 6.0 mol %), as Na2O in excess of this amount may result in an undesirably high CTE for the glass. In such embodiments, the Na2O content is at least 4.0 mol%. In embodiments, when the Na2O content meets these criteria, K2O, if included, is included in an amount less than Na2O, such as an amount greater than or equal to 0.8 mol% and less than or equal to 5 mol%, but less than the amount of Na2O, because K2O tends to increase the CTE to a greater extent than Na2O per unit composition. For example, in embodiments, the glass compositions described herein include a ratio of K2O to Na2O of about 0.1 to about 0.75. Glass compositions that meet the foregoing constraints can be suitable for fusion forming and exhibit the unique fracture behavior described herein, while still having an advantageously low CTE.
[0188] In an embodiment, the glass composition of the present disclosure includes: greater than or equal to 12.0 mol% B2O3, greater than or equal to 2.0 mol% and less than or equal to 5.0 mol% Al2O3 or greater than or equal to 3.0 mol% and less than or equal to 5.0 mol% Al2O3, greater than or equal to 4.0 mol% and less than or equal to 6.25 mol% Na2O, and greater than or equal to 0.8 mol% and less than or equal to 5.0 mol% K2O, wherein Na2O is greater than or equal to Al2O3+1.0 and the ratio of K2O content to Na2O content is greater than or equal to 0.1 and less than or equal to 0.75. Such composition range setting helps to produce the glass described herein, which has a liquidus viscosity greater than or equal to 500 kP and meets the CTE requirements described herein (e.g., LTCTE is 5.1 ppm / °C or less).
[0189] Samples having the composition of Example 26 provided in Table 300 were tested for various properties. In the first set of tests, the samples were subjected to various chemical treatments to determine the chemical durability of the samples. Two glass samples (2" by 2") having different compositions were subjected to the same chemical treatment as a comparative basis. Comparative Example 26A was a borosilicate glass comprising: 83.60 mol% SiO2, 1.20 mol% Al2O3, 11.60 mol% B2O3, 3.00 mol% Na2O, and 0.70 mol% K2O. Comparative Example 26B was an uncolored soda-lime silicate glass. Each sample was immersed in a 5% w / w HCl solution at an elevated temperature of 95°C for a period of 24 hours. Samples of the same composition were also immersed in a 5% w / w NaOH solution at an elevated temperature of 95°C for a period of 6 hours. After immersion, the samples were cleaned and subsequently dried. The optical transmittance of each sample at 450 nm was measured. Haze was also measured. The results are shown in Table 300 below.
[0190] As used herein, the terms "transmission haze" and "haze" mean the percentage of transmitted light scattered outside an angular cone of about ±2.5° as measured according to ASTM method D1003 (entitled "Standard Test Method for Haze and Luminous Transmittance of Transparent Plastics," which is incorporated herein by reference in its entirety). Unless otherwise noted, all haze measurements reported in this disclosure were obtained using a Haze-Gage Transmitter (Paul N. Gardner Company). For optically smooth surfaces, transmission haze is typically close to zero.
[0191] Table 300
[0192]
[0193] As shown in Table 300, the sample according to Example 26 described herein had a lower weight loss (about 0.010 mg / cm 2 ) and exhibited favorable optical quality, with excellent transmittance compared to both comparative examples. Alkaline chemical treatment in NaOH solution resulted in higher weight loss for both samples according to Example 26 and Comparative Example 26A. Although the sample according to Comparative Example 26B (soda-lime silicate glass) experienced lower weight loss in alkaline solution, such treatment resulted in increased haze (representing a poor optical appearance). These results indicate that the compositions described herein can have chemical durability for use in applications such as glass containers for various liquids (e.g., pharmaceutical containers, such as vials, syringes, ampoules, and cartridges).
[0194] Example 26 contained 0.1 wt % Fe2O3 as shown in Table 200. The transmission spectra of the 3.3 mm thick samples were measured for comparison with the results contained in Table 5 herein. Fig.15 Transmittance spectra measured according to ISO 13837 for samples according to Example 26 and another example with 0 mol% Fe2O3 (Example 3 in Table 1 above) are provided. It can be seen that the addition of Fe2O3 reduces the overall measured transmittance, especially in the infrared spectrum (greater than or equal to 750nm). The UV cut-off wavelength is also greater than 300nm (approximately 320nm), indicating greater UV absorption compared to the iron-free embodiment, and the transmittance is greater than or equal to 90% across the visible spectrum. Such results indicate the suitability of the glasses described herein for use in windshields while providing shielding from solar heat and UV rays while still providing a favorable transmittance in the visible spectrum. The composition according to Example 26 has a higher transmittance across the visible spectrum, which provides a clearness that is beneficial for use in windshields while still blocking the UV and IR portions of sunlight.
[0195] A 3.3 mm thick sample having a composition according to Example 26 and a 2.1 mm thick sample having a composition according to Example 29 were prepared for optical testing. Each sample was tested for visible light transmission (T VIS ) and total solar transmittance (TTS). The results are provided in Table 400 below.
[0196] Table 400
[0197] Example 26 (3.3 mm) Example 29 (2.1 mm) Fe source Oxalate Oxalate Fe Levels 0.1 wt% 0.3 wt% UV Cut-off 320nm 378nm Tuv 59.5 12.0 Tvis 91.6 88.5 TTS 90.8 87.0
[0198] As shown in Table 400, despite having greater thickness, the sample with 0.1 wt. % Fe2O3 has over 90% visible light transmission, while the samples with greater Fe2O3 content do not. Depending on the visible light transmission requirements, a suitable amount of iron oxide can be provided for the glass compositions described herein.
[0199] See also Fig.16 , samples with a thickness of 2 mm and the composition of Example 26 and Counter Examples 26a and 26b were subjected to flexural strength testing after being indented with a Vickers indenter (both before and after inducing thermal shock). The flexural strength testing was performed via a ring-on-ring test, which is generally performed according to the ASTM C-1499-03 standard test method for monotonic equibiaxial flexural strength of advanced ceramics at ambient temperature. Specifically, the samples according to Example 26 and Counter Examples 26a and 26b described herein were indented with a Vickers indenter at 3 kgf, as described above with respect to Figure 5A and 5B As discussed in the previous section. Then, for some specimens, a Ring-on-Ring test was performed immediately after indentation. After indentation, thermal shock was induced in some specimens by heating the specimens on a 125°C hot plate for 10 minutes. After heating, a drop of water (25°C ± 5°C) was dropped onto the indentation point while the specimens were still hot. The specimens were then subjected to a Ring-on-Ring test after cooling to determine the effect of thermal shock on flexural strength.
[0200] like Fig.16 As shown, the sample according to Example 26 exhibits a comparable level of retained strength as the sample according to Counter Example 26a after being thermally shocked. This comparable result is expected to be the result of a ring-on-ring test scheme. During the test, the ring is placed centered on the indentation and contacts the glass on the surface opposite to the indentation. Due to the alignment between the ring and the indentation, it is believed that the containment fracture behavior (ring cracks contain radial extension cracks) exhibited by the glass according to Example 26 has a minimized effect on the retained strength measurement. Considering that some glasses of the present disclosure have a higher CTE than conventional borofloat glass, it is not surprising that thermal shock results in a reduced flexural strength compared to samples that have not been thermally shocked. However, despite having a higher LTCTE, the sample according to Example 26 has a comparable level of retained strength as those constructed according to Counter Example 26a. The sample according to Example 26 has a higher level of retained strength than those constructed according to Counter Example 26b, which shows that the glass described herein provides a favorable retained strength and thermal performance compared to certain existing glass compositions used in existing glass laminates.
[0201] See also Figures 17A-17CThe samples having the composition according to Example 26 and Counter Examples 26a and 26b were subjected to a transverse Knoop scratch test on their surfaces to determine the scratch resistance. The sample surfaces were scratched at about 23° C. and about 50% relative humidity using a mechanical tester equipped with a Knoop diamond. The scratch length on each sample was 5.0 mm, and the sample was scratched at a speed of 24 mm / min. Fig.17A Images of samples having a composition according to Example 26 and scratched at 5N and 7N loads are shown. Fig. 17B Images of samples having a composition according to Counter Example 26a and scratched at 5N and 7N loads are shown. Fig. 17C Images of samples having a composition according to Counter Example 26b and scratched with 5N and 7N loads are shown. As shown, it is confirmed that the samples constructed according to Example 26 have a favorable scratch performance compared to the counter example. When the samples were scratched using a 5N load, the transverse crack width of the scratches of those samples had a maximum value of 67.7 μm. The samples constructed according to Counter Examples 26a and 26b had maximum transverse crack widths of 337.44 μm and 485 μm, respectively. Such results indicate that the glass compositions described herein can provide superior favorable scratch resistance performance compared to certain glasses currently used in various applications (e.g., automotive glass windows). In an embodiment, when scratched with Knoop diamond at a scratch rate of 24 mm / min, a glass article comprising a glass composition according to the present disclosure can exhibit a maximum transverse crack width of less than or equal to 80 μm (e.g., less than or equal to 75 μm, less than or equal to 70 μm).
[0202] As this article about Figure 3-4 As mentioned above, the glass compositions described herein can be sought for use in curved glass articles, such as curved glass laminates. For example, the glass according to the present disclosure can be used as Figure 3-4 , while a glass having a different composition (e.g., annealed soda-lime silicate glass, ion-exchanged aluminoborosilicate glass, etc.) may be used as the second glass layer 310. For example, in the manufacturing process of the curved glass laminate 400 (see Figure 4 ), the glass sheets 310, 320 may be subjected to a co-sag process, wherein the glass sheets 310, 320, which are initially flat, may be heated to a suitable sag temperature and bent to a suitable depth of curvature. As used herein, "sag temperature" means that the viscosity of the glass substrate is about 10 11The sag temperature is determined by fitting the Vogel-Fulcher-Tamman (VFT) equation (Logh=A+B / (TC), where T is temperature, A, B, and C are fitting constants, and h is dynamic viscosity) to the annealing point data measured using bending beam viscosity (BBV) measurements and to the softening point data measured by fiber drawing. In an embodiment, the glass compositions used in the glass plies 310, 320 include sag temperatures that differ from each other by 5°C or more, about 10°C or more, about 15°C or more, about 20°C or more, about 25°C or more, about 30°C or more, or about 35°C or more.
[0203] In an embodiment, the glasses described herein (such as those according to the embodiments described herein) include 10 11 Such viscosities are comparable to certain soda lime silicate compositions used in glass laminates at the same temperature. As a result, glasses according to the present disclosure are suitable for co-sag using existing methods and processes and can be formed into laminates having the advantageous optical deformation and shape matching performance described herein.
[0204] After heating to a suitable sag temperature and sag to a desired bend shape, the glass plies 310, 320 may be cooled at a suitable cooling rate. As a result of the cooling, the surface of the glass ply 310 (which may be formed from a glass composition according to embodiments described herein) may cool at a rate exceeding the central region of the glass ply 310, resulting in compressive stresses extending inward from the surface of the glass ply 310 to a compression depth and tensile stresses extending inward from the compression depth in the central region. Such tensile and compressive stresses are "annealing stresses". In an embodiment, the compressive stress extending into the glass ply 310 from the post-sag cooling has a compression depth equal to 0.21 times the thickness 210 of the glass ply 310 (see Figure 2 ). In such an embodiment, the magnitude of the tensile stress induced by cooling after sag can be approximated by the following method:
[0205]
[0206] Where E is the Young's modulus of the glass ply 310, α is the coefficient of thermal expansion of the glass within the temperature range over which cooling is performed, t is the thickness of the glass ply 310, R is the cooling rate, K is the thermal diffusivity of the glass, and v is the Poisson's ratio of the glass. The compressive stress integrated from the compression depth to the surface of the glass ply 26 can be calculated as -2*σ CT The film stresses were calculated for glasses constructed according to Example 26 and Counter Examples 26a and 26b described herein. The results are contained in Table 500 below.
[0207] Table 500
[0208] CE 26b CE 26a Embodiment 26 E(GPa) 72 62.8 62.7 Poisson's ratio 0.22 0.2 0.196 CTE(ppm / C) 8.8 3.25 4.5 <![CDATA[Thermal diffusivity at 600 °C (cm 2 / s)]]> 0.004813 0.006026 0.00565 Cooling rate (℃ / s) 1.67 1.67 1.67 Glass thickness(mm) 2.1 2.1 2.1 CT(MPa) 0.52 0.13 0.19 CS(MPa) -1.03 -0.26 -0.38 Compared with the CS ratio of Example 26 2.72 0.68 1 Glass thickness(mm) 3.8 3.8 3.8 CT(MPa) 1.69 0.42 0.62 CS(MPa) -3.38 -0.85 -1.25 Compared with the CS ratio of Example 26 2.72 0.68 1
[0209] As shown, the magnitude of the annealed central tension (denoted as "CT" in Table 500) and the compressive stress (denoted as "CS" in Table 500) of Example 26 is between the values of Counter Example 26b (soda-lime silicate glass) and Counter Example 26a (existing borosilicate glass). The CS and CT values were calculated at thicknesses of 2.1 mm and 3.8 mm. 2.1 mm is a common thickness for the outer ply of automotive glazing. As shown, at a thickness of 2.1 mm, the sample constructed according to Example 26 included an annealed tensile stress of 0.19 MPa, which is greater than the 0.13 MPa achieved by existing borosilicate glass and less than the 0.52 MPa achieved by soda-lime silicate glass. At a thickness of 3.8 mm, the sample constructed according to Example 26 included an annealed tensile stress of 0.62 MPa, which is greater than the 0.42 MPa achieved by existing borosilicate glass and less than the 1.69 MPa achieved by soda-lime silicate glass. The annealed stress can be measured using a SCALP apparatus.
[0210] ***
[0211] According to exemplary embodiments and further based on the information disclosed above, other aspects of the example glass compositions described herein will now be described.
[0212] In the following paragraphs, when used to describe a particular constituent component in a glass composition, the term "undefined" refers to a constituent component that is not intentionally added to the glass composition and is present in an amount less than 0.10 mol%. The undefined component may be added to the glass composition unintentionally as an impurity in another constituent component and / or by migration of the undefined component into the composition during processing of the glass composition.
[0213] In the following paragraphs, the terms "free of" and "substantially free of" are used interchangeably herein to refer to the amount of a particular component in a glass composition that has not been intentionally added to the glass composition and / or the absence of the particular component. It is to be understood that the glass composition may contain trace amounts of a particular constituent component as a contaminant or an unspecified amount of less than 0.10 mol%.
[0214] In the following paragraphs, the term "glass former" is used herein to refer to a component that, when present alone in a glass composition (i.e., without other components, except in undetermined amounts), is capable of forming a glass when a melt is cooled at a rate not exceeding about 300°C / min.
[0215] In the following paragraphs, the term "modifier" refers to an oxide of a monovalent or divalent metal, i.e., RO or RO, where "R" represents a cation. Modifiers can be added to glass compositions to alter the atomic structure of the melt and the resulting glass. In some embodiments, the modifier can change the coordination number of cations present in the glass former (e.g., boron in B2O3), which can result in the formation of a more polymeric atomic network and, as a result, can provide better glass formation.
[0216] In the following paragraphs, the term "rare earth metals" refers to the metals listed in the lanthanide series of the IUPAC periodic table of the elements plus yttrium and scandium. As used herein, the term "rare earth metal oxides" is used to describe oxides of rare earth metals in different redox states, such as "+3" for lanthanum in La2O3, "+4" for cerium in CeO2, and "+2" for europium in EuO, etc. Generally speaking, the redox state of the rare earth metals in the oxide glass can change, and in particular, the redox state may change during the melting process based on the batch composition and / or the redox conditions in the furnace where the glass is melted and / or heat treated (e.g., annealed). Unless otherwise stated, the rare earth metal oxides in this article are described in their standard formula, wherein the rare earth metal oxide has a redox state of "+3". Therefore, in the case where a rare earth metal having a redox state other than "+3" is added to the glass composition batch, the glass composition is recalculated by adding or subtracting some oxygen to maintain the stoichiometric ratio. For example, when CeO2 (cerium in the "+4" redox state) is used as a batch component, the resulting batch composition is recalculated assuming that 2 moles of CeO2 are equivalent to 1 mole of Ce2O3, and the resulting batch composition exhibits Ce2O3. As used herein, the term "RE m O n " is used to refer to the total content of rare earth metal oxides in all redox states present, and the term "RE2O3" is used to refer to the total content of rare earth metal oxides present in the "+3" redox state (also specified as "trivalent equivalent").
[0217] In the arithmetic expressions used in the following paragraphs, the term "min(A,B)" represents the smallest of the values A and B, and the term "max(A,B)" represents the largest of the values A and B, where "A" and "B" can be any values (component concentrations, property values, etc.). The term "abs(X)" represents the absolute value of the value X (without a sign).
[0218] In the glass compositions described herein, SiO2 can play the role of the main glass former. Without wishing to be bound by theory, it is believed that tetrahedrons [SiO4] (as part of the structural network of the glass) are connected to other structural units (e.g., specifically tetrahedrons [AlO4] and trihedrons [BO3]) that may be rotatable. Such connections between tetrahedrons and trihedrons can lead to the abnormal fracture behavior described herein. In addition, it is found that SiO2 increases the viscosity of the melt forming the glass, increases the liquidus viscosity, reduces the coefficient of thermal expansion and increases the Young's modulus, thereby improving the mechanical properties. Then, in the case of high content of silica, the glass can become more chemically durable. However, when the SiO2 content in the glass composition becomes too high, this may lead to unacceptably large high temperature viscosity, which may lead to certain difficulties in melting, such as corrosion of refractory materials in glass melting tanks. In addition, at very high content of SiO2, the structural network of the glass may contain insufficient amount of rotatable units, which may lead to the loss of abnormal fracture behavior. Thus, in embodiments, in addition to the other ranges of SiO2 content described herein, the glass compositions described herein may contain SiO2 in an amount greater than or equal to 60.0 mol% and less than or equal to 96.0 mol%, greater than or equal to 60.0 mol% and less than or equal to 80.0 mol%, greater than or equal to 60.0 mol% and less than or equal to 77.5 mol%, greater than or equal to 72.0 mol% and less than or equal to 78.0 mol%, greater than or equal to 73.0 mol% and less than or equal to 77.0 mol%, Greater than or equal to 73.4 mol % and less than or equal to 76.8 mol %, greater than or equal to 73.8 mol % and less than or equal to 76.4 mol %, greater than or equal to 74.62 mol % and less than or equal to 75.88 mol %, greater than or equal to 65.0 mol % and less than or equal to 75.9 mol %, greater than or equal to 72.0 mol % and less than or equal to 75.9 mol %, greater than or equal to 73.0 mol % and less than or equal to 96.0 mol %, greater than or equal to 74.6 mol % and less than or equal to 75.9 mol %.
[0219] In the glass compositions described herein, B2O3 can play the role of a network former together with SiO2 and Al2O3. As part of the structural network of the glass, boron oxide can form either tetrahedron [BO4] or trihedron [BO3], depending on the content of the other components. Without wishing to be bound by a particular theory, it is believed that when the content of the modifier (monovalent metal oxide R2O and divalent metal oxide RO) in a specific glass composition exceeds the amount of alumina, the amount of tetrahedron [BO4] increases. In an embodiment, both trihedron [BO3] and tetrahedron [BO4] play an important role in the glass compositions described herein. Tetrahedron [BO4] can increase the connectivity of the structural network, which can make the structure more rigid and increase the viscosity, especially at low temperatures, without causing undesirable precipitation of refractory minerals from the melt. Trihedron [BO3] can be a rotatable structural unit, which can provide the abnormal fracture behavior described herein. Therefore, the glass compositions described herein include boron oxide. However, when the B2O3 content becomes too high, this may reduce the liquidus viscosity, which may potentially lead to the precipitation of refractory minerals in the glass. In addition, at high levels of boron oxide, the glass composition may not have acceptable durability against alkalis and acids, or the melt forming the glass may tend to undergo liquid-liquid phase separation, which may produce glass opacity. In an embodiment, in addition to the other ranges of B2O3 content described herein, the glass composition described herein may contain B2O3 in an amount greater than or equal to 1.0 mol% and less than or equal to 25.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 17.0 mol%, greater than or equal to 10.5 mol% and less than or equal to 19.0 mol%, greater than or equal to 11.75 mol% and less than or equal to 17.75 mol%, greater than or equal to 12.07 mol% and less than or equal to 13.8 mol%.
[0220] In research, it has been found empirically that adding even small amounts of rare earth metal oxides to the glass compositions described herein may result in an increase in the liquidus temperature and precipitation of refractory minerals. It has also been found empirically that the addition of rare earth oxides may reduce the chemical durability of the resulting glass, particularly with respect to acids. For this reason, in some embodiments of the present disclosure, the content of rare earth metal oxides in the glass composition is limited, or the glass composition may preferably be free of (or substantially free of) rare earth metal oxides.
[0221] The glass compositions of the present disclosure may also include lithium oxide (Li2O). Lithium oxide may play the role of a modifier, similar to other alkali metal oxides. However, it has been empirically found that the addition of Li2O to the glass compositions of the present disclosure may result in an increase in liquidus temperature and a decrease in liquidus viscosity. In addition, glasses with Li2O may have lower chemical durability than glasses with the same amount of other alkali metal oxides. It has also been found that Li2O potentially leads to a reduction in the abnormal fracture behavior described herein. Without wishing to be bound by theory, it is believed that the addition of Li2O may result in a higher cation packing density, which may increase density and reduce abnormal fracture behavior. Therefore, in an embodiment, the Li2O content in the glass composition may be limited, or the glass composition may preferably be free of (or substantially free of) Li2O.
[0222] The glass composition of the present disclosure may also contain magnesium oxide (MgO). In an embodiment, magnesium oxide may be added to the glass composition to increase the Young's modulus of the resulting glass and / or improve other mechanical properties. Magnesium oxide may advantageously not increase the density and not increase the thermal expansion coefficient of the glass to the same extent as other glass modifiers. It has also been found that adding a small amount of magnesium oxide to the glass composition of the present disclosure can improve abnormal fracture behavior. However, when the MgO content in the glass composition is too large, the melt forming the glass may cause refractory minerals to precipitate, which may increase the liquidus temperature and / or may cause the appearance of crystal defects in the glass product. Therefore, in an embodiment, the amount of magnesium oxide (MgO) contained in the glass composition of the present disclosure may be greater than or equal to 0.0 mol% to less than or equal to 5.0 mol%, and all ranges and sub-ranges between the above values. In an embodiment, the amount of MgO contained in the glass composition may be: less than or equal to 5.0 mol%, less than or equal to 2.5 mol%, less than or equal to 2.0 mol%, less than or equal to 1.8 mol%, or less than or equal to 1.75 mol%. In an embodiment, the glass composition may include MgO in an amount of greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 2.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.8 mol%, greater than or equal to 0.35 mol% and less than or equal to 1.75 mol%, greater than or equal to 0.68 mol% and less than or equal to 1.75 mol%, and greater than or equal to 0.0 mol% and less than or equal to 1.75 mol%.
[0223] The glass composition of the present disclosure may also include calcium oxide (CaO). Calcium oxide may be added to the glass composition to improve chemical durability and increase Young's modulus, thereby improving mechanical properties. In addition, alkaline earth oxides (such as CaO and MgO) tend to reduce the liquidus temperature and increase the liquidus viscosity. It has been found that adding a small amount of CaO can improve abnormal fracture behavior. However, when the content of CaO is high, this may cause the precipitation of refractory minerals, which may lead to the appearance of crystal defects in the glass product. In addition, adding a large amount of CaO to a glass composition with a high content of B2O3 may sometimes cause liquid-liquid phase separation of the melt, resulting in a loss of transmittance. Therefore, in an embodiment, the amount of calcium oxide (CaO) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 5.0 mol%, and all ranges and sub-ranges between the above values. In some other embodiments, the glass composition may include CaO in an amount of less than or equal to 5.0 mol%, less than or equal to 2.5 mol%, less than or equal to 2.0 mol%, less than or equal to 1.9 mol%, less than or equal to 1.7 mol%, less than or equal to 1.5 mol%, or less than or equal to 1.0 mol%. In some more embodiments, the glass composition may include CaO in an amount of greater than or equal to 0.0 mol% and less than or equal to 2.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.9 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.7 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.5 mol%, greater than or equal to 0.02 mol% and less than or equal to 1.02 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.0 mol%.
[0224] In an embodiment, the glass composition of the present disclosure may have a total amount of CaO and MgO (CaO+MgO) of less than or equal to 5.0 mol% or less than or equal to 2.5 mol%. In an embodiment, CaO+MgO is greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, or greater than or equal to 0.0 mol% and less than or equal to 2.5 mol%.
[0225] The glass composition of the present disclosure may also contain zirconium oxide (ZrO2). Zirconium oxide may be added to the glass composition of the present disclosure to improve mechanical properties and / or increase the viscosity of the melt forming the glass. However, it has been found empirically that in some embodiments of the present disclosure, in particular when the total content of alkali metal oxides (in mol %) does not exceed or only slightly exceeds the content of aluminum oxide (in mol %), the addition of zirconium oxide to the glass composition (sometimes even in very small amounts) may increase the liquidus temperature and / or cause precipitation of refractory minerals from the melt forming the glass. Therefore, in some embodiments of the present disclosure, the zirconium oxide content in the glass composition is limited, or the glass composition may be substantially free of ZrO2. In an embodiment, the amount of zirconium oxide (ZrO2) contained in the glass composition may be greater than or equal to 0.0 mol % to less than or equal to 5.0 mol %, and all ranges and sub-ranges between the above values. In some other embodiments, the glass composition may include ZrO2 in an amount of less than or equal to 5.0 mol%, less than or equal to 2.5 mol%, less than or equal to 1.5 mol%, less than or equal to 1.35 mol%, less than or equal to 1.2 mol%, or less than or equal to 1.0 mol%. In some more embodiments, the glass composition may include ZrO2 in an amount of greater than or equal to 0.0 mol% and less than or equal to 1.5 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.35 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.2 mol%, greater than or equal to 0.01 mol% and less than or equal to 1.01 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.0 mol%.
[0226] The glass composition of the present disclosure may contain barium oxide (BaO). Barium oxide may be added to the glass composition unintentionally as an impurity in other raw materials, or intentionally added to facilitate lower melting temperature or higher chemical durability. It has been found that adding BaO to the glass composition of the present disclosure may result in an increase in liquidus temperature, which may cause crystallization of the melt forming the glass when cooled and formed. In addition, barium as a large cation may reduce abnormal fracture behavior. Therefore, in the glass composition of the present disclosure, the content of BaO is limited, and the glass composition may preferably be free of BaO. In an embodiment, the amount of barium oxide (BaO) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 0.2 mol%, and all ranges and sub-ranges between the above values. In some other embodiments, the amount of BaO contained in the glass composition may be less than or equal to 0.2 mol% or less than or equal to 0.1 mol%. In some more embodiments, the amount of BaO contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 0.2 mol%, greater than or equal to 0.0 mol% and less than or equal to 0.1 mol%.
[0227] The glass composition of the present disclosure may include potassium oxide (K2O). Potassium oxide may be added to the glass composition unintentionally as an impurity in other raw materials, or may be added intentionally, for example, to protect the melt forming the glass from liquid-liquid phase separation. Adding K2O may improve the chemical durability of the glass and / or reduce the liquidus temperature. Without wishing to be bound by theory, it is believed that K2O transforms the structural units generated by boron oxide from trihedrons [BO3] to tetrahedrons [BO4], which may improve the balance between these structural units in the glass composition and thus improve abnormal fracture behavior. However, adding K2O to the glass composition of the present disclosure may reduce the Young's modulus of the glass, which may reduce the mechanical properties of the glass product. Moreover, adding a large amount of K2O may cause an undesirable increase in the coefficient of thermal expansion of the glass. Therefore, in some embodiments of the present disclosure, the K2O content in the glass composition is limited, or the glass composition may be substantially free of K2O. In embodiments, the glass composition may include potassium oxide (K2O) in an amount from greater than or equal to 0.0 mol% to less than or equal to 10.0 mol%, and all ranges and subranges therebetween. In an embodiment, the glass composition may include K2O in an amount of greater than or equal to 0.0 mol% and less than or equal to 3.0 mol%, greater than or equal to 0.3 mol% and less than or equal to 2.8 mol%, greater than or equal to 0.6 mol% and less than or equal to 2.5 mol%, greater than or equal to 0.92 mol% and less than or equal to 2.18 mol%, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 0.3 mol% and less than or equal to 2.2 mol%, greater than or equal to 0.6 mol% and less than or equal to 10.0 mol%, greater than or equal to 0.6 mol% and less than or equal to 2.2 mol%, greater than or equal to 0.8 mol% and less than or equal to 2.2 mol%, greater than or equal to 0.9 mol% and less than or equal to 2.2 mol%, greater than or equal to 5.0 mol% and less than or equal to 7.0 mol%.
[0228] The glass composition of the present disclosure may also include aluminum oxide (Al2O3). In the glass composition of the present disclosure, aluminum oxide plays the role of a network former together with B2O3 and SiO2. As a network former, aluminum oxide can increase the viscosity of the melt forming the glass and increase the liquidus viscosity, and provide better protection from crystallization. In addition, adding aluminum oxide (even a small amount) can protect the melt from phase separation. Then, aluminum oxide can improve the chemical durability of the glass. Therefore, the glass composition of the present disclosure contains a certain amount of aluminum oxide. However, when added in large quantities, aluminum oxide may cause refractory minerals to precipitate from the melt, which may cause crystal defects in glass products. In addition, at high levels of aluminum oxide, the viscosity may become too high, which may cause corrosion of refractory materials in the glass melting tank. Therefore, in some embodiments of the present disclosure, the aluminum oxide content is limited. In an embodiment, the amount of aluminum oxide (Al2O3) contained in the glass composition may be greater than or equal to 0.3 mol% to less than or equal to 5.3 mol%, and all ranges and sub-ranges between the above values. In some embodiments, the glass composition may include Al2O3 in an amount greater than or equal to 0.3 mol%, greater than or equal to 2.0 mol%, greater than or equal to 2.2 mol%, greater than or equal to 2.4 mol%, greater than or equal to 2.5 mol%, greater than or equal to 3.45 mol%, greater than or equal to 3.8 mol%, greater than or equal to 4.3 mol%, greater than or equal to 4.8 mol%, or greater than or equal to 5.0 mol%. In some other embodiments, the glass composition may include Al2O3 in an amount less than or equal to 5.3 mol%, less than or equal to 5.0 mol%, less than or equal to 4.8 mol%, less than or equal to 4.3 mol%, less than or equal to 4.0 mol%, less than or equal to 3.9 mol%, less than or equal to 3.8 mol%, less than or equal to 3.65 mol%, less than or equal to 3.53 mol%, or less than or equal to 2.5 mol%.In some more embodiments, the glass composition may include Al2O3 in an amount greater than or equal to 0.3 mol% and less than or equal to 5.3 mol%, greater than or equal to 2.0 mol% and less than or equal to 4.0 mol%, greater than or equal to 2.2 mol% and less than or equal to 3.9 mol%, greater than or equal to 2.4 mol% and less than or equal to 3.65 mol%, greater than or equal to 3.45 mol% and less than or equal to 3.53 mol%, greater than or equal to 0.3 mol% and less than or equal to 2.5 mol%, greater than or equal to 2.0 mol% and less than or equal to 5.3 mol%, greater than or equal to 2.0 mol% and less than or equal to 2.5 mol%, greater than or equal to 2.2 mol% and less than or equal to 2.5 mol%, greater than or equal to 2.4 mol% and less than or equal to 2.5 mol%, greater than or equal to 2.5 mol% and less than or equal to 5.3 mol%, greater than or equal to 3.8 mol% and less than or equal to 3.9 mol%.
[0229] The glass composition of the present disclosure may also include sodium oxide (Na2O). Sodium oxide may play the role of a modifier, converting the structural units formed by aluminum and boron cations into tetrahedral forms ([AlO4] and [BO4]), which may result in a better balance between structural units assumed to be rotatable and non-rotatable, which may result in improved abnormal fracture behavior of the glass. In addition, the addition of Na2O may improve the chemical durability of the glass, reduce the liquidus temperature and increase the liquidus viscosity, thereby better protecting the melt forming the glass from crystallization. However, when added in large amounts, Na2O may undesirably reduce the Young's modulus and thus deteriorate the mechanical properties of the glass article. In addition, a large amount of Na2O in the glass composition may result in an unacceptable increase in the coefficient of thermal expansion, and in some cases reduce the chemical durability of the glass. Therefore, in some embodiments of the present disclosure, the sodium oxide content in the glass composition is limited, or the glass composition may be substantially free of Na2O. In embodiments, the glass composition may include sodium oxide (Na2O) in an amount from greater than or equal to 0.0 mol% to less than or equal to 10.0 mol%, and all ranges and sub-ranges therebetween. In some embodiments, the glass composition may include Na2O in an amount greater than or equal to 0.0 mol%, greater than or equal to 2.0 mol%, greater than or equal to 2.5 mol%, greater than or equal to 2.9 mol%, greater than or equal to 3.4 mol%, greater than or equal to 4.55 mol%, greater than or equal to 5.0 mol%, greater than or equal to 7.0 mol%, greater than or equal to 8.0 mol%, or greater than or equal to 9.0 mol%. In some other embodiments, the glass composition may include Na2O in an amount less than or equal to 10.0 mol%, less than or equal to 9.7 mol%, less than or equal to 9.0 mol%, less than or equal to 8.0 mol%, less than or equal to 7.0 mol%, less than or equal to 6.0 mol%, less than or equal to 5.5 mol%, less than or equal to 5.45 mol%, less than or equal to 5.3 mol%, less than or equal to 5.2 mol%, or less than or equal to 5.0 mol%.In some more embodiments, the glass composition may include Na2O in an amount greater than or equal to 0.0 mol% and less than or equal to 5.2 mol%, greater than or equal to 2.0 mol% and less than or equal to 8.0 mol%, greater than or equal to 2.0 mol% and less than or equal to 6.0 mol%, greater than or equal to 2.5 mol% and less than or equal to 5.3 mol%, greater than or equal to 2.9 mol% and less than or equal to 5.5 mol%, greater than or equal to 3.4 mol% and less than or equal to 6.0 mol%, greater than or equal to 4.55 mol% and less than or equal to 5.45 mol%, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 2.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 2.5 mol% and less than or equal to 5.0 mol%, greater than or equal to 3.4 mol% and less than or equal to 5.0 mol%, greater than or equal to 4.55 mol% and less than or equal to 5.0 mol%.
[0230] The glass composition of the present disclosure may contain fluorine (F). A small amount of fluorine may be added to the glass composition of the present disclosure as a fining agent component or as a component to lower the liquidus temperature. However, the addition of fluorine to the glass composition may cause environmental concerns. For this reason, in some embodiments of the present disclosure, the fluorine content is limited, and the glass composition may preferably be fluorine-free.
[0231] In an embodiment, the glass composition of the present disclosure may include a total amount of iron, chromium, molybdenum, vanadium, copper, and cobalt (Fe+Cr+Mo+V+Cu+Co) of less than or equal to 1.0 mol% or less than or equal to 0.5 mol%. In an embodiment, Fe+Cr+Mo+V+Cu+Co is greater than or equal to 0.0 mol% and less than or equal to 1.0 mol% or greater than or equal to 0.0 mol% and less than or equal to 0.5 mol%.
[0232] In an embodiment, the glass composition of the present disclosure may contain a total amount of iron (II) and iron (III) oxides (FeO + Fe2O3) of less than or equal to 0.5 mol% or less than or equal to 0.25 mol%. In an embodiment, FeO + Fe2O3 is greater than or equal to 0 mol% and less than or equal to 0.5 mol% or greater than or equal to 0.0 mol% and less than or equal to 0.25 mol%.
[0233] In an embodiment, the glass composition of the present disclosure may have a total amount of lanthanum oxide and yttrium (III) oxide La2O3+Y2O3 of less than or equal to 1.0 mol% or less than or equal to 0.5 mol%. In an embodiment, La2O3+Y2O3 is greater than or equal to 0.0 mol% and less than or equal to 1.0 mol% or greater than or equal to 0.0 mol% and less than or equal to 0.5 mol%.
[0234] In an embodiment, the glass composition of the present disclosure may have a total amount of sodium oxide and potassium oxide (Na2O+KO) greater than or equal to 0.0 mol%, greater than or equal to 5.0 mol%, or greater than or equal to 6.11 mol%. In an embodiment, Na2O+KO is less than or equal to 6.84 mol% or less than or equal to 5.0 mol%. In an embodiment, Na2O+KO is greater than or equal to 0.0 mol% and less than or equal to 6.84 mol% or greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%.
[0235] In embodiments, the glass compositions of the present disclosure may have a total amount of sodium oxide and aluminum oxide (Na2O+Al2O3) of greater than or equal to 0.0 mol%, greater than or equal to 5.0 mol%, or greater than or equal to 7.7 mol%. In embodiments, Na2O+Al2O3 is less than or equal to 9.7 mol%, less than or equal to 8.9 mol%, or less than or equal to 5.0 mol%. In embodiments, Na2O+Al2O3 is greater than or equal to 0.0 mol% and less than or equal to 9.7 mol%, greater than or equal to 0.0 mol% and less than or equal to 8.9 mol%, or greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 9.7 mol%, or greater than or equal to 5.0 mol% and less than or equal to 8.9 mol%, greater than or equal to 7.7 mol% and less than or equal to 9.7 mol%.
[0236] In an embodiment, the glass composition of the present disclosure may have a total amount of sodium oxide, potassium oxide, magnesium oxide, calcium oxide, zinc oxide, aluminum oxide, boron oxide, and silicon dioxide (Na2O+K2O+MgO+CaO+ZnO+Al2O3+B2O3+SiO2) greater than or equal to 95.0 mol%.
[0237] In embodiments, the glass compositions of the present disclosure may have a (Na2O+KO+MgO+CaO+SrO+BaO+ZnO) / (RO+RO) ratio greater than or equal to 0.000 or greater than or equal to 0.95. Oxides of sodium and potassium, as well as alkaline earth metal oxides and zinc oxide are the most common options for modifiers (RO and RO) because they may not reduce the light transmittance of the resulting glass article and dissolve well in the glass melt of the present disclosure. Other monovalent and divalent metal oxides (e.g., MgO, NiO, CuO, Ag2O, PbO, etc.) may be less soluble, or provide undesirable coloration, or cause ecological concerns, or be more expensive.
[0238] In an embodiment, the glass composition of the present disclosure may have a ratio of Na2O / Al2O3. In the case of adding Na2O to the glass composition, it may be desirable to connect it to the structural units formed by different network formers. When this occurs, the mobility of the sodium ions may be reduced, which may result in a certain improvement in the chemical durability of the glass. Without wishing to be bound by theory, it is believed that such connection may occur when the Na2O content in the glass composition is greater than or equal to the Al2O3 content. Therefore, in some embodiments of the present disclosure, it may be desirable that the ratio Na2O / Al2O3 (in mol %) is greater than or equal to about 1.0. On the other hand, when the ratio Na2O / Al2O3 becomes too high, the abnormal fracture behavior described herein may be suppressed. Therefore, in an embodiment, Na2O / Al2O3 is greater than or equal to 1.0 mol %, greater than or equal to 1.01 mol %, greater than or equal to 1.1 mol %, or greater than or equal to 1.5 mol %. In an embodiment, Na2O / Al2O3 is less than or equal to 1.67 mol%, less than or equal to 1.6 mol%, less than or equal to 1.5 mol%, or less than or equal to 1.35 mol%. In an embodiment, Na2O / Al2O3 is: greater than or equal to 1.0 mol% and less than or equal to 1.35 mol%, greater than or equal to 1.01 mol% and less than or equal to 1.67 mol%, greater than or equal to 1.0 mol% and less than or equal to 1.67 mol%, greater than or equal to 1.0 mol% and less than or equal to 1.6 mol%, greater than or equal to 1.0 mol% and less than or equal to 1.5 mol%, greater than or equal to 1.01 mol% and less than or equal to 1.6 mol%, greater than or equal to 1.01 mol% and less than or equal to 1.5 mol%, or greater than or equal to 1.01 mol% and less than or equal to 1.35 mol%, greater than or equal to 1.1 mol% and less than or equal to 1.67 mol%, greater than or equal to 1.1 mol% and less than or equal to 1.6 mol%, greater than or equal to 1.1 mol% and less than or equal to 1.5 mol%, or greater than or equal to 1.1 mol% and less than or equal to 1.35 mol%.
[0239] In embodiments, the glass compositions of the present disclosure may include the parameter B2O3+3.5*Al2O3 within certain numerical ranges. It has been found empirically that the abnormal fracture behavior described herein is preferably observed when the sum (B2O3+3.5*Al2O3) is approximately 25 mol%. Thus, in embodiments, B2O3+3.5*Al2O3 is greater than or equal to 20.3 mol%, greater than or equal to 24.2 mol%, or greater than or equal to 25 mol%. In embodiments, B2O3+3.5*Al2O3 is less than or equal to 27.5 mol%, less than or equal to 25.9 mol%, or less than or equal to 25 mol%. In an embodiment, B2O3+3.5*Al2O3 is: greater than or equal to 20.3 mol% and less than or equal to 27.5 mol%, greater than or equal to 20.3 mol% and less than or equal to 25.9 mol%, or greater than or equal to 20.3 mol% and less than or equal to 25 mol%, greater than or equal to 24.2 mol% and less than or equal to 27.5 mol%, greater than or equal to 24.2 mol% and less than or equal to 25.9 mol%, or greater than or equal to 24.2 mol% and less than or equal to 25 mol%, greater than or equal to 25 mol% and less than or equal to 27.5 mol%, or greater than or equal to 25 mol% and less than or equal to 25.9 mol%.
[0240] In some embodiments, the glass compositions described herein can exhibit a liquidus viscosity decimal logarithm (Log(eta)) of greater than or equal to 5.5 to less than or equal to 8.0. liq P)), and all ranges and subranges between the above values. In an embodiment, Log(eta liq P) is: greater than or equal to 5.5, greater than or equal to 5.9, greater than or equal to 6.0, greater than or equal to 6.5, greater than or equal to 7.4, greater than or equal to 7.5, greater than or equal to 7.6, or greater than or equal to 7.8. In an embodiment, Log(eta liq P) is: less than or equal to 8.0, less than or equal to 7.8, less than or equal to 7.7, less than or equal to 7.6, less than or equal to 7.5, less than or equal to 7.4, less than or equal to 6.5, or less than or equal to 6.0. In an embodiment, Log(eta liq P) is: greater than or equal to 5.5 and less than or equal to 8.0, greater than or equal to 5.9 and less than or equal to 7.7, greater than or equal to 5.5 and less than or equal to 6.0, greater than or equal to 5.9 and less than or equal to 6.0, greater than or equal to 6.0 and less than or equal to 8.0, greater than or equal to 6.0 and less than or equal to 6.5, greater than or equal to 7.4 and less than or equal to 8.0, greater than or equal to 7.4 and less than or equal to 7.5.
[0241] In an embodiment, a glass composition according to the present disclosure may exhibit a modifier excess parameter M calculated according to the following relationship: exc :
[0242] M exc =max(0,(Alk2O+RO)-(Al2O3+B2O3)), (Equation 2)
[0243] Wherein, Alk2O is the sum of alkali metal oxides, RO is the sum of divalent metal oxides, and the chemical formula represents the amount of the corresponding component in the glass composition. exc represents the excess of modifiers R2O and RO compared to the network formers Al2O3 and B2O3. In the case where the total content of Al2O3 + B2O3 exceeds the total content of R2O + RO, the modifier excess parameter is defined to be equal to zero. Without wishing to be bound by theory, it is believed that M exc The value of is related to the amount of non-bridging oxygen atoms in the structural network of the glass.
[0244] In embodiments, glass compositions according to the present disclosure may exhibit a total polyhedral parameter P calculated according to the following relationship: 总 :
[0245] P 总 =SiO2+2*Al2O3+2*B2O3, (Equation 3)
[0246] Wherein, the chemical formula represents the amount of the corresponding component in the glass composition. 总 Can represent the cation Si4 that forms the network + 、Al3 + and B3 + The total number of gram atoms per 100 moles of oxides present in the glass composition.
[0247] In embodiments, a glass composition according to the present disclosure may exhibit a boron excess parameter B calculated according to the following relationship: exc :
[0248] B exc =max(0,B2O3-max(0,R2O+RO-Al2O3)), (Equation 4)
[0249] Wherein, R2O is the sum of monovalent metal oxides, RO is the sum of divalent metal oxides, and the chemical formula represents the amount of the corresponding component in the glass composition. excrepresents the excess of boron oxide (in mol %) compared to the content of modifiers R2O and RO (in mol %) after deducting the content of alumina (in mol %) in the glass composition. In cases where the alumina content is greater than or equal to the total content of R2O and RO, the boron excess parameter is assumed to be equal to the boron oxide content in the glass composition.
[0250] In an embodiment, a glass composition according to the present disclosure may exhibit a silica excess parameter S calculated according to the following relationship: exc :
[0251] Si exc =SiO2-6*min(Alk2O,Al2O3)-2*min(Alk2O+RO-Al2O3,B2O3), (Equation 5)
[0252] Wherein, Alk2O is the sum of alkali metal oxides, RO is the sum of divalent metal oxides, and the chemical formula represents the amount of the corresponding components in the glass composition. exc Approximately the amount of silica that is assumed to be unattached to the structural polyhedra formed by the aluminum and boron cations.
[0253] In an embodiment, the parameter P of the glass composition described herein is 总 、M exc , B exc and S exc The following relationship can be satisfied:
[0254] (abs(2*M exc +2*min(B2O3,R2O+RO-Al2O3)+0.65*P 总 -80))–(3.4-0.5*(abs(Si exc -max(24+2*B exc ,44))))≤0.000
[0255] In an embodiment, the parameter P of the glass composition described herein is 总 、M exc , B exc and S exc The following relationship can be satisfied:
[0256] (abs(2*M exc +2*min(B2O3,R2O+RO-Al2O3)+0.65*P 总 -80))–(2.8-0.5*(abs(Si exc -max(24+2*B exc ,44))))≤0.000.
[0257] In some embodiments, glasses comprising the compositions described herein may have a value 1-2*(Alk2O+RO) / P greater than or equal to 0.83. 总 .
[0258] The glass comprising the composition described herein may also include a non-rotatable polyhedron parameter P calculated according to the following nr :
[0259] P nr =2*max(0,(Alk2O+RO)-(Al2O3+B2O3))+2*min(B2O3,R2O+RO-Al2O3), (Equation 6)
[0260] Wherein, Alk2O is the sum of alkali metal oxides, RO is the sum of divalent metal oxides, R2O is the sum of monovalent metal oxides, and the chemical formula represents the amount of the corresponding component in the glass composition. Without wishing to be bound by theory, it is believed that P nr represents the network-forming cation Si4 that cannot rotate as described above + 、Al3 + and B3 + The approximate amount is calculated as gram atoms of non-rotatable network-forming cations per 100 total moles of oxides present in the glass composition.
[0261] The glasses comprising the compositions described herein may also include a network rotatability ratio R nr , which is the value calculated according to the following equation:
[0262] R nr =1-2*(Alk2O+RO) / (SiO2+2*Al2O3+2*B2O3), (Equation 7)
[0263] Wherein, Alk2O is the sum of alkali metal oxides, RO is the sum of divalent metal oxides, and the chemical formula represents the amount of the corresponding components in the glass composition. Applicants believe that R nr The fracture behavior of the borosilicate glass compositions disclosed herein can be related to and characterized in terms of the "rotatability" of the corresponding compositions. For a composition of the form xSiO2·yAl2O3·zB2O3·uR2O·vRO, where x, y, z, u, v represent the mole % or mole fraction of each type of oxide. If (u+v)≥y, then the applicant believes that the fracture behavior is related to the network rotatability ratio R determined by Equation 7 nr Related. For R nrFor the case of about 0.80 to about 0.93, applicants have found that the Vickers indenter test produces radial and transverse cracks that are contained within small (<1 mm diameter) crack loops. As a result, glass sheets within this range do not crack to failure in the Vickers indenter test, but instead only form small circular cracks that contain other cracks and prevent them from propagating.
[0264] In an embodiment, a glass composition according to the present disclosure may include a network balance standard C calculated according to nb :
[0265] C nb =abs(SiO2-6*min(Alk2O,Al2O3)-2*min(Alk2O+RO-Al2O3,B2O3)-max(24+2*max(0,B2O3-max(0,R2O+RO-Al2O3)),44)), (Equation 8)
[0266] In the formula, Alk2O is the sum of alkali metal oxides, RO is the sum of divalent metal oxides, R2O is the sum of monovalent metal oxides, and the chemical formula represents the amount of the corresponding component in the glass composition. nb Represents the parameter Si described in this article exc With B exc When the Si composition of the example described in this article exc Parameter as B exc When plotted as a function of parameter values, the instances are grouped near the lines y = 24–x and y = 44-3*x, where y corresponds to the parameter Si exc And x corresponds to parameter B exc The examples described herein are located near the highest values calculated by these equations, which can be expressed as follows:
[0267] Si exc =max(24-B exc ,44-4*B exc ), (Equation 9)
[0268] I don't want to be limited by theory, I believe Si exc The expression (max(24-B) specified in the right side of equation 9 is exc ,44-4*B exc The difference between the Si and B connections in the structural network can characterize the balance between the silicon and boron connectivity. exc and B exc After the expression of) finally get C nb In other words, the network balance criterion can be expressed as Si exc and Bexc The terms are expressed as follows:
[0269] C nb =abs(Si exc -max(24-B exc ,44-4*B exc )). (Equation 10)
[0270] The example compositions described herein that exhibit anomalous and intermediate fracture behavior are characterized by having a small C nb Numerical values, for example: less than or equal to 5.0, or less than or equal to 4.5, or less than or equal to 4.0, or less than or equal to 3.5, or less than or equal to 3.0, or less than or equal to 2.5, or even less than or equal to 2.0.
[0271] The term "fracture category" refers to the type of fracture behavior observed when performing a Vickers indentation test, described as three categories: "normal", "abnormal" and "intermediate". The Vickers indenter test can be used to characterize the fracture behavior of glass, as discussed in Gross et al., Crack-resistant glass with high shear band density, Journal of Non-Crystalline Solids, 94 (2018) 13-20, and Gross, Deformation and cracking behavior of glasses indented with diamond tips of various sharpness, Journal of Non-Crystalline Solids, 358 (2012) 3445-3452, both of which are incorporated herein by reference. In some embodiments, when the glass of the borosilicate glass composition having the first glass ply is formed into at least 10 1 mm thick and having a major surface of at least 2x2 cm 2Polished flat samples (e.g., 100 samples) of area (e.g., 2 cm by 2 cm square) and tested with a square-based 136° four-sided pyramid Vickers indenter directed orthogonally into the center of the major surface at 25°C, 50% relative humidity and quasi-static displacement of the indenter at a rate of 60 μm per second up to a maximum indentation load of 3 kg force for 10 seconds (unless sample fracture failure occurs first), most of the time (at least 51 out of 100 times; at least 6 out of 10 times), all cracks extending radially and / or laterally through the sample from below the indenter tip (i.e., where the indenter tip contacts the glass) are interrupted by self-terminating crack loops (e.g., annular cracks), so that sample cracking from the Vickers indenter is confined to cracking in the loop. In this case, the fracture category is identified as "intermediate". Basically, the indenter crushes and cracks the glass below the indenter. However, a crack loop is formed and cracks originating from the indenter contact are prevented from propagating beyond the crack loop. Conversely, otherwise, in other glasses, transverse or radial cracks may form before and / or through such crack loops (e.g., abnormal cracking), or may not form crack loops (e.g., normal cracking), and in either case, the transverse or radial cracks are not contained by the crack loops and may propagate through the entire glass article, resulting in fracture through the article and its failure. This type of fracture behavior is identified as "normal".
[0272] In an embodiment, a glass composition according to the present disclosure may include a rotatability balance standard C according to a value calculated as follows: rb :
[0273] C rb =abs(2*max(0,(Alk2O+RO)-(Al2O3+B2O3))+2*min(B2O3,R2O+RO-Al2O3)+0.65*(SiO2+2*Al2O3+2*B2O3)-80), (Equation 11)
[0274] In the formula, Alk2O is the sum of alkali metal oxides, RO is the sum of divalent metal oxides, R2O is the sum of monovalent metal oxides, and the chemical formula represents the amount of the corresponding component in the glass composition. rb Represents the quantity P described in this article 总 With P nr When the embodiment P described in this article nr Parameter as P 总 When the function of the parameter is plotted, the P of the embodiment of the present disclosure nr The value falls near the line y=80-0.65*x, where y corresponds to the parameter P nr And x corresponds to the parameter P总 , its mathematical expression can be as follows:
[0275] P nr =80-0.65*P 总 , (Equation 12)
[0276] Where P 总 and P nr refers to the total polyhedral parameters and the non-rotatable polyhedral parameters as described herein. Without wishing to be bound by theory, it is believed that P nr The expression (80-0.65*P) specified in the right side of equation 12 总 ) can characterize the balance between the rotatable and non-rotatable structural polyhedrons. The absolute value of the difference (when substituting P nr and P 总 After the expression of) finally get C rb expression.
[0277] In other words, the network balancing standard can be expressed as Si exc and B exc The terms are expressed as follows:
[0278] C rb =abs(P nr -(80-0.65*P 总 ). (Equation 13)
[0279] Room temperature density (hereinafter referred to as "d RT ”) is a glass property that can be predicted from the glass composition. Linear regression analysis was performed on the examples of the present disclosure and certain prior art compositions to generate equations that can be used to predict the composition dependence of density for various glass compositions.
[0280] For a selection of existing glass compositions, the SciGlass information system was searched using the criteria set forth in Table 600 below.
[0281] Table 600
[0282]
[0283] About 100 glass compositions were randomly selected from the search results and from the exemplary glasses of the embodiments presented herein. The equation was determined using linear regression analysis on the data set specified above, excluding insignificant variables and outliers. The following table 700 presents the resulting equation.
[0284] Table 700
[0285] nature abbreviation unit Prediction parameters Regression equation Composition Unit Standard Deviation Room temperature density <![CDATA[d RT ]]> <![CDATA[g / cm 3 ]]> <![CDATA[P d ]]> Equation 14 Mole % 0.024
[0286] Another set of compositions meeting the same criteria in Table 600 was used as a validation set to evaluate the ability of Equation 14 herein to interpolate within predetermined composition limits, corresponding to the standard deviations specified in Table 700. An external data set of prior art glass compositions (also randomly selected from the SciGlass Information System database) was used to evaluate the ability to predict properties that fall outside the specified composition limits with reasonable accuracy. Multiple iterations of this process were performed to determine the optimal variables for each property, corresponding to the above regression equations specified in Table 700.
[0287] The data for the composition used in the linear regression modeling (including training data sets, validation data sets, and external data sets) were obtained from the publicly available SciGlass information system database. The following equation 14 was obtained from the linear regression analysis and used to predict the density of the glass:
[0288] P d =2.487-0.0068998*B2O3+0.041371*BaO+0.13897*Bi2O3+0.011637*CaO+0.055366*Cs2O+0.025420*Fe2O 3+0.10294*Gd2O3+0.0051134*K2O+0.079903*La2O3+0.0041594*Li2O+0.0084582*MgO+0.019720*MnO+0.0 064419*Na2O+0.018282*NiO+0.065781*PbO-0.002953*SiO2+0.027682*SrO+0.0055367*TiO2+0.0068497 *V2O5+0.048699*Y2O3+0.021527*ZnO+0.026527*ZrO2+0.011033*(min(B2O3,max(0,Alk2O+RO-Al2O3))).
[0289] (Equation 14)
[0290] In Equation 14, the density parameter P d is the room temperature density [g / cm 3] The parameter for prediction is calculated from the components (expressed in mole %) of the glass composition. In equation 14, each component of the glass composition is listed in the form of its chemical formula, where the chemical formula refers to the concentration of the component (expressed in mole %). For example, for the purpose of equation 14, B2O3 refers to the concentration (expressed in mole %) of B2O3 in the glass composition. It is to be understood that not all components listed in equation 14 are necessarily present in a specific glass composition, and that equation 14 is equally applicable to glass compositions containing less than all components listed in the equation. It is also to be understood that equation 14 is also applicable to glass compositions within the scope of the present disclosure and claims containing components other than those listed in the equation. If a component listed in equation 14 is not present in a particular glass composition, the concentration of the component in the glass composition is 0 mole % and the contribution of the component to the value calculated from the equation is zero. Equation 14 is used to generate density prediction values for glasses present in the embodiments described herein and in the prior art. As the density d measured at room temperature RT The predicted values are plotted as a function of . It is found that Equation 14 accurately predicts the actual measured density with an error of + / -.024 g / cm 3 .
[0291] Applicants have discovered that for certain glass compositions according to the embodiments contained herein, the density parameter P d (which represents the density predictions from the constituent components of each composition) satisfies the relationship as a function of the ratio Na2O / Al2O3. The first set of embodiments described herein were selected to satisfy the following criteria listed in the following table 800. In the table 800, "no limitation" means that when the composition is selected, it is not considered as a limitation.
[0292] Table 800
[0293]
[0294]
[0295] For the first set of examples, the density parameter P is plotted as a function of the Na2O / Al2O3 value for each composition. d Value. It is found that the first group of examples satisfies the following relationship:
[0296] P d -(2.58-0.2*Na2O / Al2O3)<0.0 (Equation 15).
[0297] It is found that the subgroups of the first set of examples satisfy the following relationship:
[0298] P d-(2.54-0.2*Na2O / Al2O3)<0.0 (Equation 16).
[0299] Certain prior art glass compositions do not satisfy the relationship defined by Equation 15 (and therefore do not satisfy the relationship defined by Equation 16). That is, the glass compositions according to the embodiments described herein exhibit lower density parameter values (and lower measured d RT As described herein, such lower densities can facilitate glasses according to the present disclosure exhibiting unique fracture behaviors described herein.
[0300] The second set of embodiments described herein were selected to meet the following criteria listed in Table 900 below.
[0301] Table 900
[0302] composition Amount (mol%) <![CDATA[SiO2]]> 60.0 to 96.0 mol% <![CDATA[B2O3]]> 1.0 to 25.0 mol% <![CDATA[Al2O3]]> ≥0.3 mol% <![CDATA[(Sum of (Na2O + Al2O3))]]> ≥9.7 mol%
[0303] In an implementation manner, the second group of embodiments may also satisfy each of the following conditions: 1.01≤Na2O / Al2O3[mol%]≤1.67, B2O3+3.5*Al2O3[mol%]≤27.5, C rb -(3.4-0.5*C nb )<0.000, where C rb is the rotatability balance criterion defined in this paper, and C nb is the network balancing standard defined in this document, or C rb -(2.8-0.5*C nb )<0.000, and 1-2*(Alk2O+RO) / P 总 >0.83, where P 总 is the total polyhedral parameter. It was found that some existing compositions cannot meet the above conditions.
[0304] The third set of embodiments described herein were selected to meet the following criteria listed in Table 1000 below.
[0305] Table 1000
[0306] composition Amount (mol%) <![CDATA[SiO2]]> 60.0 to 77.5 mol% <![CDATA[B2O3]]> 5.0 to 17.0 mol% <![CDATA[Na2O]]> 2.5 to 5.3 mol% <![CDATA[Al2O3]]> 0.3 to 5.3 mol%
[0307] It was found that the third group of examples satisfied each of the following conditions: 20.3≤B2O3+3.5*Al2O3[mol%]≤27.5, d RT -(2.58-0.2*(Na2O / Al2O3))<0.00,d RT is the room temperature density, or in some cases, d RT-(2.54-0.2*(Na2O / Al2O3))<0.000. It was found that some existing compositions could not meet the above conditions.
[0308] The fourth set of embodiments described herein were selected to meet the following criteria listed in Table 1100 below.
[0309] Table 1100
[0310]
[0311]
[0312] For each example in the fourth group, calculate C rb Parameters and as C nb For each example in the fourth group, C rb and C nb The parameters satisfy the following relationship:
[0313] C rb -(3.4-0.5*C nb )<0.00. (Equation 17)
[0314] It was discovered that glasses according to the present disclosure differ from certain prior art compositions in that Eq. 17 is satisfied.
[0315] For the subset of embodiments in the fourth group, it was found that C rb and C nb The values of the parameters also satisfy the following relationship:
[0316] C rb -(2.8-0.5*C nb )<0.00. (Equation 16)
[0317] Such glasses are found to further differ from certain prior art compositions in that Equation 16 is satisfied.
[0318] The embodiments of the present disclosure may be further understood in view of the following aspects.
[0319] A first aspect of the present disclosure includes a borosilicate glass composition comprising: at least 74 mol % SiO2; at least 10 mol % B2O3; and an amount of Al2O3 such that the sum of SiO2, B2O3, and Al2O3 is at least 90 mol %; wherein the borosilicate glass composition comprises a liquidus viscosity greater than 500 kP; and wherein, when the viscosity of the borosilicate glass composition is 200P, the temperature contained in the borosilicate glass composition is 1725°C or less.
[0320] A second aspect of the present disclosure includes the borosilicate glass according to the first aspect, further comprising about 2 mol % to about 8 mol % Na2O.
[0321] A third aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 2, further comprising about 0.8 mol % to about 4 mol % K2O.
[0322] A fourth aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 3, wherein the total amount of Na2O and K2O is at least 4 mol%.
[0323] A fifth aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 4, wherein the total amount of MgO and CaO is at most 5 mol%.
[0324] A sixth aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 5, further comprising P2O5, wherein the P2O5 is present in an amount up to 4 mol%.
[0325] A seventh aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 6, further comprising about 0.05 mol % to about 0.25 mol % SnO2.
[0326] An eighth aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 7, further comprising 0.05 mol % to 0.50 mol % of an iron compound.
[0327] A 9th aspect of the present disclosure includes the borosilicate glass according to any one of the 1st to 8th aspects, wherein the total solar transmittance measured according to ISO 13837A is 90% or less.
[0328] A tenth aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 9, wherein the visible light transmittance measured according to ISO 13837A is at least 73%.
[0329] An 11th aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 10, comprising a thermal expansion coefficient of 5.6 ppm / °C or less measured over a temperature range of 0°C to 300°C.
[0330] A twelfth aspect of the present disclosure includes a borosilicate glass according to any one of aspects 1 to 11, comprising less than 2.4 g / cm 3 density.
[0331] A 13th aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 12, comprising a strain point of about 480°C to about 560°C.
[0332] A 14th aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 13, comprising an annealing point of about 520°C to about 590°C.
[0333] A 15th aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 14, wherein the glass ply includes the borosilicate glass composition according to any preceding claim.
[0334] A 16th aspect of the present disclosure includes a borosilicate glass according to any one of aspects 1 to 15, wherein, when subjected to a quasi-static 2 kgf indentation load of a Vickers tip, the glass layer exhibits an annular crack and a plurality of radial cracks, and wherein each of the plurality of radial cracks is bounded by an annular crack.
[0335] A 17th aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 16, wherein the glass ply is formed via fusion drawing, and wherein the thickness between the first major surface and the second major surface is greater than 2 mm.
[0336] An eighteenth aspect of the present disclosure includes the borosilicate glass according to any one of aspects 1 to 17, wherein the thickness is at least 3 mm.
[0337] A 19th aspect of the present disclosure includes a laminate comprising: a first glass ply according to any one of aspects 1 to 18, a second glass ply; and an interlayer bonding the first glass ply to the second glass ply.
[0338] A 20th aspect of the present disclosure includes the laminate according to the 19th aspect, wherein the first glass ply is thicker than the second glass ply.
[0339] A 21st aspect of the present disclosure includes the laminate according to any one of aspects 19 to 20, wherein the second glass ply is strengthened.
[0340] A 22nd aspect of the present disclosure includes a laminate according to any one of aspects 19 to 21, wherein the first glass ply and the second glass ply are formed in a pair, wherein the first glass ply includes a first depth of curvature of at least 2 mm, wherein the second glass ply includes a second depth of curvature of at least 2 mm, and wherein the first depth of curvature differs from the second depth of curvature within 10%.
[0341] A 23rd aspect of the present disclosure includes a laminate according to any one of aspects 19 to 22, wherein the first glass ply is sag and includes a depth of curvature of at least 2 mm, and wherein the second glass ply is cold formed to conform to the first glass ply.
[0342] A 24th aspect of the present disclosure includes an automotive glazing comprising the laminate according to any one of aspects 19 to 24.
[0343] Aspect 25 of the present disclosure includes a vehicle comprising: a body defining an interior of the vehicle and at least one opening; an automotive glass window according to claim 24 arranged in the at least one opening; wherein the second glass layer is arranged to face the interior of the vehicle and the first glass layer faces the exterior of the vehicle.
[0344] A 26th aspect of the present disclosure includes a vehicle according to aspect 25, wherein the vehicle glass window is at least one of the following: a side light, a windshield, a rear window, a window or a sunroof.
[0345] A 27th aspect of the present disclosure includes a method for forming a glass layer comprising a first major surface and a second major surface, the method comprising: allowing at least two streams of a borosilicate glass composition to overflow in a groove of an overflow trough, the borosilicate glass composition comprising a liquidus viscosity greater than 500 kP and a temperature of 1725°C or less when the viscosity of the borosilicate glass composition is 200P, wherein the borosilicate glass composition comprises: at least 74 mol % SiO2 and at least 10 mol % B2O3, and wherein the total amount of SiO2, B2O3 and Al2O3 is at least 90 mol %; allowing the at least two streams of the borosilicate glass composition to fuse at the root of the overflow trough to form a glass layer having a thickness of at least 2 mm between the first major surface and the second major surface.
[0346] A 28th aspect of the present disclosure includes the method according to aspect 27, wherein the glass ply includes a coefficient of thermal expansion of 5.6 ppm / °C or less measured over a temperature range of 0°C to 300°C.
[0347] A 29th aspect of the present disclosure includes a method according to any one of aspects 27 to 28, wherein the glass ply comprises less than 2.4 g / cm 3 density.
[0348] A 30th aspect of the present disclosure includes a method according to any one of aspects 27 to 29, wherein the borosilicate glass composition further comprises about 2 mol % to about 8 mol % Na2O.
[0349] A 31st aspect of the present disclosure includes a method according to any one of aspects 27 to 30, wherein the borosilicate glass composition further comprises about 0.8 mol % to about 4 mol % K2O.
[0350] A 32nd aspect of the present disclosure includes a method according to any one of aspects 27 to 30, wherein the total amount of Na2O and K2O is at least 4 mol%.
[0351] A 33rd aspect of the present disclosure includes a method according to any one of aspects 27 to 32, wherein the borosilicate glass composition further comprises at least one of MgO or CaO, wherein the total amount of MgO and CaO is up to 5 mol%.
[0352] A 34th aspect of the present disclosure includes a method according to any one of aspects 27 to 33, wherein the borosilicate glass composition further comprises about 0.05 mol% to about 0.25 mol% SnO2.
[0353] A 35th aspect of the present disclosure includes a method according to any one of aspects 27 to 34, wherein the borosilicate glass composition further comprises 0.05 mol% to 0.50 mol% of an iron compound.
[0354] A 36th aspect of the present disclosure includes a method according to any one of aspects 27 to 35, further comprising P2O5, wherein the P2O5 is present in an amount up to 4 mol%.
[0355] A 37th aspect of the present disclosure includes a glass layer comprising: a first major surface and a second major surface opposite the first major surface, wherein the glass layer comprises a borosilicate glass composition; and wherein, when subjected to a quasi-static 2kgf indentation load of a Vickers tip, the glass layer exhibits an annular crack and a plurality of radial cracks, and wherein each of the plurality of radial cracks is confined by an annular crack.
[0356] A 38th aspect of the present disclosure includes a glass ply according to aspect 37, wherein the borosilicate glass composition comprises: at least 74 mol % SiO2; at least 10 mol % B2O3; and an amount of Al2O3 such that the sum of SiO2, B2O3, and Al2O3 is at least 90 mol %.
[0357] A 39th aspect of the present disclosure includes the glass ply according to the 38th aspect, wherein the borosilicate glass composition includes a liquidus viscosity greater than 500 kP.
[0358] A 40th aspect of the present disclosure includes a glass ply according to any one of aspects 38 to 39, wherein the borosilicate glass composition includes a temperature of 1725° C. or less when the viscosity of the borosilicate glass composition is 200P.
[0359] A 41st aspect of the present disclosure includes a glass ply according to any one of aspects 38 to 41, wherein the borosilicate glass composition comprises about 2 mol % to about 8 mol % Na2O.
[0360] A 42nd aspect of the present disclosure includes a glass ply according to any one of aspects 38 to 40, wherein the borosilicate glass composition comprises about 0.8 mol % to about 4 mol % K2O.
[0361] A 43rd aspect of the present disclosure includes a glass ply according to any one of aspects 38 to 42, wherein the borosilicate glass composition comprises a total amount of Na2O and K2O of at least 4 mol%.
[0362] A 44th aspect of the present disclosure includes a glass ply according to any one of aspects 38 to 43, wherein the borosilicate glass composition comprises at least one of MgO or CaO, wherein the total amount of MgO and CaO is up to 5 mol%.
[0363] A 45th aspect of the present disclosure includes a glass ply according to any one of aspects 38 to 44, wherein the borosilicate glass composition comprises P2O5 in an amount up to 4 mol%.
[0364] A 46th aspect of the present disclosure includes a glass ply according to any one of aspects 38 to 45, wherein the borosilicate glass composition comprises about 0.05 mol % to about 0.25 mol % SnO2.
[0365] A 47th aspect of the present disclosure includes the glass ply according to any one of aspects 38 to 46, wherein the borosilicate glass composition comprises 0.05 mol% to 0.50 mol% of an iron compound.
[0366] A 48th aspect of the present disclosure includes the glass ply according to any one of aspects 38 to 47, wherein the total solar transmittance through the glass ply measured according to ISO 13837A is 90% or less.
[0367] A 49th aspect of the present disclosure includes the glass ply according to any one of aspects 38 to 48, wherein the visible light transmission through the glass ply is at least 73% as measured according to ISO 13837A.
[0368] A 50th aspect of the present disclosure includes a glass ply according to any one of aspects 38 to 49, wherein the first major surface exhibits an optical distortion of at most 200 millidiopters as measured using an optical distortion detector using transmission optics in accordance with ASTM 1561.
[0369] Aspect 51 of the present disclosure includes a glass laminate comprising: a first glass ply comprising a first major surface and a second major surface opposite the first major surface, wherein the first glass ply comprises a borosilicate glass composition; a second glass ply comprising a third major surface and a fourth major surface opposite the third major surface; and an interlayer bonding the second major surface of the first glass ply to the third major surface of the second glass ply; wherein the borosilicate glass composition comprises: at least 74 mol % SiO2; at least 10 mol % B2O3; and an amount of Al2O3 such that the sum of SiO2, B2O3, and Al2O3 is at least 90 mol %.
[0370] A 52nd aspect of the present disclosure includes the glass laminate according to the 52nd aspect, wherein the first glass ply is thicker than the second glass ply.
[0371] A 53rd aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 52, wherein the second glass ply is strengthened.
[0372] A 54th aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 53, wherein the second glass ply is chemically strengthened by an ion exchange treatment.
[0373] A 55th aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 54, wherein the glass laminate is configured for use in a vehicle having a body defining an interior and an opening, wherein the glass laminate is configured to be placed in the opening, and wherein the first glass ply is arranged to face the exterior of the vehicle and the second glass ply is arranged to face the interior of the vehicle.
[0374] Aspect 56 of the present disclosure includes a glass laminate according to any one of aspects 51 to 55, wherein the first glass ply has a first thickness of at least 2 mm between the first major surface and the second major surface, and wherein the second glass ply has a second thickness of less than 2 mm between the third major surface and the fourth major surface.
[0375] A 57th aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 56, wherein the glass laminate includes a total glass thickness equal to the sum of the first thickness and the second thickness, and a ratio of the first glass thickness to the total glass thickness is at least 0.7.
[0376] A 58th aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 57, wherein the first glass thickness is at least 3 mm and the second glass thickness is 1.1 mm or less.
[0377] A 59th aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 58, wherein the first glass thickness is at least 3.3 mm and the second glass thickness is 0.7 mm or less.
[0378] A sixtieth aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 59, wherein the second glass ply comprises a second glass composition.
[0379] A 61st aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 60, wherein the second glass composition is different from the borosilicate glass composition.
[0380] Aspect 62 of the present disclosure includes a glass laminate according to any one of aspects 51 to 61, wherein the second glass composition is selected from the group consisting of soda-lime-silicate glass compositions, aluminosilicate glass compositions, alkali aluminosilicate glass compositions, alkali-borosilicate glass compositions, alkali-aluminophosphosilicate glass compositions, alkali-aluminoborosilicate glass compositions, and combinations thereof.
[0381] A 63rd aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 62, wherein the visible light transmission through the glass laminate is at least 73% as measured according to ISO 13837A.
[0382] A 64th aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 62, wherein a total solar transmittance through the glass laminate measured according to ISO 13837A is 90% or less.
[0383] Aspect 65 of the present disclosure includes a glass laminate according to any one of aspects 51 to 64, wherein the first major surface, the fourth major surface, or both the first major surface and the fourth major surface exhibit an optical distortion of at most 200 millidiopters as measured using an optical distortion detector using transmission optics in accordance with ASTM 1561.
[0384] Aspect 66 of the present disclosure includes a glass laminate according to any one of aspects 51 to 65, wherein the interlayer is selected from the group consisting of polyvinyl butyral (PVB), acoustic PVB (APVB), ionomers, ethylene vinyl acetate (EVA), thermoplastic polyurethane (TPU), polyester (PE), polyethylene terephthalate (PET), and combinations thereof.
[0385] A 67th aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 62, wherein the interlayer includes a thickness ranging from about 0.5 mm to about 2.5 mm.
[0386] A 68th aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 67, wherein the interlayer includes at least one functional layer or film.
[0387] Aspect 69 of the present disclosure includes a glass laminate according to any one of aspects 51 to 68, wherein the functional layer or film provides a function selected from the group consisting of ultraviolet absorption, infrared absorption, infrared reflection, sound attenuation, tint, antenna, adhesion promotion, anti-glare treatment, anti-reflection treatment, and combinations thereof.
[0388] Aspect 70 of the present disclosure includes a glass laminate according to any one of aspects 51 to 69, wherein a first glass ply and a second glass ply are formed in a pair, wherein the first glass ply comprises a first depth of curvature of at least 2 mm, wherein the second glass ply comprises a second depth of curvature of at least 2 mm, and wherein the first depth of curvature differs from the second depth of curvature by within 10%.
[0389] A 71st aspect of the present disclosure includes a glass laminate according to any one of aspects 51 to 70, wherein the first glass ply is sag and includes a depth of curvature of at least 2 mm, and wherein the second glass ply is cold formed to conform to the first glass ply.
[0390] Aspect 72 of the present disclosure includes a system comprising: a sensor; and a glass laminate comprising: a first glass layer comprising a first major surface and a second major surface opposite the first major surface, wherein the first glass layer comprises a borosilicate glass composition; a second glass layer comprising a third major surface and a fourth major surface opposite the third major surface; and an intermediate layer that bonds the second major surface of the first glass layer to the third major surface of the second glass layer; wherein the borosilicate glass composition comprises: at least 74 mol % SiO2; at least 10 mol % B2O3; and an amount of Al2O3 such that the sum of SiO2, B2O3, and Al2O3 is at least 90 mol %; wherein the sensor is configured to receive, transmit, or simultaneously receive and transmit a signal through the glass laminate; wherein the signal comprises a peak frequency in the range of 400 nm to 750 nm or in the range of 1500 nm or greater.
[0391] A 73rd aspect of the present disclosure includes a system according to aspect 72, wherein the sensor is a LIDAR.
[0392] A 74th aspect of the present disclosure includes a system according to any one of aspects 72 to 73, wherein the glass laminate is a glazing of a vehicle.
[0393] A 75th aspect of the present disclosure includes a system according to any one of aspects 72 to 74, wherein the visible light transmission through the glass laminate is at least 73% as measured according to ISO 13837A.
[0394] A 76th aspect of the present disclosure includes the system according to any one of aspects 72 to 75, wherein the total solar light transmittance through the glass laminate measured according to ISO 13837A is 90% or less.
[0395] Aspect 77 of the present disclosure includes a system according to any one of aspects 72 to 76, wherein the first major surface, the fourth major surface, or both the first major surface and the fourth major surface exhibit an optical deformation of up to 200 millidiopters, as measured using an optical deformation detector using transmission optics in accordance with ASTM 1561.
[0396] A 78th aspect of the present disclosure includes the system according to any one of aspects 72 to 77, wherein the first glass ply is thicker than the second glass ply.
[0397] A 79th aspect of the present disclosure includes a system according to any one of aspects 72 to 78, wherein the second glass ply is strengthened.
[0398] An 80th aspect of the present disclosure includes the system according to any one of aspects 72 to 79, wherein the second glass ply is chemically strengthened by an ion exchange treatment.
[0399] An 81st aspect of the present disclosure includes a glass laminate comprising: a first glass layer comprising a first major surface and a second major surface opposite the first major surface, wherein the first glass layer comprises a fused-formed borosilicate glass composition; a second glass layer comprising a third major surface and a fourth major surface opposite the third major surface; and an intermediate layer that bonds the second major surface of the first glass layer to the third major surface of the second glass layer; wherein the transmittance of ultraviolet light in the wavelength range of 300-380 nm through the glass laminate is 75% or less; wherein the transmittance in the visible spectrum through the glass laminate is 73% or greater; and wherein the total solar transmittance through the glass laminate is 61% or less.
[0400] Aspect 82 of the present disclosure includes a glass laminate according to aspect 81, wherein the borosilicate glass composition comprises: at least 74 mol% SiO2; at least 10 mol% B2O3; and an amount of Al2O3 such that the sum of SiO2, B2O3, and Al2O3 is at least 90 mol%.
[0401] An 83rd aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 82, wherein the first glass ply is thicker than the second glass ply.
[0402] An 84th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 83, wherein the second glass ply is strengthened.
[0403] An 85th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 84, wherein the second glass ply is chemically strengthened by an ion exchange treatment.
[0404] An 86th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 85, wherein the second glass ply comprises an ion-exchangeable glass frit applied to the third major surface, the fourth major surface, or both the third major surface and the fourth major surface.
[0405] An 87th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 86, wherein the first glass ply has a first thickness of at least 2 mm between the first major surface and the second major surface, and wherein the second glass ply has a second thickness of less than 2 mm between the third major surface and the fourth major surface.
[0406] An 88th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 87, wherein the glass laminate includes a total glass thickness equal to the sum of the first thickness and the second thickness, and a ratio of the first glass thickness to the total glass thickness is at least 0.7.
[0407] An 89th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 88, wherein the first glass thickness is at least 3 mm and the second glass thickness is 1.1 mm or less.
[0408] A 90th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 89, wherein the first glass thickness is at least 3.3 mm and the second glass thickness is 0.7 mm or less.
[0409] A 91st aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 90, wherein the second glass ply comprises a second glass composition.
[0410] A 92nd aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 91, wherein the second glass composition is different from the borosilicate glass composition.
[0411] Aspect 93 of the present disclosure includes a glass laminate according to any one of aspects 81 to 92, wherein the second glass composition is selected from the group consisting of aluminosilicate glass compositions, alkali aluminosilicate glass compositions, alkali borosilicate glass compositions, alkali aluminophosphosilicate glass compositions, alkali aluminoborosilicate glass compositions, and combinations thereof.
[0412] A 94th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 93, wherein the interlayer is selected from the group consisting of polyvinyl butyral (PVB), acoustic PVB (APVB), ionomers, ethylene vinyl acetate (EVA), thermoplastic polyurethane (TPU), polyester (PE), polyethylene terephthalate (PET), and combinations thereof.
[0413] A 95th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 93, wherein the interlayer includes a thickness ranging from about 0.5 mm to about 2.5 mm.
[0414] A 96th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 95, wherein the interlayer includes at least one functional layer or film.
[0415] Aspect 97 of the present disclosure includes a glass laminate according to any one of aspects 81 to 96, wherein the functional layer or film provides a function selected from the group consisting of ultraviolet absorption, infrared absorption, infrared reflection, sound attenuation, tint, antenna, adhesion promotion, anti-glare treatment, anti-reflection treatment, and combinations thereof.
[0416] A 98th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 97, wherein the first glass ply and the second glass ply are formed in a pair, wherein the first glass ply includes a first depth of curvature of at least 2 mm, wherein the second glass ply includes a second depth of curvature of at least 2 mm, and wherein the first depth of curvature differs from the second depth of curvature within 10%.
[0417] A 99th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 98, wherein the first glass ply comprises a first glass ply having a viscosity of 10 11 The first temperature of the second glass layer includes a viscosity of 10 11 The second temperature is a second temperature when the first temperature is different from the second temperature.
[0418] A 100th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 99, wherein the first glass ply is thicker than the second glass ply, and wherein the second temperature is greater than the first temperature.
[0419] A 101st aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 100, wherein the first glass ply is sag and includes a depth of curvature of at least 2 mm, and wherein the second glass ply is cold formed to conform to the first glass ply.
[0420] A 102nd aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 101, wherein the second glass ply comprises a pigment coating on the third major surface.
[0421] A 103rd aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 102, wherein the first glass ply or the second glass ply comprises a coating.
[0422] A 104th aspect of the present disclosure includes a glass laminate according to any one of aspects 81 to 103, wherein the coating includes an infrared reflective coating having at least one layer of metal and optionally at least one layer of dielectric.
[0423] Aspect 105 of the present disclosure includes a glass composition comprising: SiO2 in an amount of about 72 mol% to about 80 mol%; Al2O3 in an amount of about 2.5 mol% to about 5 mol%; and B2O3 in an amount of about 11.5 mol% to about 14.5 mol%; wherein the glass composition comprises a liquidus viscosity greater than 500 kP; and wherein the glass composition comprises a temperature of 1725°C or less when the viscosity of the borosilicate glass composition is 200P.
[0424] A 106th aspect of the present disclosure includes the glass composition according to aspect 105, further comprising Na2O in an amount from about 4 mol% to about 8 mol%.
[0425] A 107th aspect of the present disclosure includes a glass composition according to any one of aspects 105 to 106, further comprising an amount of Na2O from about 4.5 mol% to about 8 mol%.
[0426] A 108th aspect of the present disclosure includes a glass composition according to any one of aspects 105 to 107, further comprising K2O in an amount from about 0.5 mol% to about 3 mol%.
[0427] A 109th aspect of the present disclosure includes a glass composition according to any one of aspects 105 to 108, further comprising MgO in an amount of about 0.5 to about 2.5 mol%.
[0428] A 110th aspect of the present disclosure includes a glass composition according to any one of aspects 105 to 109, further comprising up to about 4 mol% CaO.
[0429] A 111th aspect of the present disclosure includes a glass composition according to any one of aspects 105 to 110, wherein the amount of SiO2 is at least 74 mol%.
[0430] Aspect 112 of the present disclosure includes a glass composition comprising: 74 mol% to 80 mol% SiO2, 2.5 mol% to 5 mol% Al2O3, 11.5 mol% to 14.5 mol% B2O3, 4.5 mol% to 8 mol% Na2O, 0.5 mol% to 3 mol% K2O, 0.5 mol% to 2.5 mol% MgO, and 0 mol% to 4 mol% CaO.
[0431] A 113th aspect of the present disclosure includes the glass composition according to aspect 112, wherein the total amount of Na2O and K2O is at least 5.5 mol%.
[0432] A 114th aspect of the present disclosure includes a glass composition according to any one of aspects 112 to 113, wherein the total amount of MgO and CaO is at least 1.5 mol%.
[0433] A 115th aspect of the present disclosure includes a glass composition according to any one of aspects 112 to 114, wherein the total amount of Na2O, K2O, MaO, and CaO is at least 7 mol%.
[0434] A 116th aspect of the present disclosure includes a glass composition according to any one of aspects 112 to 114, wherein the total amount of Na2O and K2O is at least 8 mol%.
[0435] A 117th aspect of the present disclosure includes a glass composition according to any one of aspects 112 to 116, comprising a total amount of Fe2O3 and FeO of 0.03 mol% to 0.5 mol%.
[0436] Aspect 118 of the present disclosure includes an article comprising: a first glass ply comprising a first major surface and a second major surface opposite the first major surface, wherein the first glass ply comprises a borosilicate glass composition; a second glass ply comprising a third major surface and a fourth major surface opposite the third major surface; and an interlayer bonding the second major surface of the first glass ply to the third major surface of the second glass ply; wherein: (A) the borosilicate glass composition of the first glass ply comprises: (i) SiO2, B2O3, and optionally Al2O3 and / or P2O5; and (ii) one or more alkali metal oxides, and optionally one or more alkaline earth metal oxides and / or ZnO; wherein the molar percentage of SiO2, B2O3, the one or more alkali metal oxides, and when included in the composition, Al2O3, P2O5, and the one or more alkaline earth metal oxides and / or ZnO oxides is (B) when a glass of a borosilicate glass composition having a first glass ply is subjected to a Vickers indentation test using a quasi-static 2 kg force indentation load and a 136° Vickers indenter, the glass exhibits a plurality of radial cracks and annular cracks that limit the propagation of the radial cracks; and (C) when the article is installed in a vehicle, the first glass ply is an outboard of the second glass ply.
[0437] A 119th aspect of the present disclosure includes the article according to aspect 118, wherein the first glass ply is thicker than the second glass ply, and wherein the second glass ply is chemically strengthened by an ion exchange treatment.
[0438] A 120th aspect of the present disclosure includes an article according to any one of aspects 118 to 119, wherein the first glass ply has a first thickness between the first major surface and the second major surface of at least 2 mm, and wherein the second glass ply has a second thickness between the third major surface and the fourth major surface of less than 2 mm.
[0439] A 121st aspect of the present disclosure includes an article according to any one of aspects 118 to 120, wherein a ratio of the first thickness to the sum of the first and second thicknesses is at least 0.7.
[0440] A 122nd aspect of the present disclosure includes an article according to any one of aspects 118 to 121, wherein the first thickness is at least 3.3 mm and the second thickness is 0.7 mm or less.
[0441] A 123rd aspect of the present disclosure includes an article according to any one of aspects 118 to 122, wherein the second glass ply comprises a second glass composition that is different from the borosilicate glass composition of the first glass ply, and wherein the second glass composition is selected from the group consisting of a soda-lime silicate glass composition, an aluminosilicate glass composition, an alkali aluminosilicate glass composition, an alkali-containing borosilicate glass composition, an alkali aluminophosphosilicate glass composition, and an alkali aluminoborosilicate glass composition.
[0442] Aspect 124 of the present disclosure includes an article according to any one of aspects 118 to 123, wherein the visible light transmittance through the article measured according to ISO 13837A is at least 73%, and wherein the total solar transmittance through the article measured according to ISO 13837A is 90% or less.
[0443] Aspect 125 of the present disclosure includes an article according to any one of aspects 118 to 124, wherein the first major surface, the fourth major surface, or both the first major surface and the fourth major surface exhibit an optical distortion of at most 200 millidiopters as measured using an optical distortion detector using transmission optics in accordance with ASTM 1561.
[0444] Aspect 126 of the present disclosure includes an article according to any one of aspects 118 to 125, wherein the intermediate layer is selected from the group consisting of polyvinyl butyral (PVB), acoustic PVB (APVB), ionomers, ethylene vinyl acetate (EVA), thermoplastic polyurethane (TPU), polyester (PE), polyethylene terephthalate (PET), and combinations thereof; wherein the thickness of the intermediate layer ranges from 0.5 mm to 2.5 mm; wherein the intermediate layer comprises at least one functional layer or film, and wherein the functional layer or film provides a function selected from the group consisting of ultraviolet absorption, infrared absorption, infrared reflection, sound attenuation, hue, antenna, adhesion promotion, anti-glare treatment, anti-reflection treatment, and combinations thereof.
[0445] Aspect 127 of the present disclosure includes an article according to any one of aspects 118 to 126, wherein the first glass ply and the second glass ply are formed in a pair, wherein the first glass ply comprises a first depth of curvature of at least 2 mm, wherein the second glass ply comprises a second depth of curvature of at least 2 mm, and wherein the first depth of curvature differs from the second depth of curvature by within 10%.
[0446] Aspect 128 of the present disclosure includes an article according to any one of aspects 118 to 127, wherein the first glass ply is sag and includes a depth of curvature of at least 2 mm, and wherein the second glass ply is cold formed to conform to the first glass ply.
[0447] Aspect 129 of the present disclosure includes an article according to any one of aspects 118 to 128, wherein the first glass ply is manufactured by a down-draw process, wherein the down-draw process is a fusion down-draw process, wherein the glass of the borosilicate glass composition having the first glass ply has a liquidus viscosity greater than or equal to 500 kilopoise, and wherein the glass of the borosilicate glass composition having the first glass ply has a 200 poise temperature less than or equal to 1725°C.
[0448] Aspect 130 of the present disclosure includes an article comprising: a borosilicate glass and an outer layer having a thickness of at least 200 μm and not more than 1 cm, wherein the composition of the borosilicate glass comprises, in terms of constituent oxides, SiO2, B2O3, Al2O3, one or more alkali metal oxides, and one or more divalent cation oxides of the group consisting of MgO, CaO, SrO, BaO, and ZnO, wherein the concentrations, in terms of molar percentage of the oxides of SiO2, B2O3, the one or more alkali metal oxides, Al2O3, and the one or more alkaline earth metal oxides, satisfy the following relationship: (R2O+R'O)≥Al2O3, 0.80<(1-[(2R2O+2R'O) / (SiO2+2Al 2O3+2B2O3)])<0.93, wherein R2O is the sum of the concentrations of the one or more alkali metal oxides, and R'O is the sum of the concentrations of the one or more alkaline earth metal oxides; an inner sheet comprising a second glass having a composition different from that of the borosilicate glass of the outer sheet, wherein the inner sheet reinforces the outer sheet so that the outer sheet is hardened against a bending force applied thereto, and wherein the composition of the second glass is selected from the group consisting of a soda-lime-silicate glass composition, an aluminosilicate glass composition, an alkali aluminosilicate glass composition, an alkali-containing borosilicate glass composition, an alkali aluminophosphorus silicate glass composition, and an alkali aluminoborosilicate glass composition; an intermediate layer connecting the inner and outer sheets, wherein the intermediate layer is a polymer and inhibits the propagation of cracks from the outer sheet to the inner sheet.
[0449] A 131st aspect of the present disclosure includes an article according to aspect 130, wherein when the glass of the composition of the borosilicate glass having the outer layer is formed into 100 sheets with a thickness of 1 mm and a major surface of 2 x 2 cm 2When a polished flat sample of a certain area is tested at 25°C, 50% relative humidity using a square-based 136° four-sided pyramid Vickers indenter directed vertically to the center of the major surface and the indenter is quasi-statically displaced at a rate of 60 μm per second to an indentation load of a maximum force of 3 kg for 10 seconds, tending to all cracks from the indenter extending radially and / or laterally through the sample are contained in the crack loop.
[0450] A 132nd aspect of the present disclosure includes an article according to any one of aspects 130 to 131, wherein cracks that tend to extend radially and / or laterally through the sample do not propagate beyond the crack loop when rapidly cooled from 25°C to 1°C by placing the sample in cold water.
[0451] A 133rd aspect of the present disclosure includes an article according to any one of aspects 130 to 132, wherein a majority of the crack loops of the sample are circular and have a radius less than 1 mm.
[0452] A 134th aspect of the present disclosure includes an article comprising: a first glass ply comprising a first major surface and a second major surface opposite the first major surface, wherein the first glass ply comprises borosilicate glass, and wherein the composition of the borosilicate glass comprises, in terms of constituent oxides: SiO2, B2O3, Al2O3, one or more alkali metal oxides, and one or more divalent cation oxides selected from the group consisting of MgO, CaO, SrO, BaO, and ZnO, wherein the concentrations, in terms of mole percentages of oxides of SiO2, B2O3, the one or more alkali metal oxides, Al2O3, and the one or more divalent cation oxides, satisfy the following relationship: (R2O+R'O)≥Al2O3, 0 .80<(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])<0.93, wherein R2O is the sum of the concentrations of the one or more alkali metal cations, and R'O is the sum of the concentrations of the one or more divalent cation oxides; a second glass layer comprising a third major surface and a fourth major surface opposite to the third major surface; and an interlayer bonding the second major surface of the first glass layer to the third major surface of the second glass layer; wherein the transmittance of ultraviolet light in the wavelength range of 300-380 nm through the article is 75% or less; wherein the transmittance of the visible spectrum through the article is 73% or more; and wherein the total solar transmittance through the article is 61% or less.
[0453] Aspect 135 of the present disclosure includes an article according to aspect 134, wherein the borosilicate glass composition comprises: at least 74 mol% SiO2; at least 10 mol% B2O3; and an amount of Al2O3 such that the sum of SiO2, B2O3, and Al2O3 is at least 90 mol%.
[0454] Aspect 136 of the present disclosure includes an article comprising: a borosilicate glass, wherein the composition of the borosilicate glass comprises, in terms of constituent oxides, SiO2, B2O3, Al2O3, one or more alkali metal oxides, and one or more divalent cation oxides selected from the group consisting of MgO, CaO, SrO, BaO, and ZnO, wherein the molar percentage of the oxides of SiO2, B2O3, the one or more alkali metal oxides, Al2O3, and the one or more divalent cation oxides is The concentration satisfies the following relationship: (R2O+R'O)≥Al2O3, 0.80<(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])<0.93, wherein R2O is the sum of the concentrations of the one or more alkali metal oxides, and R'O is the sum of the concentrations of the one or more divalent cation oxides; a crack loop is formed in the borosilicate glass, wherein the article does not contain radial or transverse cracks that intersect the crack loop and extend outward beyond the crack loop.
[0455] A 137th aspect of the present disclosure includes the article according to aspect 136, wherein the crack loop has a circumference.
[0456] A 138th aspect of the present disclosure includes an article according to any one of aspects 136 to 137, wherein the circumference has a diameter of less than 1 mm.
[0457] A 139th aspect of the present disclosure includes an article according to any one of aspects 136 to 138, wherein the borosilicate glass has a thickness of at least 200 μm and no more than 1 cm.
[0458] A 140th aspect of the present disclosure includes an article according to any one of aspects 136 to 139, wherein the borosilicate glass has a low temperature coefficient of thermal expansion greater than 3.25 ppm / °C and less than 8.7 ppm / °C.
[0459] A 141st aspect of the present disclosure includes an article according to any one of aspects 30 to 129, wherein the thickness is greater than or equal to 2.0 mm.
[0460] A 142nd aspect of the present disclosure includes an article according to any one of aspects 30 to 129, wherein the composition of the borosilicate glass comprises greater than or equal to 4 mol % and less than or equal to 6 mol % Na2O.
[0461] Aspect 143 of the present disclosure includes an article according to any one of aspects 30 to 129, wherein the composition of the borosilicate glass comprises: greater than or equal to 3 mol% and less than or equal to 5 mol% Al2O3; and greater than or equal to 12 mol% and less than or equal to 16 mol% B2O3.
[0462] Aspect 144 of the present disclosure includes an article according to any one of aspects 30 to 129, wherein at least one of the following conditions exists: the composition of the borosilicate glass contains greater than or equal to 0.03 mol% and less than or equal to 0.5 mol% Fe2O3, and the thickness is less than or equal to 3.3 mm, and the outer layer has a transmittance greater than or equal to 90% and less than or equal to 92.5% across the entire visible spectrum.
[0463] A 145th aspect of the present disclosure includes an article according to any one of aspects 30 to 129, wherein the outer glass ply is composed of borosilicate glass.
[0464] A 146th aspect of the present disclosure includes a borosilicate glass composition comprising: greater than or equal to 60 mol% and less than or equal to 96.0 mol% SiO2, greater than or equal to 1.0 mol% and less than or equal to 25.0 mol% B2O3, greater than or equal to 0.3 mol% Al2O3, greater than or equal to 0.0 mol% and less than or equal to 0.3 mol% Li2O, a non-zero amount of Na2O, and one or more divalent metal oxides RO, wherein: represented by the molecular formula of each component, the composition amount of each component in mol% satisfies the following relationship: B2O3+3.5*Al2O3≤27.5 mol%, and at least one of the following: (A) the composition amount of each component satisfies both of the following conditions: (i) C rb -(3.4-0.5*C nb )<0.000, and (ii)1-2*(Alk2O+RO) / P 总 >0.83, where: (a) C rb is the rotatability balance parameter value, which is calculated from the composition in mole % of the components according to the following equation: rb =abs(2*max(0,(Alk2O+RO)-(Al2O3+B2O3))+2*min(B2O3,R2O+RO-Al2O3)+0.65*(SiO2+2*Al2O3+2*B2O3)-80), (b)C nbis the network equilibrium parameter value, which is calculated from the composition in mole % of the components according to the following equation: nb = abs(SiO2-6*min(Alk2O,Al2O3)-2*min(Alk2O+RO-Al2O3,B2O3)-max(24+2*max(0,B2O3-max(0,R2O+RO-Al2O3)),44)), (c) Alk2O represents one or more alkali metal oxides, if included in the composition, (d) P 总 is the total polyhedral parameter value, which is calculated from the composition in mole % of the components according to the following equation: 总 =SiO2+2*Al2O3+2*B2O3, and (B) the composition amount of each component satisfies the following conditions: P d -(2.58-0.2*(Na2O / Al2O3))<0.000, where P d is the density parameter value, which is calculated from the glass composition in terms of mole % of the components according to the following equation: d =2.487-0.0068998*B2O3+0.041371*BaO+0.13897*Bi2O3+0.011637*CaO+0.055366*Cs2O+0.025420*Fe2O 3+0.10294*Gd2O3+0.0051134*K2O+0.079903*La2O3+0.0041594*Li2O+0.0084582*MgO+0.019720*MnO+0.0 064419*Na2O+0.018282*NiO+0.065781*PbO-0.002953*SiO2+0.027682*SrO+0.0055367*TiO2+0.0068497 *V2O5+0.048699*Y2O3+0.021527*ZnO+0.026527*ZrO2+0.011033*(min(B2O3,max(0,Alk2O+RO-Al2O3))).
[0465] A 147th aspect of the present disclosure includes a borosilicate glass composition according to the 146th aspect, wherein: the composition amount of each component satisfies the following two conditions at the same time: (i) C rb -(3.4-0.5*C nb )<0.000; and (ii) 1-2*(Alk2O+RO) / P 总 >0.83, the total amount of Na2O and Al2O3 contained in the composition is less than or equal to 9.7 mol%, and the composition is essentially free of BaO, fluorine and rare earth oxides.
[0466] A 148th aspect of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 147, wherein the composition comprises: greater than or equal to 60.0 mol% and less than or equal to 78 mol% SiO2, greater than or equal to 5.0 mol% and less than or equal to 17.0 mol% B2O3, greater than or equal to 2.5 mol% and less than or equal to 5.3 mol% Na2O, greater than or equal to 0.3 mol% and less than or equal to 5.3 mol% Al2O3, greater than or equal to 0.0 mol% and less than or equal to 3.0 mol% K2O, greater than or equal to 0.0 mol% and less than or equal to 1.5 mol% CaO, greater than or equal to 0.0 mol% and less than or equal to 0.2 mol% Li2O, greater than or equal to 5.0 mol% Na2O+K2O, and the composition amount of each component satisfies the following condition: 20.3≤B2O3+3.5*Al2O3≤27.5.
[0467] A 149th aspect of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 148, wherein the composition comprises: greater than or equal to 0.0 mol% and less than or equal to 5.0 mol% MgO, greater than or equal to 0.0 mol% and less than or equal to 4.0 mol% P2O5, greater than or equal to 0 mol% and less than or equal to 0.25 mol% SnO2, and the total amount of (Na2O+K2O+MgO+CaO+ZnO+Al2O3+B2O3+SiO2) is greater than or equal to 95 .0 mol %, the total amount of (CaO + MgO) is greater than or equal to 0.0 mol % and less than or equal to 5.0 mol %, and the total amount of (FeO + Fe2O3) is greater than or equal to 0.0 mol % and less than or equal to 0.5 mol %, and wherein the composition amount of each component of the composition satisfies the following two conditions at the same time: (C) (Na2O + K2O + MgO + CaO + SrO + BaO + ZnO) / (R2O + RO) ≤ 0.95, and (D) 1.01 ≤ Na2O / Al2O3 ≤ 1.35.
[0468] Aspect 150 of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 149, wherein the composition comprises: greater than or equal to 72.0 mol% and less than or equal to 78.0 mol% SiO2, greater than or equal to 5.0 mol% and less than or equal to 20.0 mol% B2O3, greater than or equal to 2.0 mol% and less than or equal to 8.0 mol% Na2O, greater than or equal to 2.0 mol% and less than or equal to 4.0 mol% Al2O3, greater than or equal to 0.0 mol% and less than or equal to 3.0 mol% K2O, greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% CaO, greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% MgO, and greater than or equal to 0.0 mol% and less than or equal to 0.2 mol% SnO2.
[0469] Aspect 151 of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 150, wherein the composition comprises: greater than or equal to 0.0 mol% and less than or equal to 0.5 mol% MnO2, greater than or equal to 0.0 mol% and less than or equal to 0.5 mol% MnO, greater than or equal to 0.0 mol% and less than or equal to 0.5 mol% TiO2, and a total amount of (Fe+Cr+Mo+V+Cu+Co) greater than or equal to 0.0 mol% and less than or equal to 1.0 mol%, wherein the composition is: substantially free of Li2O, and substantially free of PbO.
[0470] A 152nd aspect of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 151, wherein the composition amount of each component satisfies the following condition: (E) 0.0≤2*M exc +2*min(B2O3,R2O+RO-Al2O3)+0.65*P 总 -80≤3.0, where: M exc is the modifier excess parameter value, which is calculated from the glass composition in terms of mole % of the component according to the following equation: exc =max(0,(Alk2O+RO)-(Al2O3+B2O3)), and (F)0.0≤abs(Si exc -3*((B2O3+Al2O3)-(Alk2O+RO))-max(24-B exc ,44-3*B exc ))≤3.0, where: (i)Si exc is the silica excess parameter value, which is calculated from the glass composition in terms of mole % of the components according to the following equation: Si exc=SiO2–6*min(Alk2O,Al2O3O3)–2*min(Alk2O+RO–Al2O3O3,B2O3), and (ii)B exc is the boron excess parameter value, which is calculated from the glass composition in terms of mole % of the component according to the following equation: exc =max(0,B2O3–max(0,R2O+RO–Al2O3)).
[0471] A 153rd aspect of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 152, wherein the composition amount of each component satisfies the following conditions: d –(2.58–0.2*(Na2O / Al2O3O3))<0.000.
[0472] A 154th aspect of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 153, wherein the composition comprises: greater than or equal to 60.0 mol% and less than or equal to 77.5 mol% SiO2, greater than or equal to 5.0 mol% and less than or equal to 17.0 mol% B2O3, greater than or equal to 2.5 mol% and less than or equal to 5.3 mol% Na2O, greater than or equal to 0.3 mol% and less than or equal to 5.3 mol% Al2O3, greater than or equal to 0.0 mol% and less than or equal to 3.0 mol% K2O, greater than or equal to 0.0 mol% and less than or equal to 0.2 mol% Li2O, greater than or equal to 0.0 mol% and less than or equal to 0.2 mol% BaO, and the total amount of (Na2O+K2O) is greater than or equal to 5.0 mol%.
[0473] Aspect 155 of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 154, wherein the composition comprises: greater than or equal to 5.0 mol% and less than or equal to 5.2 mol% Na2O, greater than or equal to 0.3 mol% MgO, and greater than or equal to 0.0 mol% and less than or equal to 0.3 mol% TiO2, wherein the composition is essentially free of fluorine.
[0474] A 156th aspect of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 155, wherein the composition amount of each component satisfies the following condition: 1-2*(Alk2O+RO) / P 总 >0.83.
[0475] A 157th aspect of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 156, wherein the composition amount of each component satisfies the following condition: (G) 77 ≤ (2*M exc+2*min(B2O3,R2O+RO-Al2O3))+0.65*P 总 ≤82, of which: M exc is the modifier excess parameter value, which is calculated from the glass composition in terms of mole % of the component according to the following equation: exc =max(0,(Alk2O+RO)-(Al2O3+B2O3)), and (H)0.84≤1-2*(Alk2O+RO) / P 总 ≤0.90.
[0476] A 158th aspect of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 157, wherein the composition comprises: greater than or equal to 0.0 mol% and less than or equal to 4.0 mol% P2O5, greater than or equal to 0 mol% and less than or equal to 0.25 mol% SnO2, a total amount of (Na2O+K2O+MgO+CaO+ZnO+Al2O3+B2O3+SiO2) greater than or equal to 95.0 mol%, (CaO+MgO ) is greater than or equal to 0.0 mol % and less than or equal to 5.0 mol %, and the total amount of (FeO+Fe2O3) is greater than or equal to 0.0 mol % and less than or equal to 0.5 mol %, and wherein the composition amount of each component of the composition satisfies the following two conditions at the same time: (I) (Na2O+K2O+MgO+CaO+SrO+BaO+ZnO) / (R2O+RO)≤0.95, and (J) 1.01≤Na2O / Al2O3≤1.35.
[0477] Aspect 159 of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 158, wherein the composition comprises: greater than or equal to 72.0 mol% and less than or equal to 77.5 mol% SiO2, greater than or equal to 2.0 mol% and less than or equal to 4.0 mol% Al2O3, greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% CaO, greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% MgO, and greater than or equal to 0.0 mol% and less than or equal to 0.2 mol% SnO2.
[0478] Aspect 160 of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 159, wherein the composition comprises: greater than or equal to 0.0 mol% and less than or equal to 0.5 mol% MnO2, greater than or equal to 0.0 mol% and less than or equal to 0.5 mol% MnO, greater than or equal to 0.0 mol% and less than or equal to 0.5 mol% TiO2, the total amount of (Fe+Cr+Mo+V+Cu+Co) is greater than or equal to 0.0 mol% and less than or equal to 1.0 mol%, and the total amount of (La2O3+Y2O3) is greater than or equal to 0.0 mol% and less than or equal to 1.0 mol%.
[0479] A 161st aspect of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 160, wherein the composition is substantially free of fluorine, BaO, Li2O, and PbO.
[0480] A 162nd aspect of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 161, wherein the composition amount of each component satisfies the following condition: (K) 0.0 ≤ 2*M exc +2*min(B2O3,R2O+RO-Al2O3)+0.65*P 总 -80≤3.0, where: M exc is the modifier excess parameter value, which is calculated from the glass composition in terms of mole % of the component according to the following equation: exc =max(0,(Alk2O+RO)-(Al2O3+B2O3)), and (L)0.0≤abs(Si exc -3*((B2O3+Al2O3)-(Alk2O+RO))-max(24-B exc ,44-3*B exc ))≤3.0, where: (i)Si exc is the silica excess parameter value, which is calculated from the glass composition in terms of mole % of the components according to the following equation: Si exc =SiO2–6*min(Alk2O,Al2O3O3)–2*min(Alk2O+RO–Al2O3O3,B2O3), and (ii)B exc is the boron excess parameter value, which is calculated from the glass composition in terms of mole % of the component according to the following equation: exc =max(0,B2O3–max(0,R2O+RO–Al2O3)).
[0481] Aspect 163 of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 162, wherein the composition comprises: greater than or equal to 11 mol% and less than or equal to 16 mol% B2O3, greater than or equal to 2 mol% and less than or equal to 6 mol% Al2O3, and the total amount of Na2O, K2O, MgO and CaO is greater than or equal to 7.0 mol%.
[0482] A 164th aspect of the present disclosure includes a borosilicate glass composition according to any one of aspects 146 to 163, wherein the composition comprises greater than or equal to 4 mol % and less than or equal to 6 mol % Na2O.
[0483] Aspect 165 of the present disclosure includes an article according to any one of aspects 146 to 164, wherein the composition of the borosilicate glass comprises: greater than or equal to 3 mol% and less than or equal to 5 mol% Al2O3; and greater than or equal to 12 mol% and less than or equal to 16 mol% B2O3.
[0484] A 166th aspect of the present disclosure includes a glass article comprising the borosilicate glass composition according to any one of aspects 146 to 165.
[0485] A 167th aspect of the present disclosure includes a glass article according to aspect 166, wherein the glass article comprises a carbon fiber having a carbon content of less than 2.5 g / cm3 measured at 20°C. 3 density.
[0486] A 168th aspect of the present disclosure includes a glass article according to the 167th aspect, wherein the density measured at 20° C. is less than 2.3 g / cm 3 .
[0487] A 109th aspect of the present disclosure includes a glass article according to any one of aspects 167 to 168, wherein when the glass having a borosilicate composition is formed into 100 major surfaces with a thickness of 1 mm and a thickness of 2 x 2 cm 2 When a polished flat sample of a certain area is tested at 25°C, 50% relative humidity using a square-based 136° four-sided pyramid Vickers indenter directed vertically to the center of the major surface and the indenter is quasi-statically displaced at a rate of 60 μm per second to an indentation load of a maximum force of 3 kg for 10 seconds, tending to all cracks from the indenter extending radially and / or laterally through the sample are contained in the crack loop.
[0488] Item 170 includes the glass article of aspect 169, wherein a majority of the crack loops of the sample are circular and have a radius less than 1 mm.
[0489] The construction and arrangement of the compositions, assemblies and structures shown in various exemplary embodiments are only schematic. Although only some embodiments are described in detail in the present disclosure, many improvements are feasible (e.g., the size, scale, structure, shape and proportion of various elements, parameter values, installation arrangements, use of materials, colors, changes in orientation), which do not essentially deviate from the novel teachings and advantages of the subject matter described herein. Materials (e.g., glazing disclosed herein) can be used for glazing (e.g., windows, partitions) in building applications or can be used anywhere else, such as in packaging (e.g., containers). The order or sequence of any process, logical algorithm or method steps can be changed or reordered according to alternative embodiments. Without departing from the scope of the present invention, other replacements, modifications, changes and omissions can be made to the design, operating conditions and arrangements of various exemplary embodiments.
[0490] The borosilicate compositions (and / or borofusion compositions) described herein are suitable and advantageous for use in solar energy applications, in particular, in solar panels and / or solar modules, as described herein.
[0491] A series of experiments were completed to compare the borosilicate glass described herein with prior art soda-lime-silicate glass commonly used in the solar industry as cover glass for solar panels and solar modules. It was determined that the borosilicate compositions described herein, when incorporated into the first (front) substrate and / or second (back) substrate of a solar module or panel, achieve a mediated advantageous design including, but not limited to: (1): enhanced crack resistance to subsurface cracking when scratched; (2) scratch and weathering resistance; (3) lower density / 10% weight savings (providing an overall lighter module or panel compared to soda-lime-silicate glass of the same thickness); (4) higher transmittance across the spectrum (e.g., 300-800), with particular advantages / improvements observed at certain wavelengths; (5) consistent transmission over the service duration of the installation / field location; and (6) improved abrasion resistance; (7) lower potential for subsurface damage compared to soda-lime-silicate glass, among other advantages (processability, CTE matching / tuning with interlayers / encapsulants, lower CTE than SLG).
[0492] Fig.18 A schematic cross-sectional side view of an embodiment of a solar panel 10 is provided having one or more substrates from the borosilicate composition described herein incorporating various aspects of the present disclosure.
[0493] See also Fig.18, the solar cell 40 is held between two substrates (the first substrate 32 and the second substrate 42). The encapsulant 38 (e.g., the first encapsulant) is configured to be located between the solar cell 40 and the second surface 36 of the first substrate 32. The encapsulant 48 (e.g., the second encapsulant or an integral layer / monobody of the encapsulant 38) is configured to be located between the first surface 44 of the second substrate and the solar cell 40. In this configuration, the solar cell 40 is attached to the first substrate 32 and the second substrate 42.
[0494] The solar cell 40 is constructed with a functional material 50 that converts photons into electrons (a functional component of a solar cell). The solar cell 40 is constructed from the functional material 50, an electrode / electrode layer that configures the solar cell 40, a transparent oxide layer, and / or additives or intermediate layers. This layup and edge seal 22 provide an embodiment of the solar module 12. Fig.18 The solar panel 10 incorporates a frame 20 (e.g., constructed around the perimeter of the outer edge of the solar module 12 (e.g., at least partially overlapping the edge seal 22 of the solar module 12). The frame optionally includes a gasket that is configured to be located between the body of the frame 20 and the outer edge of the solar module 12. Optionally, a coating (e.g., an anti-reflective coating) is applied to the first surface 34 of the first substrate 32 (and / or the second surface 45 of the second substrate 42 (not shown)).
[0495] The solar cell 40 is configured with electrical leads that connect the solar cell to electrical wires and / or a junction box so that the solar cell is in electrical communication with the junction box and can transfer electrons out of the solar cell 40 in the form of electricity / current.
[0496] In some embodiments, the leads and wires / contacts are configured to be located within the edge of the frame 20, between the edge seal 22 and the frame / gasket assembly.
[0497] In some embodiments, the leads and wires are configured to extend through at least a portion of the second substrate (e.g., through a hole or a discontinuous edge portion) so that the wires are routed through a major surface portion of the second substrate and out of the solar panel into the junction box 24.
[0498] As shown, the first substrate can be configured as a major surface facing the sun / photon capture. The solar panel 10 or module 12 can also be configured in a bifacial configuration, thereby configuring for photon capture via the first substrate 32 and the second substrate 42.
[0499] Fig.19A-C According to one or more embodiments of the present disclosure, various schematic embodiments of enlarged cross-sectional side views of aspects are provided, which incorporate the borosilicate composition of the embodiments of the present disclosure into a layer in a solar module of various configurations ( Fig.19A and 19B ) and as a retrofit cover configured to attach to a surface of a solar panel ( Fig.19C ).
[0500] Fig.19A Illustrative examples of solar modules 12 are provided having an embodiment borosilicate composition incorporated therein as a first substrate or a second substrate incorporating one or more aspects of the present disclosure.
[0501] because Fig.19A -C combines the Fig.18 so those reference numerals and relative descriptions also apply to Fig.19A -C.
[0502] See also Fig.19A , showing two solar cells (solar cells 40 and 40'). The solar cells are arranged adjacent to each other and can be printed, adhered, constructed, deposited or layered, etc., to form a series solar module, wherein one solar cell 40 (first solar cell) is constructed to be at least partially located on top of another solar cell 40' (second solar cell).
[0503] Fig.19B Illustrative examples of solar modules 12 are provided having an embodiment borosilicate composition incorporated therein as a first substrate or a second substrate, incorporating one or more aspects of the present disclosure. Likewise, Fig.19B It includes two solar cells: solar cells 40 and 40'. Fig.19A , Fig.19B The tandem configuration shown incorporates an intervening encapsulation layer 48 between the solar cells. In this configuration, the solar module 12 is Fig.19B Three packages 38, 48 and 56 are used in the layup construction.
[0504] See also Fig.19C , showing an illustrative example of a retrofit cover 54 for a solar module 12 (or solar panel 10) according to one or more aspects of the present disclosure. Fig.19CAs shown, the first substrate in the covering comprises an embodiment borosilicate composition, in combination with one or more aspects of the present disclosure. In addition, the encapsulation is adjusted to: (1) provide a protective surface covering for the first substrate; (2) provide structural rigidity and / or cushioning support for the first substrate during shipping, transportation, and on-site; and / or (3) provide a surface configured to adhere to the surface of an existing solar panel on-site. As a non-limiting embodiment, the encapsulant can be configured as a sealant, glue, adhesive, room temperature curing polymer, UV curing polymer, adhesive, optically clear adhesive, and / or combinations thereof. In an embodiment, by incorporating a modified covering on the surface of a (e.g., installed) solar panel, the uppermost surface of the solar panel can be adjusted for one or more advantages of the embodiment borosilicate composition of the present invention, as described herein.
[0505] In some embodiments, an anti-reflective coating is applied to the first surface of the first substrate to reduce reflection on the surface of the glass coating, thereby increasing the efficiency of the solar panel. In some embodiments, the AR coating is configured to allow more photons to enter the solar cell.
[0506] Example: Comparative analysis of borosilicate glass embodiments and soda-lime-silicate glass comparative examples.
[0507] In order to better quantify whether one or more borosilicate glass compositions of the present disclosure have advantages when used in solar module applications, a series of analytical and experimental measurements were completed in which the borosilicate glass compositions were evaluated against soda-lime silicate glasses in terms of various parameters, as described in the following paragraphs.
[0508] Fig. 20 Transmission data for iron-free borosilicate glass and clear soda-lime silicate glass are provided, plotted as percent transmittance versus wavelength (300nm to 800nm). Each glass sample was constructed to have the same 1.08mm thickness. Fig. 20 As shown, at all wavelengths, the iron-free boron fused glass has higher transmission than the clear SLG. In addition, there is a sharp contrast in transmission between 300nm and 400nm for the borosilicate glass: at 300nm, the SLG is approximately 4% transmission, while the borosilicate is 67% transmission; at 350nm, the soda-lime-silicate glass is 82% transmission, while the borosilicate is 92% transmission; and in the wavelength range of 400-800nm, improvements between approximately 3-7% improvement were measured, as shown in Figure 2. Fig. 20Without being limited to any particular mechanism or theory, by incorporating one or more embodiments of borosilicate glass described herein into a solar module or solar panel, the functional material in the panel receives more photons than soda-lime-silicate glass at all evaluated wavelengths. Compared to the measured transmission of soda-lime-silicate glass, the selected improvement, although Fig. 20 Comparative examples of borosilicate glass composition embodiments compared to SLG are shown, but this measured improvement is believed to apply to all borosilicate glass compositions described in detail herein that do not contain iron.
[0509] Table 1200: Table 1200 provides a list of mechanical, thermal, and optical properties of borosilicate glasses (boron melts) of the present disclosure compared to soda-lime silicate glasses.
[0510]
[0511]
[0512] *DCB as mentioned above means double cantilever beam.
[0513] As shown in Table 1200, for mechanical properties, the borosilicate glass composition embodiments provide substantially comparable properties. For thermal properties, the density of the borosilicate glass composition embodiments is approximately 10% lower than the SLG comparative, and the CTE of the borosilicate glass composition embodiments is approximately half that of the soda-lime-silicate glass comparative, and the remaining thermal properties are substantially comparable to each other. The optical properties (refractive index and stress optical coefficient) referred to in Table 1200 are also substantially comparable to each other.
[0514] The properties in Table 1200 show that the borosilicate glass compositions have lower density (i.e., lighter weight for the same dimensional dimensions) and lower CTE than soda-lime-silicate glass. Without wishing to be bound by any mechanism or theory, the borosilicate glass compositions described herein provide at least one of the following advantages, including, but not limited to: a lightweight drop-in replacement for soda-lime-silicate glass in solar panel and solar module applications, adjusting items such as frames and / or support rails / gantry based on panel weight reduction. In addition, given the formability and low CTE of borosilicate glass, it is believed that solar modules and / or solar panels incorporating borosilicate glass (e.g., as a substrate or superstrate) will have improved processability and lower thickness compared to corresponding soda-lime-silicate glass counterparts, providing at least one of the following advantages, including, but not limited to: improved manufacturing yield, improved lamination yield, and / or increased time.
[0515] Fig.21A series of SEM images at 20,000x magnification are provided of the surfaces of two glass samples: (1) soda lime silicate glass (top row), versus (2) a borosilicate glass composition embodiment described in detail above (bottom row), in three conditions: initial state before weathering (initial state); after weathering, and after weathering and cleaning. The starting glass sample, 'unweathered' is the as-fabricated state without any intentionally introduced damage, and both samples were constructed to have approximately the same cross-sectional thickness (2.1 mm cross-sectional thickness for SLG and 2.2 mm cross-sectional thickness for borosilicate glass).
[0516] Both samples were subjected to weathering after which their surface roughness was observed (middle image in 'After Weathering' column). Weathering on the samples involved keeping the samples at 85 degrees Celsius at a steady state of 85% relative humidity for a duration of 14 days.
[0517] After weathering, Fig.21 As shown, the soda-lime-silicate glass exhibits a significant increase in surface roughness that is visually observable and in stark contrast to the surface roughness of the borosilicate glass embodiment. The borosilicate glass embodiment appears to be in approximately the same condition / surface roughness in the 'unweathered state' and in the 'after weathering state'. Without wishing to be bound by any particular mechanism or theory, it is believed that the soda-lime-silicate glass undergoes surface reactions during weathering such that weathering byproducts (e.g., sodium carbonate) are deposited along the surface, such that the decomposition of the glass and the deposition of byproducts on the surface result in a significant increase in surface roughness. Although the specifications
[0518] After weathering, both samples were subjected to a cleaning cycle in a commercially available cleaning machine configured with ultrasonic capabilities, after which their surface roughness was observed again (right image in the 'Weathering + After Cleaning' column). Each glass sample was cleaned according to the following cleaning process steps: rinsed with deionized (DI) water; cleaned with 4% semi clean detergent at an ultrasonic frequency of 40 kHz; rinsed with DI water; rinsed with DI water at an ultrasonic frequency of 40 kHz; rinsed with DI water while the sample was slowly removed from the ultrasonic environment; and the sample was air dried. Each step of the cleaning process was completed at an elevated temperature (temperature of 160 degrees Fahrenheit), and each step lasted for 720 seconds.
[0519] After weathering and cleaning, the surface roughness of the soda-lime-silicate glass sample still exhibits a noticeable surface roughness compared to the 'unweathered' image, but appears to be a smoother surface roughness compared to the 'after weathering' image. Without being bound by any particular mechanism or theory, it is believed that the cleaning process can achieve a more uniform surface decomposition of the soda-lime-silicate glass, such that the weathering byproducts (e.g., sodium carbonate) are distributed in a more uniform manner compared to the initial weathering state alone (shown as a visual improvement after weathering + cleaning), which is relative to the 'after weathering' image alone. In both states (after weathering and after weathering and cleaning), the soda-lime-silicate glass decomposes to increase the surface roughness, such as Fig.21 As shown in the SEM image.
[0520] After weathering and cleaning, the surface roughness of the borosilicate glass composition embodiment appears unchanged compared to the 'unweathered' and 'after weathering' images. Comparing the two 'after weathering + cleaning' SEM images, the soda-lime-silicate glass sample has a visually observable significantly higher surface roughness than the borosilicate glass composition embodiment. Thus, the borosilicate glass composition embodiment exhibits improved weathering compared to the soda-lime-silicate glass composition.
[0521] Overall, the soda-lime-silicate glass samples showed a significant amount of decomposition / weathering compared to the borosilicate glass composition embodiments. It is believed that weathering and / or weathering and cleaning processes are proxy assessments of the durability of the substrate in an installed state (e.g., as a superstrate or substrate in a solar module or solar panel). Without being limited to any particular mechanism or theory, it is believed that at least one or both of the decomposition manufacturing products occurring on the surface of the soda-lime-silicate glass are detrimental to the transmittance of the substrate in solar applications. For example, an increase in surface roughness (e.g., due to an unregulated approach to weathering and cleaning) results in scattering in the substrate, thereby reducing the transmittance of photons through the glass substrate and into the functional materials in the solar module or solar panel. Similarly, surface decomposition of soda-lime-silicate glass resulting in weathering byproducts (e.g., sodium carbonate) creates a non-transmissive surface covering all or part of the surface of the soda-lime-silicate glass substrate, thereby contributing to adverse effects when used in solar applications (e.g., reduced transmission, increased absorption of photons entering the non-transparent material, increased haze, and scattering, etc.), which results in lower transmission and, therefore, reduced efficiency of the functional material used in the solar module or solar panel.
[0522] See also Fig. 22 , two samples of the borosilicate glass composition embodiment and the soda-lime silicate glass were subjected to Fig.21The same weathering and cleaning process as described above was followed, but here the scratch damage evolution after weathering was evaluated as a proxy for the durability of the substrate to be installed in a solar application (solar panel or solar module). Fig. 22 As shown, each sample was subjected to a series of scratches according to the Knoop scratch test at either 2N or 3N (top row 'after scratching, before weathering and cleaning'), followed by weathering and then cleaning (the final image taken for each sample is shown in the bottom row 'after weathering and cleaning'). Fig. 22 As shown, the Knoop scratch does impart some visually detectable damage to the soda lime silicate glass prior to weathering and cleaning, whereas the Knoop scratch does not impart any visually detectable surface damage to the borosilicate glass composition embodiment prior to weathering and cleaning.
[0523] The weathering and cleaning steps exposed subsurface damage (imparted by Knoop scratches) on each type of glass, wherein prior to the weathering and cleaning steps, the subsurface damage was not visually detectable in any of the four samples. Through the weathering and cleaning cycles, the subsurface damage was exposed and was visually detectable / observable, such as Fig. 22 As shown in the bottom row, the soda-lime silicate glass has significantly more subsurface damage in both 2N and 3N cases compared to either of the borosilicate glass compositions.
[0524] As described above, and without being limited to any particular mechanism or theory, subsurface damage due to scratches imparts significant degradation initiation sites in soda-lime silicate glass samples, while having very little effect on borosilicate glass compositions. For solar applications, it is believed that any surface or subsurface damage reduces the transmission through the substrate into the functional materials in the solar panel / solar module, which can adversely affect the efficiency and / or long-term durability of the solar panel once one or more scratches are imparted on the surface of the substrate.
[0525] like Fig.23 As shown, a microscope image at 100x magnification shows spot and scratch damage on a sample derived from a proxy analysis from the automotive field. This evaluation was adopted as an evaluation mode of whether and how repeated friction wear combined with weathering and cleaning processes would affect the surface quality / deterioration in substrates used for solar applications, where such effects on surface quality / deterioration could be detrimental to transmission.
[0526] One of each type (boron fusion glass and soda-lime silicate glass with 0.1 wt. % Fe2O3, 3.3 mm cross-sectional thickness, respectively) was subjected to a linear abrasion test as described herein, followed by a weathering and then a cleaning process (wherein the weathering and cleaning processes were the same as above with respect to Fig.21 and22 are the same).
[0527] Linear Abrasion Process Windshield wiper abrasion was conducted using a Taber 5750 Linear Abraser with a 250 g load, set to 60 cycles / minute, and continued for 500 cycles, wherein the process was configured to dispense the AZ dust / water solution to clean the glass every ~50 cycles. It is noted that the iron in the borosilicate glass composition is believed to have no effect on weathering performance, and it is believed that the compositions evaluated would perform substantially the same if the iron-free compositions described herein were evaluated.
[0528] like Fig.23 As shown, after abrasion and weathering, the comparative example has obvious spots and areas of line / scratch damage that are easily visually observable, while the corresponding borosilicate glass composition has very faint, barely visually visible, visually observable lines. It is believed that the spots and large areas of discoloration in the soda-lime-silicate glass are caused by weathering byproducts (as described above), which can be washed away (also as described above). After weathering and washing, the weathering byproducts appear to be significantly removed from the soda-lime-silicate glass, leaving streaks / line marks on the glass that are easily detected by visual observation. In contrast, after weathering, the borosilicate glass composition embodiment has more obvious streaks / line marks than before washing, but even after washing, the line marks / scratches in the borosilicate glass composition embodiment are still far less obvious than in the soda-lime-silicate glass comparative example. That is, by this evaluation, the borosilicate glass has improved performance compared to the soda-lime-silicate glass.
[0529] See also Fig.24 , provides Fig.23 Confocal microscopy images of the samples described in , except that the confocal microscopy images were taken after abrasion (top row) and then after weathering and cleaning (bottom row). Confocal microscopy provides a qualitative analysis of the presence and approximate depth of scratches, and also provides a quantitative analysis of the depth of surface damage / scratch penetration (see the corresponding scale bar on the right side of each image, with a lower depth limit of 0.1 micrometers (i.e., -0.10 micrometers, as shown in Figure 2). Fig.24 Each image has a size of 117 microns by 88 microns. Fig.24 As shown, the soda-lime silicate glass exhibits greater surface roughness and linear wear depth than the borosilicate glass composition embodiment.
[0530] Figures 25A to 25C Three separate % transmission diffusion plots over the visible light spectrum (nm) are provided and show that borosilicate glass after linear abrasion ( Fig.25A ), after linear wear followed by weathering ( Fig.25B), and after linear wear followed by weathering and then washing ( Fig.25C ) to maintain the transmissive support. Weathering and cleaning are similar to those described above. Fig.21 Linear wear is the same as Fig.23 Same process as discussed above.
[0531] Since the soda-lime-silicate glass was manufactured so that it had two different major surfaces (facing tin or 'tin side' and facing air or 'air side'), for comparison purposes with borosilicate glass composition embodiments, two comparative soda-lime-silicate glass samples with abrasion / weathering / cleaning on opposite sides were subjected to diffusion measurements.
[0532] See all Fig.25A , 25B At 25°C and 25°C, the borosilicate glass had lower % transmission diffuse (haze) under all conditions compared to the soda lime silicate glass on either side. Although the SLG tin side showed less haze than the air side (indicating improved abrasion resistance), both SLG sides provided showed a significant amount of haze after abrasion and weathering compared to the borosilicate glass. This is believed to be due to surface degradation of the soda lime silicate glass by the weathering byproducts (sodium carbonate) formed during the weathering process as described above. Fig.25C It was shown that the cleaning process can make the soda-lime silicate glass have their respective percentage transmission diffusion reduced on both the tin-facing and air-facing sides, and the air side cannot be restored to the 'pre-weathering state' (such as Fig.25A It is important to note that although the cleaning process brings the tin side closer to its 'pre-weathering state', the cleaning cycle is only a temporary marginal improvement for field-installed solar modules containing soda-lime-silicate glass, because when installed, the soda-lime-silicate glass will continue to weather and decompose, forming haze-inducing weathering byproducts, which in turn will again reduce transmission.
[0533] Referring to Table 1300 below, the haze for each sample after each step was calculated and is shown below.
[0534] Table 1300
[0535]
[0536] Next, a chemical durability test was completed to show the influence of the substrate and the comparative substrate under acidic, neutral (control) and alkaline conditions in a comparative manner. Chemical durability was measured by immersing the glass sample in a 5 mass % HCl aqueous solution at 95°C for 24 hours and in a 5 mass % NaOH at 95°C for 6 hours. Before immersing the sample, the sample was rinsed with distilled water (16M resistance) for 5 minutes while squeezing the Tygon tube to obtain a shower-like rinse; ultrasonic vibration (50 / 60Hz frequency) in 4% Semiclean Detergent (semi-clean detergent) at 60°C to 65°C for 1 minute; rinsed again with 16M distilled water for 5 minutes while squeezing the Tygon tube to obtain a shower-like rinse; followed by a final rinse of 18M distilled water bath in a waterfall for 5 minutes. The sample was then transferred to a glass rack on a stainless steel tray and dried in an oven at 110°C for 1 hour and placed in a desiccator for use.
[0537] HCl tests were performed in Pyrex tubes in a hot water bath; NaOH tests were done in platinum tubes in the same bath type. After treatment, the samples were flooded with 16 and 18 M distilled water, dried in a 110°C oven for approximately 30 minutes, and weighed to determine mass loss.
[0538] The soda lime silicate glass was found to undergo no significant decomposition in the alkaline chemical durability test. Without being bound by any particular mechanism or theory, it is believed that the soda lime silicate glass forms byproducts in the soda lime silicate, which act as some kind of surface protection for the surface of the soda lime silicate glass, preventing further decomposition. The NaOH byproduct is believed to be CaSiO4, which is formed as a result of the reaction of NaOH with the soda lime silicate in the NaOH bath, releasing some of the Ca (from the glass) into the alkaline solution. 2+ and forms Ca(OH)2. Calcium hydroxide, in turn, is chemically available to react with the silicon dioxide in the soda lime silicate to form CaSiO4, which has very low solubility in alkaline solutions so that it can deposit on the glass surface and form a "protective layer", but also increases haze / reduces transmission through the substrate. The following table 1400 shows the weight change and optical results, with the test media listed at the head of each row.
[0539] Table 1400: Weight changes and optical results
[0540]
[0541]
[0542] Borosilicate glass exhibited the highest weight loss after the alkaline chemical durability test, but despite this weight loss, no haze was detected.
[0543] Fig.26A To show the crack behavior under subcritical stress, two groups of samples were subjected to a 3kgf Vickers indentation glass ring-on-ring test under subcritical crack growth stress at different applied stresses (30MPa and 35MPa). Fig.26A As shown, under an applied stress of 30 MPa, the load stress generated by the ring on ring caused the soda lime silicate glass to break in about one minute (all three samples); in sharp contrast, the borosilicate glass samples (4 in total) evaluated under the same conditions did not break after 10 minutes (end of run). Under a higher stress (35 MPa), the three soda lime silicate glass samples each broke within 10 seconds, while the borosilicate glass samples exceeded the end of the run time (10 minutes). In order to better understand the capabilities of the borosilicate glass, two samples continued to be evaluated even after the end of the run time (10 minutes), one sample broke when almost one and a half minutes of the test duration had passed, and the other sample broke more than 37 minutes after the end of the test run time (more than 47 minutes in total).
[0544] Fig.26B Shows Fig.26A Two representative images of a boron fusion glass sample evaluated in the test, where the top image shows the initial crack in the boron fusion sample, and the bottom image shows the crack growth of the same boron fusion glass sample after being held at 35 MPa for 10 minutes of run time. Fig.26B As shown, after being held under pressure in the ring-on-ring test, some radial cracks grew larger, but the radial cracks did not extend into the annular cracks.
[0545] Fig. 27 and 28 The following illustrative support is provided: One or more borosilicate glass compositions of the present disclosure can be prepared by thermal tempering ( Fig. 27 ) or ion exchange ( Fig.28 ) is strengthened by at least one of the following.
[0546] See also Fig. 27 , shows an illustrative example of one or more embodiments of the present disclosure, showing compressive stress from thermal tempering plotted along a cross-sectional profile side view of a boron fusion glass. As shown in the formula accompanying the cross section, the depth of layer of the thermally strengthened glass is 21% of its thickness, and the stress magnitude is determined by the thickness squared.
[0547] When calculating the central tension of soda lime silicate glass and borosilicate glass, a relative sense of the effect of thermal tempering stress on boron fusion and SLG is provided. As shown in Table 1500 below, when both glasses are tempered using the same conditions, SLG responds with a higher compressive stress than boron fusion glass (2.7 times higher).
[0548] The following table 1500 is the variables used in the stress distribution example:
[0549]
[0550]
[0551] like Fig.28 As shown, one or more borosilicate glass compositions of the present invention may be chemically strengthened by ion exchange. Fig.28 The strength (MPa) of the boron fusion glass composition and the ion exchanged boron fusion glass composition is shown. Even after 5 psi of 90 mesh SiC abrasion on 0.6 mm glass, the ion exchanged sample retained its strength. The ion exchange results from 100% KNO3 at 360°C are shown in Table 1600 below, and the Vickers indentation threshold is in Table 1700 below.
[0552] Table 1600: Ion exchange results of 100% KNO3, 380°C
[0553] Time (hours) CS(MPa) DOL(μm) 4 283 7 6 276 8 9 272 10 16 262 12.5 24 254 15
[0554] Table 1700: Vickers indentation thresholds
[0555] Time (hours) CS(MPa) DOL(μm) 4 283 7 6 276 8 9 272 10 16 262 12.5 24 254 15
[0556] In some embodiments, the solar module is a frameless module. When the solar module is a frameless module, the edge seal is configured to surround the solar stack in a perimeter manner to protect the electronic and functional material components from environmental influences (eg, water, oxygen, dust, humidity).
[0557] In some embodiments, the solar module is configured with a frame. In some embodiments, the solar module includes an edge seal configured around a perimeter edge of the solar stack.
[0558] In some embodiments, the frame together with the gasket provides sealing engagement around the perimeter edge of the solar module and / or provides compressive retention of the stacked modules.
[0559] In some embodiments, a frit glass or metal is used between the first substrate and the second substrate, wherein the frit glass is laser bonded to create an edge seal.
[0560] In some embodiments, the encapsulant is an intermediate layer that is laminated with the first substrate, the second substrate, and the solar cell to form a solar module.
[0561] In some embodiments, the encapsulant is EVA, polyolefin or similar material. In some embodiments, the encapsulant is a polymer configured to protect the solar cell from water egress and / or provide an elastic modulus to prevent cracking of the first and / or second substrate. In some embodiments, the encapsulant properties (thickness, elastic modulus) are adjusted based on the glass strength so that the designed solar panel can withstand the impact and load forces required in service.
[0562] In some embodiments, the first surface of the first substrate is configured with a textured coating. The textured coating is configured to facilitate photon guidance through the first glass substrate and into the solar cell. In one or more embodiments described herein, the texture of the front coating can be adjusted to improve efficiency.
[0563] In some embodiments, the coating on the back glass can be configured to provide a refractive index match to the second package, thereby providing improved adhesion.
[0564] In some embodiments, the borosilicate compositions described herein provide crack-trapping features after receiving a crack-initiating force, thereby reducing, preventing, and / or eliminating crack propagation and damage to the solar panel.
[0565] In some embodiments, the solar panel passes a 2-4J hail impact test.
[0566] In some embodiments, the solar panels undergo load testing sufficient to withstand snow loads, wind updrafts and downdrafts, and other environmental assessments for the solar panels and / or solar devices.
[0567] In some embodiments, the solar panels are adjusted to have appropriate design features and materials to ensure continued performance in headwind, tailwind, excessive temperature and / or deflection situations caused by the above-mentioned environmental conditions.
[0568] In some embodiments, the stack is 3 to 4 mm thick.
[0569] In some embodiments, the stack is symmetrical.
[0570] In some embodiments, the stacking is asymmetric.
[0571] In some embodiments, Fig.18And the solar panel or solar module described in 19A-C is configured to have an additional substrate (and attached packaging) on the first surface or the second surface to further protect the solar module.
[0572] In some embodiments, the first substrate and the second substrate are configured to facilitate at least one of the following properties: protecting the solar cell from impact, imperfections, and bending, minimizing light loss, managing surface properties, and the like.
[0573] In some embodiments, the solar panel is configured to be bifacial (capturing photons from the back side / second substrate of the solar module).
[0574] In some embodiments, the solar panel is a tandem design (multiple solar cells are stacked in the panel).
[0575] In some embodiments, glass compressive stress is conditioned (eg, configured to be in compression) to reduce, prevent, and / or eliminate crack and / or defect migration.
[0576] In some embodiments, the solar cell is selected from the categories of silicon, semiconductor compounds, and emerging market materials. In some embodiments, the silicon solar cell comprises a crystalline (e.g., single crystal or multicrystalline) or amorphous (hydrogenated amorphous silicon) solar cell. In some embodiments, the semiconductor material comprises a chalcogenide (e.g., cadmium telluride, copper zinc tin sulfide, copper indium gallium diselenide) or a III-V compound (e.g., gallium indium phosphide, gallium arsenide, etc.). In some embodiments, the solar material is an emerging market material category including dye-sensitized solar cells, colloidal quantum dots, perovskites, or organic materials.
[0577] In one or more embodiments described herein, the solar modules and / or solar panels are configured to pass IEC type tests for dynamic loads, static loads, and / or thermal cycling.
[0578] In one or more embodiments described herein, the solar module and / or solar panel is configured to pass at least one of: IEC 61216 module quality test (MQT) for: UV pre-conditioning (MQT 10), thermal cycling (MQT 11), humidity freeze (MQT 12), damp heat (MQT 13), potential induced degradation (MQT 21); and perovskite stability test, which covers: thermal, irradiation, electrical and environmental scenarios (PACT scenario described by IEC as of the date of this application) and / or combinations thereof. In some embodiments, the solar module and / or solar panel is configured to pass: IEC 61216 module quality test (MQT) for: UV pre-conditioning (MQT 10), thermal cycling (MQT 11), humidity freeze (MQT 12), damp heat (MQT 13), potential induced degradation (MQT 21); and perovskite stability test, which covers: thermal, irradiation, electrical and environmental scenarios (PACT scenario described by IEC as of the date of this application).
[0579] Reference numerals
[0580] Solar Panel 10
[0581] Solar Module 12
[0582] First surface 14
[0583] Second surface 16
[0584] Edge 18
[0585] Frame 20
[0586] Edge seal 22
[0587] Junction Box 24
[0588] Electrical connection 26
[0589] Electrical lead 28
[0590] Coating (e.g. AR coating / anti-reflective coating) 30
[0591] First substrate 32
[0592] The first surface 34 of the first substrate
[0593] The second surface 36 of the first substrate
[0594] First package (middle layer) 38
[0595] Solar cell 40, 40'
[0596] Second package 48
[0597] Second substrate 42
[0598] The first side 44 of the second substrate
[0599] The second side 46 of the second substrate
[0600] Holes for leads 48
[0601] Functional Materials 50
[0602] Electrode 52
[0603] Modification coverage 54
[0604] Third package 56
Claims
1. A solar module comprising: a) at least one solar cell having a functional material arranged in electrical communication with an electrical wiring assembly, wherein, The functional materials of solar cells are constructed to capture photons and convert them into electrons. b) a first substrate constructed as a transparent material; c) a second substrate configured to be in spaced relationship with the first substrate such that the functional material is configured to be located between the first substrate and the second substrate, and d) an encapsulant configured to be located between the first substrate and the solar cell and between the second substrate and the solar cell, and configured to keep the solar cell fixed between the first substrate and the second substrate; e) wherein at least one of the first substrate and the second substrate is a borosilicate glass composition comprising: at least 75 mol % SiO2; At least 10 mol % B2O3; and The amount of Al2O3 is such that the sum of SiO2, B2O3 and Al2O3 is at least 90 mol%.
2. The solar module according to claim 1, wherein: The borosilicate glass composition also includes a liquidus viscosity of at least 200 kP and no more than 500 kP.
3. The solar module according to claim 1 or 2, wherein: The borosilicate glass composition also includes a liquidus viscosity greater than 500 kP.
4. The solar module according to any one of claims 1 to 3, wherein: The borosilicate glass composition includes a viscosity of 200P at 1725°C or less.
5. The solar module according to any one of claims 1 to 4, wherein: The first substrate is a borosilicate glass composition, and the second substrate is a soda-lime-silicate glass.
6. The solar module according to any one of claims 1 to 4, wherein: The first substrate is a borosilicate glass composition, and the second substrate is a flexible glass rod.
7. The solar module according to any one of claims 1 to 4, wherein: The first substrate is soda lime silicate glass.
8. The solar module according to any one of claims 1 to 4, wherein: Both the first substrate and the second substrate are borosilicate glass compositions.
9. The solar module according to any one of claims 1 to 4, wherein: The first substrate and the second substrate have the same thickness.
10. The solar module according to any one of claims 1 to 4, wherein: The first substrate and the second substrate have different thicknesses.
11. The solar module according to any one of claims 1 to 4, wherein: The first substrate is thicker than the second substrate.
12. The solar module according to any one of claims 1 to 4, wherein: The first substrate is thinner than the second substrate.
13. The solar module according to any one of claims 1 to 12, wherein: The encapsulant is selected from: OCA, adhesive, polymer interlayer, ionomer, and / or combinations thereof.
14. The solar module of any one of claims 1 to 13, further comprising electrical connections configured to receive and transmit electrons from the solar cells to the junction box.
15. The solar module of any one of claims 1 to 14, further comprising a seal configured to sealingly engage the at least one solar module.
16. The solar module according to any one of claims 1 to 15, wherein: The second substrate is constructed of a transparent, translucent or opaque material.
17. The solar module according to any one of claims 1 to 4, wherein: At least one of the first and second substrates is a polymer or resin material.
18. The solar module according to any one of claims 1 to 17, wherein: The module includes a frame and a gasket configured to sealingly engage the solar module.
19. The solar module according to any one of claims 1 to 18, further configured as a solar panel.
20. The solar module of any one of claims 1 to 19, further comprising an anti-reflective coating on the first surface of the first substrate.
21. The solar module according to any one of claims 1 to 20, wherein: The electrical connections are configured to transfer electrons from the solar cells to the junction box or battery pack.
22. The solar module of any one of claims 1 to 21, the borosilicate glass composition further comprising about 2 mol% to about 8 mol% Na2O.
23. The solar module of any one of claims 1 to 22, the borosilicate glass composition further comprising about 1 mol% to about 4 mol% K2O.
24. The solar module according to any one of claims 1 to 21, a borosilicate glass composition, wherein: The total amount of Na2O and K2O is at least 4 mol%.
25. The solar module according to any one of claims 1 to 24, wherein the borosilicate glass composition further comprises at least one of MgO or CaO, wherein: The total amount of MgO and CaO is at most 5 mol%.
26. The solar module according to any one of claims 1 to 24, wherein the borosilicate glass composition further comprises: The total amount of Na2O, K2O, MgO and CaO is at least 7 mol%.
27. The solar module according to any one of claims 1 to 26, wherein the borosilicate glass composition further comprises P2O5, wherein P2O5 may be present in amounts up to 4 mol%.
28. The solar module of any one of claims 1 to 27, the borosilicate glass composition further comprising from about 0.05 mol% to about 0.25 mol% SnO2.
29. The solar module of any one of claims 1 to 28, the borosilicate glass composition further comprising 0.05 mol% to 0.50 mol% Fe2O3.
30. The solar module of any one of claims 1 to 29, wherein the borosilicate glass composition further comprises less than 2.4 g / cm 3 density.
31. The solar module of any one of claims 1 to 30, the borosilicate glass composition further comprising a strain point of about 500°C to about 560°C.
32. The solar module of any one of claims 1 to 30, the borosilicate glass composition further comprising an annealing point of about 550°C to about 590°C.
33. A substrate in a solar module, comprising: Comprising borosilicate glass and an outer sheet having a thickness of at least 200 μm and not more than 1 cm, wherein The composition of borosilicate glass includes, in terms of constituent oxides, SiO2, B2O3, Al2O3, one or more alkali metal oxides, and one or more divalent cation oxides selected from the group consisting of MgO, CaO, SrO, BaO, and ZnO, wherein, in terms of molar percentage of SiO2 and B2O3 oxides, the concentration is greater than or equal to 11 mol % and less than or equal to 16 mol % B2O3, greater than or equal to 2 mol % and less than or equal to 6 mol % Al2O3, and The total amount of Na2O, K2O, MgO and CaO is greater than or equal to 7.0 mol%, Wherein, the one or more alkali metal oxides, Al2O3 and the one or more alkaline earth metal oxides satisfy the following relationship: (R2O+R'O)≥Al2O3 0.80<(1-[(2R2O+2R'O) / (SiO2+2Al2O3+2B2O3)])<0.93, wherein R2O is the sum of the concentrations of the one or more alkali metal oxides, and R'O is the sum of the concentrations of the one or more alkaline earth metal oxides; An inner ply comprising a second glass having a composition different from that of the borosilicate glass of the outer ply, wherein the inner ply reinforces the outer ply so that the outer ply is stiffened against bending forces applied thereto, and wherein the composition of the second glass is selected from the group consisting of a soda-lime-silicate glass composition, an aluminosilicate glass composition, an alkali aluminosilicate glass composition, an alkali-containing borosilicate glass composition, an alkali aluminophosphosilicate glass composition, and an alkali aluminoborosilicate glass composition; An intermediate layer connecting the inner and outer sheets, wherein the intermediate layer is a polymer and inhibits the propagation of cracks from the outer sheet to the inner sheet.
34. The substrate of claim 33, wherein When the glass composition of the outer layer sheet of borosilicate glass is formed into 100 pieces with a thickness of 1 mm and a main surface of 2 x 2 cm 2 When a polished flat sample of a certain area is tested at 25°C, 50% relative humidity using a square-based 136° four-sided pyramid Vickers indenter directed vertically to the center of the major surface and the indenter is quasi-statically displaced at a rate of 60 μm per second to an indentation load of a maximum force of 3 kg for 10 seconds, tending to all cracks from the indenter extending radially and / or laterally through the sample are contained in the crack loop.
35. The substrate of claim 34, wherein When the sample was rapidly cooled from 25°C to 1°C by placing it in cold water, cracks that tended to extend radially and / or transversely through the sample did not propagate beyond the crack loop.
36. The substrate according to any one of claims 33 to 35, wherein Most of the crack loops of the samples were circular and had a radius less than 1 mm.
37. The substrate according to any one of claims 33 to 36, wherein The borosilicate glass of the outer layer comprises at least 74 mol % SiO2 and at least 10 mol % B2O3; and wherein the sum of SiO2, B2O3 and Al2O3 contained in the borosilicate glass of the outer layer is at least 90 mol %.
38. The substrate according to any one of claims 33 to 37, wherein The outer sheet is thicker than the inner sheet, and wherein the second glass of the inner sheet is chemically strengthened by an ion exchange process.
39. The substrate according to any one of claims 33 to 38, wherein The thickness of the outer sheet is a first thickness, wherein the first thickness is at least 2 mm, and wherein the inner sheet has a second thickness less than 2 mm.
40. The substrate according to any one of claims 33 to 39, wherein The ratio of the first thickness to the sum of the first and second thicknesses is at least 0.
7.
41. The substrate according to any one of claims 33 to 40, wherein The first thickness is at least 3.3 mm, and the second thickness is 0.7 mm or less.
42. The substrate of any one of claims 33 to 41, wherein The visible light transmission through the article is at least 73% as measured according to ISO 13837A; and wherein the total solar transmittance through the article is 90% or less as measured according to ISO 13837A.
43. The substrate according to any one of claims 33 to 42, wherein The major surface of the outer sheet farthest from the inner sheet and the major surface of the inner sheet farthest from the outer sheet both exhibit an optical distortion of at most 200 millidiopters as measured by an optical distortion tester in accordance with ASTM 1561 using transmission optics.
44. The substrate of any one of claims 33 to 43, wherein The middle layer is selected from the group consisting of polyvinyl butyral (PVB), acoustic PVB (APVB), ionomer, ethylene vinyl acetate (EVA), thermoplastic polyurethane (TPU), polyester (PE), polyethylene terephthalate (PET), and combinations thereof; and wherein the thickness of the middle layer ranges from 0.5 mm to 2.5 mm.
45. The substrate of any one of claims 33 to 43, wherein The outer sheet and the inner sheet are formed in a pair, wherein the outer sheet includes a first depth of curvature of at least 2 mm, wherein the inner sheet includes a second depth of curvature of at least 2 mm, and wherein the first depth of curvature differs from the second depth of curvature by within 10%.
46. The substrate of any one of claims 33 to 45, wherein The outer sheet includes a depth of curvature of at least 2 mm, and wherein the inner sheet has stress from being cold formed to conform to the outer sheet.
47. The substrate of any one of claims 33 to 46, wherein The glass of the borosilicate glass composition with outer flakes has a liquidus viscosity greater than or equal to 500 kilopoise, and wherein the glass of the borosilicate glass composition with outer flakes has a 200 poise temperature less than or equal to 1725°C.
48. The substrate of any one of claims 33 to 47, wherein When the article is installed in a vehicle, the outer layer is configured as an outer panel of the inner layer.
49. The substrate of any one of claims 33 to 48, wherein Borosilicate glass has a low temperature thermal expansion coefficient greater than 3.25 ppm / °C and less than 8.7 ppm / °C.
50. The substrate of any one of claims 33 to 49, wherein Thickness greater than or equal to 2.0 mm.
51. The substrate of any one of claims 33 to 50, wherein The composition of the borosilicate glass includes greater than or equal to 4 mol % and less than or equal to 6 mol % Na2O.
52. The substrate of any one of claims 33 to 51, wherein The composition of borosilicate glass includes: Greater than or equal to 3 mol % and less than or equal to 5 mol % Al2O3; and Greater than or equal to 12 mol % and less than or equal to 16 mol % B2O3.
53. The substrate of any one of claims 33 to 52, wherein At least one of the following conditions exists: The composition of the borosilicate glass includes greater than or equal to 0.03 mol % and less than or equal to 0.5 mol % Fe2O3, and The thickness is less than or equal to 3.3 mm and the outer sheet has a transmittance greater than or equal to 90% and less than or equal to 92.5% over the entire visible spectrum.
54. The substrate of any one of claims 33 to 53, wherein The outer sheet is made of borosilicate glass.
Citation Information
Patent Citations
Method of decorating chemically strengthened glass
EP2617690B1
Fusion formable and steam strengthenable glass compositions with platinum compatibility
US11339084B2
Decorative porous inorganic layer compatible with ion exchange processes
US20160002104A1
Laminate having organic ink decoration and high impact resistance
US20200171800A1
Polymer-based portion, adhesive, foldable apparatus, and methods of making
US20210108077A1